Glass containers having improved strength and improved damage resistance - Patents.com

JP7668851B2Active Publication Date: 2025-04-25CORNING INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023135452
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2013-11-08
Filing Date
2023-08-23
Publication Date
2025-04-25
Estimated Expiration
2033-11-22

AI Technical Summary

Technical Problem

Glass containers used for pharmaceutical packaging face issues with delamination and mechanical damage, particularly due to high throughput production processes, leading to potential sterility compromise and package destruction.

Method used

The glass containers feature a thickened portion with a compressive stress layer and a smooth coating, enhancing resistance to delamination and mechanical strength, while maintaining chemical durability.

Benefits of technology

The solution provides improved resistance to delamination and mechanical strength, ensuring the integrity and sterility of pharmaceutical containers under handling and storage conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000071_0000
    Figure 00000071_0000
  • Figure 00000072_0000
    Figure 00000072_0000
  • Figure 00000072_0001
    Figure 00000072_0001
Patent Text Reader

Abstract

To provide glass containers that have at least two performance attributes selected from resistance to delamination, improved strength, and increased damage resistance.SOLUTION: In one embodiment, a glass container may include a body having an inner surface, an outer surface and a wall thickness extending between the outer surface and the inner surface. A compressively stressed layer may extend from the outer surface of the body into the wall thickness. The compressively stressed layer may have a surface compressive stress greater than or equal to 150 MPa. A lubricous coating may be positioned around at least a portion of the outer surface of the body. The outer surface of the body with the lubricous coating may have a coefficient of friction less than or equal to 0.7.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Cross - reference to related applications

[0001] This application is a divisional application of Japanese Patent Application No. 2022 - 22733, which is filed and patented claiming priority from U.S. Provisional Patent Application No. 61 / 731,767, filed on November 30, 2012, entitled "Glass Containers With Improved Attributes", U.S. Patent Application No. 13 / 912,457, filed on June 7, 2013, entitled "Delamination Resistant Glass Containers", U.S. Patent Application No. 13 / 780,754, filed on February 28, 2013, entitled "Glass Articles With Low - Friction Coatings", and U.S. Patent Application No. 14 / 075,630, filed on November 8, 2013, entitled "Glass Containers With Improved Strength and Improved Damage Tolerance" under 35 U.S.C. § 119.

Technical Field

[0002] This specification generally relates to glass containers, and more particularly to glass containers used for storing pharmaceutical formulations.

Background Art

[0003] Historically, glass has been used as a preferred material for packaging pharmaceuticals due to its hermeticity, optical transparency, and excellent chemical durability compared to other materials. In particular, the glass used for packaging pharmaceuticals must have sufficient chemical durability so as not to affect the stability of the pharmaceutical formulation contained therein. Glasses with suitable chemical durability include glass compositions in ASTM standard "Type IA" and "Type IB" glass compositions, which have a track record regarding chemical durability.

[0004] Type IA and Type IB glass compositions are commonly used in pharmaceutical packaging, but they have several drawbacks, such as a tendency for glass microparticles to detach or "delamination" to occur on the inner surface of the pharmaceutical packaging after exposure to pharmaceutical solutions.

[0005] In particular, the high processing speeds during production and filling of glass pharmaceutical packages can cause the packages to come into contact with processing equipment, handling equipment, and / or other packages, potentially resulting in mechanical damage such as scratches on the package surface. This mechanical damage can significantly reduce the strength of the glass pharmaceutical package, increasing the likelihood of cracks spreading in the glass, potentially compromising the sterility of the pharmaceuticals contained within the package, or even causing the package to completely break. [Overview of the project] [Problems that the invention aims to solve]

[0006] Therefore, there is a need for alternative glass containers used as pharmaceutical packaging that exhibit a combination of improved resistance to delamination, high strength, and / or damage resistance. [Means for solving the problem]

[0007] According to one embodiment, the glass container may comprise a body having an inner surface, an outer surface, and a thickened portion extending between the outer and inner surfaces. A compressive stress layer may extend from the outer surface of the body into the thickened portion. The compressive stress layer may have a surface compressive stress of 150 MPa or more. A smooth coating may be located around at least a portion of the outer surface of the body. The outer surface of the body with the smooth coating may have a coefficient of friction of 0.7 or less.

[0008] In other embodiments, the glass container may comprise a body having an inner surface, an outer surface, and a thickened portion extending between the outer and inner surfaces. The body may be formed from Type 1, Class B glass conforming to ASTM standard E438-92. A compressive stress layer may extend from the outer surface of the body into the thickened portion. The compressive stress layer may have a surface compressive stress of 150 MPa or more. A smooth coating may be located around at least a portion of the outer surface of the body. The outer surface of the body with the smooth coating may have a coefficient of friction of 0.7 or less.

[0009] Additional characteristics and advantages of the embodiments of the glass containers described herein are described in the following embodiments for carrying out the invention, which will be readily apparent to a person skilled in the art to some extent by this description, or will be recognized by a person skilled in the art by carrying out the embodiments described herein, including the following embodiments for carrying out the invention, the claims and the accompanying drawings.

[0010] It should be understood that both the above summary and the following embodiments for carrying out the invention describe various embodiments and are intended to provide an overview or framework for understanding the nature and features of the claimed subject matter. The accompanying drawings are included to further enhance the understanding of the various embodiments and are incorporated into and constitute part of this specification. The drawings illustrate the various embodiments described herein and, together with their descriptions, are useful in explaining the principles and operation of the claimed subject matter. [Brief explanation of the drawing]

[0011] [Figure 1] A schematic diagram of a cross-section of a glass container according to one or more embodiments described herein is shown. [Figure 2] Figure 1 schematically illustrates the compressive stress layer in a portion of the sidewall of the glass container. [Figure 3] A schematic diagram shows a portion of the sidewall of a glass container formed from laminated glass. [Figure 4] A schematic diagram of a horizontal compression apparatus for testing the horizontal compressive strength of glass containers is shown. [Figure 5] A schematic diagram illustrates a glass container having a barrier coating located on at least a portion of the inner surface of the glass container according to one or more embodiments shown and described herein. [Figure 6] A schematic diagram shows a portion of the sidewall of a glass container with continuous layer homogeneity. [Figure 7] A schematic diagram shows a portion of the sidewall of a glass container having continuous surface homogeneity. [Figure 8] A schematic diagram shows a glass container having a smooth coating on its outer surface. [Figure 9] A schematic diagram shows a test fixture for measuring the coefficient of friction between two glass containers. [Figure 10] A schematic diagram shows an apparatus for evaluating the thermal stability of coatings applied to glass containers. [Figure 11] The light transmittance data measured in the 400-700 nm visible light spectrum for coated and uncoated vials relating to one or more embodiments shown and described herein is shown in the figure. [Figure 12A] A schematic diagram illustrates a robust organic smooth coating located on the outer surface of a glass container according to one or more embodiments shown and described herein. [Figure 12B] A schematic diagram illustrates a robust organic smooth coating located on the outer surface of a glass container according to one or more embodiments shown and described herein. [Figure 13] The chemical structures of diamine monomers that can be used to form polyimide coating layers are schematically illustrated. [Figure 14] The chemical structures of other diamine monomers that can be used to form polyimide coating layers are schematically illustrated. [Figure 15]The chemical structures of several monomers that can be used as polyimide coatings applied to glass containers are schematically illustrated. [Figure 16] The effects of composition and temperature on volatilization of Type IB glass and non-boron-containing glass are illustrated. [Figure 17] A schematic diagram illustrates the reaction steps of a silane bonded to a substrate, relating to one or more embodiments shown and described herein. [Figure 18] A schematic diagram illustrates the reaction steps of a polyimide bonded to a silane, relating to one or more embodiments described herein. [Figure 19] The probability of failure in a horizontal compression test on a vial, depending on the applied load, according to one or more embodiments shown and described herein, is illustrated. [Figure 20] This specification includes a table reporting the load and measured coefficient of friction for Type IB glass vials and vials formed from ion-exchanged and coated reference glass compositions relating to one or more embodiments shown and described herein. [Figure 21] The probability of failure, depending on the applied stress in four-point bending, is illustrated for tubes formed from a reference glass composition in the raw state, ion-exchange state (uncoated), ion-exchange state (coated and abraded), and ion-exchange state (uncoated and abraded), as well as for tubes formed from Type IB glass in the raw state and ion-exchange state, according to one or more embodiments shown and described herein. [Figure 22] The following schematic diagram illustrates gas chromatography-mass spectrometer output data for APS / Novastrat® 800 coatings relating to one or more embodiments shown and described herein. [Figure 23] The gas chromatography-mass spectrometer output data for DC806A coatings relating to one or more embodiments shown and described herein are shown. [Figure 24] This table reports different smooth coating compositions tested under freeze-drying conditions, relating to one or more embodiments shown and described herein. [Figure 25] This chart reports the coefficient of friction for uncoated glass vials and vials with silicone resin coatings, tested in vial overlay fixtures relating to one or more embodiments shown and described herein. [Figure 26] This chart reports the coefficient of friction for vials coated with APS / PMDA-ODA (poly(4,4'-oxydiphenylene-pyromellitoimide) polyimide coating) and rubbed multiple times with different loads in a vial overlay fixture, relating to one or more embodiments shown and described herein. [Figure 27] This chart reports the coefficient of friction for vials coated with APS coating and rubbed multiple times under different loads in a vial overlay fixture, relating to one or more embodiments shown and described herein. [Figure 28] This chart reports the coefficient of friction for vials coated with APS / PMDA-ODA (poly(4,4'-oxydiphenylene-pyromellitoimide) polyimide coating) according to one or more embodiments shown and described herein, after being exposed to 300°C for 12 hours and then rubbed multiple times with different loads in a vial stacking fixture. [Figure 29] This chart reports the coefficient of friction for vials coated with APS coating, exposed to 300°C for 12 hours, and then rubbed multiple times with different loads in a vial overlay fixture, according to one or more embodiments shown and described herein. [Figure 30]This chart reports the coefficient of friction for Type IB vials coated with PMDA-ODA (poly(4,4'-oxydiphenylene-pyromellitoimide) polyimide coating) and rubbed multiple times with different loads in a vial overlay fixture, according to one or more embodiments shown and described herein. [Figure 31] The coefficient of friction before and after freeze-drying is shown for vials coated with APS / Novastrat® 800 according to one or more embodiments shown and described herein. [Figure 32] The coefficient of friction before and after autoclave is shown for vials coated with APS / Novastrat® 800 according to one or more embodiments shown and described herein. [Figure 33] The coefficient of friction for coated and uncoated glass containers exposed to different temperature conditions is illustrated. [Figure 34] The probability of failure in a horizontal compression test on a vial, depending on the applied load, according to one or more embodiments shown and described herein, is illustrated. [Figure 35] This table shows the change in the coefficient of friction associated with changes in the composition of the coupling agent for the smooth coating applied to the glass containers described herein. [Figure 36] The coefficient of friction, applied force, and frictional force against the coated glass container before and after the removal of the exothermic substance are illustrated. [Figure 37] The coefficient of friction, applied force, and frictional force on the coated glass container before and after the removal of the exothermic substance are illustrated in one or more embodiments shown and described herein. [Figure 38] The probability of failure in a horizontal compression test on a vial, depending on the applied load, according to one or more embodiments shown and described herein, is illustrated. [Figure 39]The coefficient of friction, applied force, and frictional force on the coated glass container before and after the removal of the exothermic substance are illustrated in one or more embodiments shown and described herein. [Figure 40] The coefficient of friction, applied force, and force due to friction on a coated glass container under different exothermic substance removal conditions are illustrated. [Figure 41] The coefficient of friction after changing the number of heat treatments for one or more embodiments shown and described herein is illustrated. [Figure 42] The light transmittance data measured in the 400-700 nm visible light spectrum for coated and uncoated vials relating to one or more embodiments shown and described herein is shown in the figure. [Figure 43] The coefficient of friction, applied force, and frictional force on the coated glass container before and after the removal of the exothermic substance are illustrated in one or more embodiments shown and described herein. [Figure 44] The probability of failure in a horizontal compression test on a vial, depending on the applied load, according to one or more embodiments shown and described herein, is illustrated. [Figure 45] This is a micrograph of a coating relating to one or more embodiments shown and described herein. [Figure 46] This is a micrograph of a coating relating to one or more embodiments shown and described herein. [Figure 47] This is a micrograph of a coating relating to one or more embodiments shown and described herein. [Figure 48] The coefficient of friction, degree of scratch penetration, applied vertical force, and frictional force (y-coordinate) are shown for the plain coated vial of the comparative example, corresponding to the length of the applied scratch (x-coordinate). [Figure 49]The coefficient of friction, degree of scratch penetration, applied normal force, and frictional force (y-coordinate) for the heat-treated vial of the comparative example, corresponding to the length of the applied scratch (x-coordinate), are illustrated. [Figure 50] The coefficient of friction, degree of scratch penetration, applied vertical force, and frictional force (y-coordinate) are shown for the plain coated vial of the comparative example, corresponding to the length of the applied scratch (x-coordinate). [Figure 51] The coefficient of friction, degree of scratch penetration, applied normal force, and frictional force (y-coordinate) for the heat-treated vial of the comparative example, corresponding to the length of the applied scratch (x-coordinate), are illustrated. [Figure 52] The coefficient of friction, degree of scratch penetration, applied perpendicular force, and frictional force (y-coordinate) are illustrated for a vial with a tack accelerator layer in its uncoated state, depending on the length of the applied scratch (x-coordinate). [Figure 53] The coefficient of friction, degree of scratch penetration, applied perpendicular force, and frictional force (y-coordinate) are illustrated for a vial with a tack accelerator layer in its uncoated state, depending on the length of the applied scratch (x-coordinate). [Figure 54] The friction coefficient, scratch penetration degree, applied vertical force, and frictional force (y-coordinate) for the vial with the adhesion promoter layer after removal of the heat-generating substance are illustrated according to the length of the applied scratch (x-coordinate). [Figure 55] The friction coefficient, scratch penetration degree, applied vertical force, and frictional force (y-coordinate) for the vial with the adhesion promoter layer after removal of the heat-generating substance are illustrated according to the length of the applied scratch (x-coordinate). [Figure 56] The probability of failure in a horizontal compression test for a vial having a tack accelerator layer, depending on the applied load, according to one or more embodiments shown and described herein, is illustrated. [Figure 57] The probability of failure in a horizontal compression test for a vial having a tack accelerator layer, depending on the applied load, according to one or more embodiments shown and described herein, is illustrated. [Modes for carrying out the invention]

[0012] Herein, embodiments of glass containers illustrated in the attached drawings will be described in more detail. The same reference numerals will always be used throughout the drawings whenever possible for reference to identical or similar parts. The glass containers described herein have at least two performance characteristics selected from resistance to delamination, improved strength, and high damage resistance. For example, a glass container may have resistance to delamination and improved strength; improved strength and high damage resistance; or a combination of resistance to delamination and high damage resistance. In a particular embodiment, the glass container described herein has at least two performance characteristics selected from resistance to delamination, improved strength, and high damage resistance. In one embodiment, the glass container may comprise a body having an inner surface, an outer surface, and a thickened portion extending between the outer and inner surfaces. A compressive stress layer may extend from the outer surface of the body into the thickened portion. The compressive stress layer may have a surface compressive stress of 150 MPa or more. A smooth coating may be located around at least a portion of the outer surface of the body. The outer surface of the body with the smooth coating may have a coefficient of friction of 0.7 or less. Glass containers having various combinations of resistance to delamination, improved strength, and high damage resistance will be described in more detail herein with specific reference to the accompanying drawings.

[0013] In the embodiments of the glass compositions described herein, the concentrations of constituent components (e.g., SiO2, Al2O3, B2O3, etc.) are expressed in mole percent (mol.%) based on the oxide, unless otherwise specified.

[0014] The term "substantially absent" means, when used to describe the concentration and / or absence of a particular component in a glass composition, that component has not been intentionally added to the glass composition. However, a glass composition may contain trace amounts of a component as a contaminant or inclusion, in amounts less than 0.1 mol.%.

[0015] As used herein, the term “chemical durability” refers to the resistance of a glass composition to degradation when exposed to specific chemical conditions. Specifically, the chemical durability of the glass compositions described herein may be evaluated according to three established material test standards: DIN 12116, dated March 2001, entitled “Testing of glass—Resistance to attack by a boiling aqueous solution of hydrochloric acid—Method of test and classification”; ISO 695:1991, entitled “Glass—Resistance to attack by a boiling aqueous solution of mixed alkali—Method of test and classification”; ISO 720:1985, entitled “Glass—Hydrolytic resistance of glass grains at 121 degrees C—Method of test and classification”; and ISO 719:1985, entitled “Glass—Hydrolytic resistance of glass grains at 98 degrees C—Method of test and classification”. Each standard and its classification are described in further detail herein. Alternatively, the chemical durability of glass compositions is evaluated using the USP, titled "Surface Glass Test," which assesses the durability of the glass surface. <660> , and / or may be evaluated in accordance with European Pharmacopoeia 3.2.1, titled "Glass Containers For Pharmaceutical Use".

[0016] "Distortion point" and "T 歪み The term "glass viscosity" is used herein to mean a viscosity of 3 × 10 14 This refers to the temperature at which the Poise temperature is reached.

[0017] As used herein, the term "softening point" refers to a point where the viscosity of the glass composition is 1 × 10⁻⁶. 7.6 This refers to the temperature at which the Poise temperature is reached.

[0018] Conventional glass containers used for storing pharmaceuticals and / or other consumable products can be damaged during filling, packaging, and / or transport. Such damage may take the form of surface abrasions, scratches, and / or scuffs, and if excessively deep, can lead to perforations or even complete breakage of the glass container, thereby damaging the contents of the glass package.

[0019] In addition, certain conventional glass containers, especially those made of alkali borosilicate glass, are prone to delamination. Delamination refers to the phenomenon in which glass particles are released from the surface of the glass through a series of leaching, erosion, and / or weathering reactions. Typically, these glass particles are silica-rich glass flakes brought from the inner surface of the package by the leaching of modifying agent ions into the solution contained in the package. These flakes are generally about 1 nm to 2 micrometers (μm) thick and can be more than 50 μm wide. Since these flakes consist mainly of silica, they generally do not decompose further after being released from the surface of the glass.

[0020] Previously, it was hypothesized that delamination was caused by phase separation that occurs in alkali borosilicate glass when the glass is exposed to the high temperatures used when reshaping the glass into a container.

[0021] However, currently, the delamination of silica-rich glass flakes from the inner surface of glass containers is thought to be due to the compositional characteristics of the glass container immediately after its formation. Specifically, due to the high silica content of alkali borosilicate glass, the melting and molding temperatures of the glass are relatively high. However, the alkali and borate components in the glass composition melt and / or volatilize at considerably lower temperatures. In particular, the borate species in the glass are highly volatile and vaporize from the glass surface at the high temperatures required for molding and reshaping the glass.

[0022] Specifically, the glass stock is reshaped into a glass container at high temperatures and in a flame. Higher temperatures are required for higher apparatus speeds, which increases the vaporization of volatile borate species from parts of the glass surface. If this evaporation occurs within the internal space of the glass container, the volatile borate species reattach to other areas of the glass container surface, causing compositional heterogeneity on the glass container surface, particularly in near-surface areas inside the glass container (i.e., areas on the inner surface of the glass container or areas adjacent to the inner surface of the glass container). For example, if one end of the glass tube is sealed to form the bottom or floor of the container, borate species can vaporize from the bottom of the tube and reattach to other parts of the tube. Evaporation of material from the heel and floor of the container is particularly pronounced because these areas of the container are most extensively reshaped and therefore exposed to the highest temperatures. As a result, areas of the container exposed to higher temperatures may have a silica-rich surface. Other areas of the container that are prone to boron adhesion may have a boron-rich layer on their surface. In regions where boron is likely to adhere, such as those above the annealing point of the glass composition but below the highest temperature the glass experiences during reshaping, boron incorporation into the glass surface can occur. The solution contained in the container may leach boron from the boron-rich layer. As the boron-rich layer leaches from the glass, a high-silica glass network (gel) remains, which swells and deforms during hydration, eventually peeling off from the surface.

[0023] The glass containers described herein mitigate at least two of the aforementioned problems. Specifically, the glass containers have at least two performance characteristics selected from resistance to delamination, improved strength, and high damage resistance. For example, the glass containers may have resistance to delamination and improved strength; improved strength and high damage resistance; or a combination of resistance to delamination and high damage resistance. Each performance characteristic and the methods for achieving these performance characteristics are described in further detail herein.

[0024] Referring here to Figures 1 and 2, one embodiment of a glass container 100 for storing pharmaceutical formulations is schematically illustrated in cross-section. The glass container 100 generally comprises a body 102. The body 102 extends between the inner surface 104 and the outer surface 106 and substantially encloses the internal space 108. In the embodiment of the glass container 100 shown in Figure 1, the body 102 generally comprises a wall portion 110 and a floor portion 112. The wall portion 110 continues to the floor portion 112 via a heel portion 114. The body 102 has a thickened portion T extending between the inner surface 104 and the outer surface 106, as shown in Figure 1. W It holds.

[0025] Although the glass container 100 is shown in Figure 1 as having a specific shape (i.e., a vial), it should be understood that the glass container 100 may have other shapes, including but not limited to Vacutainers®, cartridges, syringes, ampoules, bottles, flasks, small bottles, tubes, beakers, etc. Furthermore, it should be understood that the glass containers described herein, while not particularly limited, can be used for a variety of applications, including pharmaceutical packaging and beverage containers. strength Referring further to Figures 1 and 2, in some embodiments described herein, the body 102 has a thickness T from the outer surface 106 of the body 102 to the layer depth DOL. WThe glass container 100 is equipped with a compressive stress layer 202 that extends from at least the outer surface 106 of the main body 102. The compressive stress layer 202 generally increases the strength of the glass container 100 and also improves its resistance to damage. Specifically, a glass container having a compressive stress layer 202 can generally withstand severe surface damage such as scratches and chips without breaking, compared to an untempered glass container, because the compressive stress layer 202 reduces the propagation of cracks in the compressive stress layer 202 from surface damage.

[0026] In the embodiments described herein, the layer depth of the compressive stress layer may be about 3 μm or more. In some embodiments, the layer depth may be greater than 10 μm, or even greater than 20 μm. In some embodiments, the layer depth may be about 25 μm or more, or even greater than about 30 μm. For example, in some embodiments, the layer depth may be about 25 μm or more and about 150 μm or less. In some other embodiments, the layer depth may be about 30 μm or more and about 150 μm or less. In yet another embodiment, the layer depth may be about 30 μm or more and about 80 μm or less. In some other embodiments, the layer depth may be about 35 μm or more and about 50 μm or less.

[0027] The compressive stress layer 202 generally has a surface compressive stress of 150 MPa or more (i.e., compressive stress measured on the outer surface 106). In some embodiments, the surface compressive stress may be 200 MPa or more, or even 250 MPa or more. In some embodiments, the surface compressive stress may be 300 MPa or more, or even 350 MPa or more. For example, in some embodiments, the surface compressive stress may be about 300 MPa or more and about 750 MPa or less. In some other embodiments, the surface compressive stress may be about 400 MPa or more and about 700 MPa or less. In yet another embodiment, the surface compressive stress may be about 500 MPa or more and about 650 MPa or less. Stress in ion-exchange glass articles can be measured with an FSM (Fundamental Stress Meter) instrument. This instrument combines light entering and leaving a birefringent glass surface. The measured birefringence is then associated with stress via material constants, stress optical coefficients, or photoelastic coefficients (SOC or PEC). Two parameters are obtained: maximum surface compressive stress (CS) and layer replacement depth (DOL). Alternatively, compressive stress and layer depth can be measured using refractive near-field stress measurement techniques.

[0028] The compressive stress layer 202 extends from the outer surface 106 to the thickened portion T of the main body 102. W As shown and described herein, the body 102 extends from the inner surface 104 to the thick portion T of the body 102, in some embodiments. W It should be understood that a second compressive stress layer extending within may be further provided. In this embodiment, the layer depth and surface compressive stress of the second compressive stress layer are determined by the thickness T of the main body 102. W A mirror image of the compressive stress layer 202 can be formed with respect to its centerline.

[0029] A compressive stress layer 202 can be formed in the body 102 of the glass container 100 by utilizing a number of different techniques. For example, in embodiments where the body 102 is formed from ion-exchangeable glass, the compressive stress layer 202 can be formed in the body 102 by ion exchange. In these embodiments, the compressive stress layer 202 is formed by placing the glass container in a molten salt bath to promote the exchange of relatively large ions in the molten salt with relatively small ions in the glass. A number of different exchange reactions can be used to achieve the compressive stress layer 202. In one embodiment, the bath may contain a molten KNO3 salt, while the glass on which the glass container 100 is formed contains lithium ions and / or sodium ions. In this embodiment, potassium ions in the bath are exchanged with relatively small lithium and / or sodium ions in the glass, thereby forming the compressive stress layer 202. In another embodiment, the bath may contain a NaNO3 salt, and the glass on which the glass container 100 is formed contains lithium ions. In this embodiment, sodium ions in the bath are exchanged with relatively small lithium ions in the glass, thereby forming the compressive stress layer 202.

[0030] In a particular embodiment, the compressive stress layer 202 can be formed by immersing a glass container in a molten salt bath of 100% KNO3 or a molten salt bath of a mixture of KNO3 and NaNO3. For example, in one embodiment, the molten salt bath can include KNO3 with up to about 10% NaNO3. In this embodiment, the glass from which the container is formed may contain sodium ions and / or lithium ions. The temperature of the molten salt bath can be 350°C or higher and 500°C or lower. In some embodiments, the temperature of the molten salt bath can be 400°C or higher and 500°C or lower. In still other embodiments, the temperature of the molten salt bath can be 450°C or higher and 475°C or lower. The glass container can be held in the molten salt bath for a time sufficient to facilitate the exchange of relatively large ions in the salt bath with relatively small ions in the glass, thereby achieving the desired surface compressive stress and layer depth. For example, the glass can be held in the molten salt bath for a time of 0.05 hours or more up to about 20 hours or less to achieve the desired layer depth and surface compressive stress. In some embodiments, the glass container can be held in the molten salt bath for 4 hours or more and about 12 hours or less. In other embodiments, the glass container can be held in the molten salt bath for about 5 hours or more and about 8 hours or less. In an exemplary embodiment, the glass container can be ion-exchanged in a molten salt bath containing 100% KNO3 at a temperature of about 400°C or higher and about 500°C or lower over a time of about 5 hours or more and about 8 hours or less.

[0031] Typically, the ion-exchange process is carried out at a temperature below the glass's strain point (T 歪み) is carried out at a temperature lower than 150°C. However, in some embodiments, the compressive stress layer 202 is formed in a molten salt bath at a temperature above the strain point of the glass. This type of ion exchange strengthening is referred to herein as "high-temperature ion exchange strengthening". In high-temperature ion exchange strengthening, relatively small ions in the glass are exchanged for relatively large ions from the molten salt bath, as described above. When relatively small ions are exchanged for relatively large ions at a temperature above the strain point, the resulting stress is released or "relaxed". However, the replacement of small ions in the glass with large ions forms a surface layer in the glass with a lower coefficient of thermal expansion (CTE) than the rest of the glass. As the glass cools, the difference in CTE between the glass surface and the rest of the glass forms the compressive stress layer 202. This high-temperature ion exchange technique is particularly suitable for strengthening glass articles such as glass containers with complex geometric shapes, and typically shortens the strengthening process time and allows for greater layer depth compared to typical ion exchange processes.

[0032] Referring further to Figures 1 and 2, in an alternative embodiment, the compressive stress layer 202 may be introduced into the body 102 of the glass container 100 by thermal strengthening. The compressive stress layer is formed by thermal strengthening, which involves heating the glass container and cooling the glass surface with a difference compared to the bulk portion of the glass. Specifically, rapidly cooled glass has a larger molar volume (or lower density) than slowly cooled glass. Therefore, if the glass surface is intentionally cooled rapidly, the glass surface will have a larger volume, and the interior of the glass (i.e., the rest of the glass below the outer surface) will inevitably cool at a slower rate because heat must be released from the bulk portion through the surface. WBy forming a continuous gradient of molar volume (or thermal history / density) up to a certain point, a compressive stress layer 202 is formed having a radial stress profile (i.e., compressive stress decreases radially as the distance from the outer surface 106 of the main body 102 increases). The thermal strengthening process is generally faster and less expensive than the ion exchange process. However, the surface compressive stress obtained by the thermal strengthening process is generally lower than that obtained by the ion exchange process. In embodiments in which a glass container is thermally strengthened, the resulting compressive stress layer is formed in the thick portion T of the glass container. W It extends from the outer surface 106 to a layer depth DOL of 22% or less. For example, in some embodiments, the DOL is located in the thickened portion T W It could be approximately 5% to 22%, or even thicker T W It could be approximately 10% to 22%.

[0033] In a typical heat strengthening process, the glass container 100 is first heated to its softening point, and then the outer surface 106 of the main body 102 is rapidly cooled to a temperature below the softening point by a fluid such as a gas jet, creating a temperature difference between the outer surface 106 and the rest of the main body 102, as described above. This temperature difference between the outer surface 106 and the rest of the main body causes the outer surface 106 to cool the thicker portion T of the main body 102. W A compressive stress layer 202 extending therein is formed. For example, the glass may first be heated to a temperature 50-150°C higher than its softening point, and then rapidly cooled to room temperature by directing a fluid onto the glass. This fluid is not particularly limited, but may include air, oil, or an oil-based fluid.

[0034] Referring here to Figures 1-3, in other embodiments, the glass container 100 may be formed from a laminated glass tube which is convenient for forming a compressive stress layer 202 on at least the outer surface 106 of the body 102. Laminated glass generally comprises a glass core layer 204 and at least one glass cladding layer 206a. In the embodiment of the glass container 100 illustrated in Figure 3, the laminated glass comprises a pair of glass cladding layers 206a, 206b. In this embodiment, the glass core layer 204 generally comprises a first surface 205a and a second surface 205b opposite to the first surface 205a. The first glass cladding layer 206a is fused to the first surface 205a of the glass core layer 204, and the second glass cladding layer 206b is fused to the second surface 205b of the glass core layer 204. The glass cladding layers 206a and 206b are fused to the glass core layer 204 without the need for any additional materials such as adhesives or coating layers between the glass core layer 204 and the glass cladding layers 206a and 206b.

[0035] In the embodiment shown in Figure 3, the glass core layer 204 has an average core thermal expansion coefficient CTE. core It is formed from a first glass composition having the mean thermal expansion coefficient CTE, and the glass cladding layers 206a and 206b have the mean thermal expansion coefficient CTE clad It is formed from a different second glass composition having the following characteristics: In the embodiments described herein, a compressive stress layer is present in at least one of the core layer or the cladding layer, CTE core is CTE clad This is not equal to CTE. In some embodiments, CTE core is CTE clad This is greater than the compressive stress generated in the glass cladding layers 206a, 206b without ion exchange or thermal strengthening. In some other embodiments, such as when the laminated glass comprises a single core layer and a single cladding layer, CTE clad CTE coreIt may be larger than this, which generates compressive stress in the glass core layer without ion exchange or thermal strengthening.

[0036] The laminated glass tube from which the glass container is formed may be formed as described in U.S. Patent No. 4,023,953, which is incorporated herein by reference. In embodiments, the glass forming the glass core layer 204 has the mean thermal expansion coefficient CTE of one of the glass cladding layers 206a, 206b clad The average coefficient of thermal expansion CTE is larger than core It is formed from a glass composition having the following properties. Therefore, as the glass core layer 204 and the glass cladding layers 206a and 206b cool, a compressive stress layer is generated in the glass cladding layers 206a and 206b due to the difference between the average thermal expansion coefficient of the glass core layer 204 and the average thermal expansion coefficient of the glass cladding layers 206a and 206b. When a container is formed using laminated glass, these compressive stress layers extend from the outer surface 106 of the glass container 100 to the thicker part T W Extending to the thickened portion T W An inner surface 104 of the glass container is formed inside. In some embodiments, the compressive stress layer extends from the outer surface of the glass container body to a thickness T of approximately 1 μm. W The thickness of the wall extends to a layer depth of approximately 90%. W It may extend within. In some other embodiments, the compressive stress layer extends from the outer surface of the glass container body to a thickness of approximately 1 μm to T. W The thickness of the wall section T extends to a layer depth of approximately 33%. W It may extend within. In yet another embodiment, the compressive stress layer extends from the outer surface of the glass container body to a thickness of approximately 1 μm to T. W The thickness of the wall section T extends to a layer depth of approximately 10%. W It can extend within.

[0037] After forming the laminated tube, the tube can be molded into a container shape using conventional tube conversion technology.

[0038] In some embodiments in which the glass container is formed from laminated glass, at least one cladding layer forms the inner surface of the body of the glass container such that at least one glass cladding layer is in direct contact with the product stored in the glass container. In these embodiments, at least one cladding layer may be formed from a glass composition that is resistant to delamination, as described in further detail herein. It should be understood that at least one cladding layer may have a delamination coefficient of 10 or less, as described in further detail herein.

[0039] In other alternative embodiments, glass containers can be strengthened by applying a coating to the glass body. For example, a coating of an inorganic material such as titania can be applied to at least a portion of the outer surface of the glass body by soot deposition or a deposition process. The titania coating has a lower coefficient of thermal expansion than the glass to which it is deposited. During the cooling of the coating and glass, the contraction of the titania is less than that of the glass, resulting in tension on the surface of the glass body. In these embodiments, it should be understood that the surface compressive stress and layer depth are measured from the surface of the coating, not the surface of the coated glass body. While inorganic coating materials are described herein as including titania, it should be understood that other inorganic coating materials having preferably low coefficients of thermal expansion are also conceivable. In embodiments, the inorganic coating may have a coefficient of friction of less than 0.7 compared to a similarly coated container. As further described herein, the inorganic coating may also be thermally stable at temperatures above 250°C.

[0040] In other alternative embodiments, the glass body can be strengthened by a glass body having a high modulus coating with a coefficient of thermal expansion equal to or greater than that of the underlying glass body. Strengthening is achieved by the difference in elastic modulus, which imparts damage resistance, while the difference in thermal expansion brings compressive stress to the glass surface (equilibrium with tension in the high modulus coating). In these embodiments, it should be understood that the surface compressive stress and layer depth are measured from the surface of the glass body, not the surface of the coated glass body. Due to the high modulus, scratching and damage are difficult to occur, and the underlying compression layer prevents the progression of scratches and defects. Exemplary material pairs demonstrating this effect are a sapphire coating on 33-expansion borosilicate glass, or a zirconium oxide coating deposited on 51-expansion borosilicate glass.

[0041] Based on the above, it should be understood that in some embodiments, a glass container may have a compressive stress layer extending from at least the outer surface of the body into the thicker parts of the glass container. The compressive stress layer improves the mechanical strength of the glass container compared to a glass container without a compressive stress layer. The compressive stress layer also improves the damage resistance of the glass container, thereby enabling the glass container to withstand more severe surface damage (i.e., scratches, chips, etc. extending deep into the thicker parts of the glass container) without breaking, compared to a glass container without a compressive stress layer. Furthermore, it should also be understood that in some embodiments, a compressive stress layer may be formed in the glass container by ion exchange, by thermal strengthening, by forming the glass container from laminated glass, or by coating the glass body. In some embodiments, the compressive stress layer may be formed by a combination of these techniques. Delamination resistance In some embodiments, the glass container 100 may also be resistant to delamination even after prolonged exposure to certain chemical compositions stored in the container. As described above, delamination can be caused by the release of silica-rich glass flakes into the solution after prolonged exposure to the solution contained in the glass container. Therefore, resistance to delamination can be characterized by the number of glass particles present in the solution after exposure to the solution contained in the glass container under specific conditions. To evaluate the long-term resistance of the glass container to delamination, an accelerated delamination test is used. This test can be performed on both ion-exchange and non-ion-exchange glass containers. This test consists of washing the glass container at room temperature for 1 minute and removing exothermic substances from the container at approximately 320°C for 1 hour. Subsequently, fill the glass container to 80-90% capacity with a 20 mM glycine aqueous solution at pH 10, cover the glass container, and rapidly heat the glass container to 100°C, then heat from 100°C to 121°C at a pressure of 2 atmospheres and a heating rate of 1 deg / min. Hold the glass container and solution at this temperature for 60 minutes, cool to room temperature at a rate of 0.5 deg / min, and repeat this heating cycle and holding. Then, heat the glass container to 50°C and hold it for at least 10 days due to the high temperature conditions. After heating, drop the glass container from a height of at least 18 inches (45.72 centimeters) onto a hard surface such as a laminate tile floor to remove any flakes or particles that are weakly adhering to the inner surface of the glass container. The drop height can be appropriately estimated to prevent damage to large vials due to impact.

[0042] Subsequently, the solution contained in the glass container is analyzed to determine the number of glass particles present per liter of solution. Specifically, the solution from the glass container is poured directly into the center of a Millipore Isopore membrane filter (Millipore #ATTP02500 held in the assembly with part numbers AP1002500 and M000025A0) connected to vacuum suction, and 5 mL of the solution is filtered through the filter for 10-15 seconds. Then, an additional 5 mL of water is used to rinse and remove buffer residue from the filter medium. Next, the granular flakes are counted in reflection mode using a differential interference contrast (DIC) microscope, as described in "Differential interference contrast (DIC) microscopy and modulation contrast microscopy," Fundamentals of light microscopy and digital imaging. New York: Wiley-Liss, pp. 153-168. The field of view is set to approximately 1.5 mm × 1.5 mm, and particles larger than 50 μm are counted manually. Perform this measurement nine times in a 3x3 pattern without image superposition at the center of each filter membrane. If a larger area of ​​the filter medium is analyzed, the results will be expressed as an equivalent area (i.e., 20.25 mm²). 2) can be normalized. Images recovered from an optical microscope are examined with an image analysis program (Media Cybernetic's ImagePro Plus version 6.1) to measure and count the number of glass flakes present. This is achieved as follows: all features in the image that appear darker than the background are highlighted by simple grayscale segmentation; then the length, width, area and perimeter of all highlighted features with a length greater than 25 micrometers are measured; then all that are clearly not glass particles are removed from the data; then the measurement data is exported to a spreadsheet. Next, all features that are greater than 25 micrometers in length and lighter than the background are extracted and measured; the length, width, area, perimeter and XY aspect ratio of all highlighted features with a length greater than 25 micrometers are measured; all that are clearly not glass particles are removed from the data; and the measurement data is added to the already exported data in the spreadsheet. Next, the data in the spreadsheet is sorted by feature length and divided into bins according to size. The reported results are for features with a length greater than 50 micrometers. Next, count each of these groups and report the count for each sample.

[0043] A minimum of 100 mL of solution should be tested. Therefore, solutions may be pooled from multiple small containers to achieve a total volume of 100 mL. For containers with volumes exceeding 10 mL, the test is repeated for 10 containers formed from the same glass composition under the same processing conditions, and the average particle count is determined by averaging the particle count results across the 10 containers. Alternatively, for small containers, the test is repeated for 10 vials, each analyzed, and the average particle count for each test is determined by averaging the particle counts across multiple tests. The average particle count across multiple containers will capture potential differences in the delamination behavior of individual containers. Table 1 summarizes some non-limiting examples of sample volumes and numbers of containers to be tested.

[0044] [Table 1]

[0045] It should be understood that the aforementioned tests are used to identify particles that detach from the inner wall of the glass container due to delamination, rather than particles that are present in the container from the molding process or particles that precipitate from the solution contained in the glass container due to the reaction of the solution with the glass. Specifically, delamination particles can be distinguished from infused glass particles based on the aspect ratio of the particles (i.e., the ratio of the maximum length to the thickness of the particles, or the ratio of the maximum dimension to the minimum dimension). Delamination produces granular flakes or slabs with irregular shapes, typically with a maximum length exceeding about 50 μm, and often exceeding about 200 μm. The thickness of the flakes is usually exceeding about 100 nm, and can be as thick as about 1 μm. Therefore, the minimum aspect ratio of the flakes is typically greater than about 50. The aspect ratio can be greater than about 100, and often greater than about 1000. In contrast, infused glass particles generally have a low aspect ratio of less than about 3. Therefore, particles originating from layer delamination can be distinguished from contaminating particles based on their aspect ratio in microscopic observation. Other common non-glass particles include hair, fibers, metal particles, plastic particles, and other contaminants, which are therefore excluded during the inspection process. Verification of the results can be achieved by evaluating the internal region of the tested container. During the observation process, evidence of epidermal erosion / spotting / flake removal described in "Nondestructive Detection of Glass Vial Inner Surface Morphology with Differential Interference Contrast Microscopy," Journal of Pharmaceutical Sciences, 101(4), 2012, pages 1378-1384 is noteworthy.

[0046] The delamination coefficient for the tested vial set can be determined by utilizing the number of particles present after the accelerated delamination test. For glass containers tested where, after the accelerated delamination test, there are fewer than 10 glass particles per test on average with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50, the delamination coefficient is considered to be 10. For glass containers tested where, after the accelerated delamination test, there are fewer than 9 glass particles per test on average with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50, the delamination coefficient is considered to be 9. For glass containers tested where, after the accelerated delamination test, there are fewer than 8 glass particles per test on average with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50, the delamination coefficient is considered to be 8. For glass containers tested where, after the accelerated delamination test, there are fewer than 7 glass particles per test on average with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50, the delamination coefficient is considered to be 7. In glass containers tested after an accelerated delamination test, the delamination coefficient is considered to be 6 if, on average, there are fewer than 6 glass particles per test with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50. In glass containers tested after an accelerated delamination test, the delamination coefficient is considered to be 5 if, on average, there are fewer than 5 glass particles per test with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50. In glass containers tested after an accelerated delamination test, the delamination coefficient is considered to be 4 if, on average, there are fewer than 4 glass particles per test with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50. In glass containers tested after an accelerated delamination test, the delamination coefficient is considered to be 3 if, on average, there are fewer than 3 glass particles per test with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50. For glass containers tested after an accelerated delamination test, if the average number of glass particles per test is less than 2 with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50, the delamination coefficient is considered to be 2. For glass containers tested after an accelerated delamination test, if the average number of glass particles per test is less than 1 with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50, the delamination coefficient is considered to be 1.In a glass container test where, after an accelerated delamination test, there are no glass particles with a minimum length of approximately 50 μm and an aspect ratio greater than approximately 50 per test, the delamination coefficient is considered to be 0. Therefore, it should be understood that the smaller the delamination coefficient, the higher the resistance of the glass container to delamination. In some embodiments described herein, at least the inner surface of the body of the glass container has a delamination coefficient of 10 or less (e.g., a delamination coefficient of 3, 2, 1, or 0). In some other embodiments, the entire body of the glass container, including both the inner and outer surfaces, has a delamination coefficient of 10 or less (e.g., a delamination coefficient of 3, 2, 1, or 0).

[0047] In some embodiments, glass containers having a delamination coefficient of 10 or less can be obtained by forming a glass container having a barrier coating on the inner surface of the body such that the barrier coating is on the inner surface of the body. Referring to Figure 5 as an example, a glass container 100 is schematically illustrated having a barrier coating 131 provided on at least a portion of the inner surface 104 of the body 102. The barrier coating 131 does not delaminate or decompose and prevents contact between the product stored in the internal space 108 of the glass container 100, such as a pharmaceutical composition, and the inner surface 104 of the body 102, thereby reducing delamination of the glass container. Barrier coatings are generally impermeable to aqueous solutions, water-insoluble, and hydrolyzably stable.

[0048] In some embodiments described herein, the barrier coating 131 is a robust inorganic coating permanently bonded to the inner surface 104 of the glass container 100. The barrier coating 131 may be a metal nitride coating, a metal oxide coating, a metal sulfide coating, SiO2, diamond-like carbide, graphene, or carbide coating. For example, in some embodiments, the robust inorganic coating may be formed from at least one metal oxide such as Al2O3, TiO2, ZrO2, SnO, SiO2, Ta2O5, Nb2O5, Cr2O3, V2O5, ZnO, or HfO2. In some other embodiments, the robust inorganic coating may be formed from a combination of two or more metal oxides such as Al2O3, TiO2, ZrO2, SnO, SiO2, Ta2O5, Nb2O5, Cr2O3, V2O5, ZnO, or HfO2. In some other embodiments, the barrier coating 131 may comprise a first layer of a first metal oxide deposited on the inner surface of the glass container, and a second layer of a second metal oxide deposited on top of the first layer. In these embodiments, the barrier coating 131 can be deposited using a variety of deposition techniques, including but not limited to atomic layer deposition, chemical vapor deposition, and physical vapor deposition. Alternatively, the barrier coating can be applied using one or more liquid application techniques, such as dip coating, spray coating, or plasma coating. Spray coating techniques may include high volume low pressure (HVLP) and low volume low pressure (LVLP) spray coating, electrostatic spray coating, gasless spray coating, ultrasonic spraying with gasless spray coating, aerosol jet coating, and inkjet coating. Plasma coating techniques may include standard primary and secondary plasma coating, microwave-assisted plasma coating, and atmospheric pressure plasma coating.

[0049] Although embodiments of barrier coating 131 are described herein as including inorganic materials, it should be understood that in some embodiments, barrier coating 131 may be an organic coating. For example, in embodiments where barrier coating 131 is an organic coating, the organic coating may include fluorinated polyolefins including polybenzimidazole, polybisoxazole, polybisthiazole, polyetherimide, polyquinoline, polythiophene, phenylene sulfide, polysulfone, polycyanurate, parylene, polytetrafluoroethylene and other fluorosubstituted polyolefins, perfluoroalkoxy polymers, polyetheretherketone (PEEK), polyamide, epoxy, polypolyphenol, polyurethane acrylate, cyclic olefin copolymer and cyclic olefin polymer These may include polyethylene-containing polyolefins, polyethylene oxide, polypropylene, polyethylene / propylene copolymers, polyethylene / vinyl acetate copolymers, polyvinyl chloride, polyacrylate, polymethacrylate, polystyrene, polyterpenes, polyacid anhydrides, polymaleic anhydride, polyformaldehyde, polyacetals and polyacetal copolymers, polysiloxanes of dimethyl, diphenyl, or methyl / phenyl mixtures, perfluorinated siloxanes and other substituted siloxanes, polyimides, polycarbonates, polyesters, paraffins and waxes, or various combinations thereof. In some embodiments, the organic coating used as the barrier coating 131 may include polysiloxanes of dimethyl, diphenyl, or methyl / phenyl mixtures. Alternatively, the organic coating may be polycarbonate or polyethylene terephthalate. In some embodiments, the barrier coating 131 may be formed from a laminated structure comprising one or more of the aforementioned polymers and / or copolymers.

[0050] Barrier coatings can be used in conjunction with glass containers formed from any glass composition. However, barrier coatings are particularly preferred when used with glass containers formed from glass compositions that do not exhibit resistance to delamination when applied to glass containers. Such glass compositions are not particularly limited, but may include glass compositions referred to as Type I Class A, Type I Class B, and Type II glass compositions, in accordance with ASTM standard E438-92 (2011), titled "Standard Specification for Glasses in Laboratory Apparatus." Such glass compositions may meet the essential requirements for chemical durability in the ASTM standard, but do not exhibit resistance to delamination. For example, Table 2 below lists several non-limiting examples of Type I Class B glass compositions that do not exhibit resistance to delamination. Therefore, the barrier coatings described herein can be used on at least the inner surface of containers formed from these compositions, thereby giving the container a delamination coefficient of 10 or less.

[0051] [Table 2]

[0052] In some alternative embodiments, glass containers having a delamination coefficient of 10 or less are achieved by forming the glass container such that it has homogeneous compositional characteristics, thereby reducing its susceptibility to delamination, as described in U.S. Patent Application No. 13 / 912,457, concurrently continuing, filed on June 7, 2013, titled "Delamination Resistant Glass Containers," assigned to Corning Incorporated. Specifically, delamination of glass containers is thought to be at least partially due to heterogeneity in the glass composition, at least within the glass container, as described above. By suppressing such compositional heterogeneity, glass containers having a delamination coefficient of 10 or less are obtained.

[0053] Referring here to Figures 1 and 6, in some embodiments, the glass container described herein has a homogeneous composition throughout the thickness of the glass body 102 in each of the wall, heel, and floor portions, and as a result, at least the inner surface 104 of the body has a peel coefficient of 10 or less. Specifically, Figure 6 schematically illustrates a partial cross-section of the wall portion 110 of the glass container 100. The glass body 102 of the glass container 100 is approximately 10 nm (D in Figure 6) below the inner surface 104 of the glass container 100. LR1 (as shown) to a depth D greater than the inner surface 104 of the glass container LR2 The internal region 120 extends into the wall portion 110. The internal region extending from approximately 10 nm below the inner surface 104 is distinguished from the composition in the first 5-10 nm below the surface by experimental artifacts. At the start of the dynamic secondary ion mass spectrometry (DSIMS) analysis to determine the composition of the glass, the first 5-10 nm is not included in the analysis due to three concerns: the fluctuating sputtering rate of ions from the surface due to exogenous carbon, the establishment of a partial steady-state charge due to the fluctuating sputtering rate, and the mixing of species while steady-state sputtering conditions are established. As a result, the first two analytical data points are excluded. Thus, the internal region 120 is D LR2 ~DLR1 Thickness T equal to LR It should be understood that the glass composition in the internal region is determined by the thickness T of the internal region. LR In relation to this, the glass container has sufficient continuous layer homogeneity to prevent delamination of the glass body even after long-term exposure to the solution contained in the internal space of the glass container. In some embodiments, the thickness T LR It is at least about 100 nm. In some embodiments, the thickness T LR The thickness is at least about 150 nm. In some other embodiments, the thickness T LR The thickness is at least about 200 nm, or even more than about 250 nm. In some other embodiments, the thickness T LR The thickness is at least about 300 nm, or even more than about 350 nm. In yet another embodiment, the thickness T LR The thickness is at least about 500 nm. In some embodiments, the internal region 120 has a thickness T of at least about 1 μm, or even at least about 2 μm. LR It can extend up to that point.

[0054] The internal region extends from 10 nm below the inner surface 104 of the glass container 100 to a depth D greater than the inner surface 104 of the glass container 100. LR2 Although it is described herein that the thickness T extends into the wall portion of section 110, it should be understood that other embodiments are possible. For example, regardless of the experimental artifacts described above, the internal region having continuous layer homogeneity may actually extend from the inner surface 104 of the glass container 100 into the wall portion of section 100, and thus, in some embodiments, thickness T LR From the inner surface 104 to depth D LR2 It has been hypothesized that the thickness T may be up to this point. LR The thickness can be at least about 100 nm. In some embodiments, the thickness T LR The thickness can be at least about 150 nm. In some other embodiments, the thickness T LR The thickness T can be at least about 200 nm, or even more than about 250 nm. In some other embodiments, the thickness TLR The thickness T may be at least about 300 nm, or even more than about 350 nm. In yet another embodiment, the thickness T LR This can be at least about 500 nm. In some embodiments, the internal region 120 has a thickness T of at least about 1 μm, or even at least about 2 μm. LR It may extend to [the specified location].

[0055] In embodiments where the glass container is formed to have continuous layer homogeneity, the phrase "continuous layer homogeneity" means that the concentration of a component of the glass composition (e.g., SiO2, Al2O3, Na2O, etc.) in the internal region is not so different from the concentration of the same component at the midpoint of the thickness of the glass layer including the internal region that prolonged exposure to the solution contained in the glass container would cause delamination of the glass body. For example, in embodiments where the glass container is formed from a single glass composition, the glass body consists of a single layer of glass, and the concentration of the component in the internal region is compared with the concentration of the same component at a point along the midpoint line MP that bisects the glass body between the inner surface 104 and the outer surface 106 to determine whether continuous layer homogeneity exists. However, in embodiments where the glass container is formed from laminated glass in which the glass cladding layer of laminated glass forms the internal surface of the glass container, the concentration of the component in the internal region is compared with the concentration of the same component at a point along the midpoint line that bisects the glass cladding layer forming the internal surface of the glass container. In the embodiments described herein, continuous layer homogeneity in the internal region of the glass body is such that the extreme values ​​(i.e., minimum or maximum) of the layer concentration of each component of the glass composition in the internal region 120 are about 80% or more and about 120% or less of the same component at the midpoint of the glass layer including the internal region 120. As used herein, continuous layer homogeneity refers to the state of the glass container when it is in the as-formed state or after one or more surface treatments applied to at least the internal surface of the glass container, such as etching. In other embodiments, continuous layer homogeneity in the internal region of the glass body is such that the extreme values ​​of the layer concentration of each component of the glass composition in the internal region 120 are about 90% or more and about 110% or less of the same component at the midpoint of the thickness of the glass layer including the internal region 120.In yet another embodiment, the continuous layer homogeneity in the internal region of the glass body is such that the extreme values ​​of the layer concentrations of each component of the glass composition in the internal region 120 are approximately 92% or more and approximately 108% or less of the same component at the midpoint of the glass thickness portion of the glass layer including the internal region 120. In some embodiments, the continuous layer homogeneity does not include components of the glass composition present in amounts of less than approximately 2 mol.%.

[0056] As used herein, the term “as-formed” refers to the composition of the glass container 100 after it has been formed from glass stock but before it is subjected to any additional processing steps such as ion exchange strengthening, coating, or ammonium sulfate treatment. In some embodiments, the term “as-formed” includes the composition of the glass container 100 after it has been formed and subjected to etching to selectively remove all or part of at least the inner surface of the glass container. In embodiments described herein, the layer concentration of components in the glass composition is determined by collecting a composition sample from the wall thickness of the glass body in the region of interest using dynamic secondary ion mass spectrometry (DSIMS) analysis. In embodiments described herein, the composition profile is sampled from a region of the inner surface 104 of the glass body 102. The sampled region is 1 mm 2 This technique provides the maximum area of ​​the sample region.

[0057] As described above, forming a glass container with continuous layer homogeneity generally improves the resistance of the glass container to delamination. Specifically, by providing an internal region with a homogeneous composition (i.e., the extreme value of the concentration of the constituent components in the internal region is within + / - 20% of the same constituent component at the midpoint of the thickness of the glass layer including the internal region), localized concentration of components of the glass composition that may be prone to leaching is prevented. As a result, even when these components leach from the glass surface, the loss of glass particles from the inner surface of the glass container is reduced.

[0058] As described herein, containers having continuous layer homogeneity in the as-formed state do not have coatings, including inorganic and / or organic coatings, applied to the inner surface of the glass body. Therefore, it should be understood that the body of the glass container is formed from a substantially single composition extending to a depth of at least 250 nm, or even at least 300 nm, from the inner surface of the body. The term "single composition" refers to the fact that the glass forming the portion of the body extending into the wall portion of the body to a depth of at least 250 nm, or even at least 300 nm, from the inner surface, is a single composition of substance, compared to coating materials applied to other materials of the same or different composition. For example, in some embodiments, the body of the container may consist of a single glass composition. In other embodiments, the body of the container may consist of laminated glass such that the inner surface of the body has a single composition extending to a depth of at least 250 nm, or even at least 300 nm, from the inner surface. As described above, the glass container may have an internal region extending from the inner surface or to a depth of at least 10 nm to 100 nm below the inner surface. This internal region may have continuous layer homogeneity.

[0059] Referring here to Figures 1 and 7, in some embodiments, the glass containers described herein may also have a homogeneous surface composition throughout the inner surface 104 of the body 102, such that at least the inner surface 104 of the body 102, including the walls, heels, and floor portions, has a peel coefficient of 10 or less when the glass container is in the as-formed state. Figure 7 schematically illustrates a partial cross-section of the wall portion 110 of the glass container 100. The glass container 100 has a surface region 130 that extends over the entire inner surface of the glass container. The surface region 130 extends from the inner surface 104 of the glass container 100 to the outer surface in the thick portion of the glass body. SR It has. Therefore, the surface region 130 has a depth D SR Thickness T equal to SR It should be understood that this surface region has a depth of at least about 10 nm D from the inner surface 104 of the glass container 100. In some embodiments, this surface region has a depth of at least about 10 nm D SR It extends to a depth of at least about 50 nm. In some other embodiments, the surface region 130 has a depth of D SR It may extend to a depth of D of about 10 nm to about 50 nm. In some other embodiments, the surface region 130 has a depth of D of about 10 nm to about 50 nm. SR It can extend to a depth of D. Therefore, it should be understood that the surface region 130 extends to a shallower depth than the interior region 120. The glass composition of the surface region is such that the depth of the interior region D SR In relation to this, the glass container has sufficient continuous surface homogeneity to prevent delamination of the glass body even after prolonged exposure to the solution contained in the internal space of the glass container.

[0060] In the embodiments described herein, the phrase “continuous surface homogeneity” means that the concentration of a component of the glass composition (e.g., SiO2, Al2O3, Na2O, etc.) at an independent point in the surface region is not so different from the concentration of the same component at any second independent point in the surface region that prolonged exposure to a solution contained in the glass container would result in delamination of the glass body. In the embodiments described herein, continuous surface homogeneity in the surface region means that, for an independent point on the inner surface 104 of the glass container, the extreme values ​​(i.e., minimum or maximum) of the surface concentration of each component in the surface region 130 at that independent point are about 70% or more and about 130% or less of the concentration of the same component in the surface region 130 at any second independent point on the inner surface 104 of the glass container 100, respectively, when the glass container 100 is in its as-formed state. For example, Figure 7 shows three independent points (A, B, and C) on the inner surface 104 of the wall portion 110. Each point is spaced at least approximately 3 mm apart from adjacent points. The extreme values ​​of the surface concentrations of each component at point "A" in surface region 130 are approximately 70% or more and approximately 130% or less of the same component at points "B" and "C" in surface region 130. Regarding the heel portion of the container, independent points may be centered approximately at the apex of the heel, and adjacent points are located at least 3 mm from the apex of the heel along the bottom portion and the wall portion of the container, with the distance between points being limited by the radius of the container and the height of the sidewall (i.e., the point where the sidewall transitions to the shoulder of the container).

[0061] In some embodiments, continuous surface homogeneity in the surface region is such that the extreme values ​​of the surface concentrations of each component of the glass composition in the surface region 130 are about 75% or more and about 125% or less of the same component in the surface region 130 at any second independent point on the inner surface 104 of the glass container 100, for any independent point on the inner surface 104 of the glass container 100. In some other embodiments, continuous surface homogeneity in the surface region is such that the extreme values ​​of the surface concentrations of each component of the glass composition in the surface region 130 are about 80% or more and about 120% or less of the same component in the surface region 130 at any second independent point on the inner surface 104 of the glass container 100, for any independent point on the inner surface 104 of the glass container 100. In yet another embodiment, continuous surface homogeneity in the surface region is such that the extreme values ​​of the surface concentrations of each component of the glass composition in the surface region 130 are about 85% or more and about 115% or less of the same component in the surface region 130 at any second independent point on the inner surface 104 of the glass container 100. In the embodiments described herein, the surface concentrations of the components of the glass composition in the surface region are measured by X-ray photoelectron spectroscopy. In some embodiments, components of the glass composition present in amounts less than about 2 mol.% are excluded from continuous surface homogeneity in the surface region.

[0062] The homogeneity of the surface concentration of glass components in the surface region 130 is generally an indicator of the tendency of a glass composition to delaminate and detach from the inner surface 104 of a glass container 100. When a glass composition has continuous surface homogeneity in the surface region 130 (i.e., the extreme value of the surface concentration of glass components in the surface region 130 at an independent point on the inner surface 104 is + / - 30% of the same component in the surface region 130 at any second independent point on the inner surface 104), the glass composition has improved resistance to delamination.

[0063] Glass containers having continuous layer homogeneity and / or continuous surface homogeneity can be achieved using various techniques. For example, in some embodiments, at least the inner surface 104 of the body 102 of the glass container is etched such that at least the inner surface of the glass container has a delamination coefficient of 10 or less, thereby resulting in a glass container having continuous layer homogeneity and / or continuous surface homogeneity. Specifically, as described above, compositional changes in the glass due to the volatilization of seeds from the glass and the subsequent reattachment of the volatilized seeds during the molding of the container are considered to be one of the mechanisms that cause delamination. The thin epidermis of volatilized and reattached seeds on the inner surface of the glass container is compositionally heterogeneous and hydrolytically weak, and therefore alkali and boron species are rapidly lost from the epidermis during exposure to the pharmaceutical composition. This behavior leaves a large surface area silica-rich layer. When the pharmaceutical composition is exposed to the silica-rich layer, the layer swells and eventually peels off from the inner surface of the body (i.e., delamination). However, by etching the inner surface of the glass container body, this thin surface layer is removed, and continuous layer homogeneity and / or continuous surface homogeneity are brought to at least the inner surface of the glass container body.

[0064] In some embodiments described herein, the body of the glass container is etched to remove a layer of glass material from the inner surface of the glass body. The etching is sufficient to remove a thin surface layer of volatile and re-adhered species, thereby providing continuous layer homogeneity and / or continuous surface homogeneity to at least the inner surface of the glass container body such that the layer delamination coefficient of at least the inner surface of the glass body is 10 or less. For example, in some embodiments, the body of the glass container is etched to remove glass material from the inner surface of the glass body to a depth of 1 μm, or even 1.5 μm. In some other embodiments, the body of the glass container may be etched to remove glass material to depths greater than 1.5 μm, including, but not limited to, 2 μm, 3 μm, or even 5 μm. In these embodiments, at least the inner surface of the glass container may be formed from a glass composition that meets the criteria for Type I, Class A (Type IA) or Type I, Class B (Type IB) glass according to ASTM standard E438-92 (2011), entitled "Standard Specification for Glasses in Laboratory Apparatus". Borosilicate glass meets the Type I (A or B) criteria and is routinely used in pharmaceutical packaging. Examples of borosilicate glass include, but are not limited to, Corning® Pyrex® 7740, 7800, Wheaton 180, 200 and 400, Schott Duran®, Schott Fiolax®, KIMAX® N-51A, Gerresheimer GX-51 Flint, and others.

[0065] In one embodiment, etching can be achieved by exposing the inner surface of the glass container to an acidic solution or a combination of acidic solutions. Examples of acidic solutions, though not particularly limited, include sulfuric acid, nitric acid, hydrochloric acid, hydrofluoric acid, hydrobromic acid, and phosphoric acid. For example, the acidic solution may include a mixture of 1.5 M hydrofluoric acid and 0.9 M sulfuric acid. These acidic solutions effectively remove a thin surface layer of volatile and re-adhered organic solutions without leaving a deficient "leaching layer" on the inner surface of the glass container. Alternatively, etching can be achieved by exposing the inner surface of the glass container to a basic solution or a combination of basic solutions. Suitable basic solutions include, for example, sodium hydroxide, potassium hydroxide, ammonium hydroxide, or a combination thereof. Alternatively, etching can be achieved by exposing the acidic solution followed by the basic solution, or in the reverse order.

[0066] While one specific etching process is described herein, it should be understood that other etching processes may also be used. For example, the etching processes disclosed in U.S. Patent No. 2,106,744, U.S. Patent Publication No. 2011 / 0165393, U.S. Patent Publication No. 2013 / 0122306, and U.S. Patent Publication No. 2012 / 0282449 may also be used to etch at least the inner surface of a glass container.

[0067] In further embodiments, continuous layer homogeneity and / or continuous surface homogeneity can be brought to a glass container by forming the glass container from a glass composition in which the components of the glass composition form a species with relatively low vapor pressure (i.e., a species with low volatility) at the temperature required for reshaping the glass stock into a glass container of the desired container shape. Because these components form a species with relatively low vapor pressure at the reshaping temperature, the components are less likely to volatilize and vaporize from the glass surface, thereby forming a glass container with a compositionally homogeneous surface on the inner surface and within the wall thickness of the glass container.

[0068] Certain components of a glass composition can be highly volatile at the glass forming and reforming temperatures, which can result in compositional heterogeneity and subsequent delamination. The forming and reforming temperatures of glass compositions generally correspond to temperatures in which the glass composition has a viscosity in the range of about 200 poise to about 100 kilopoise. Therefore, in some embodiments, the glass composition forming a glass container forms species that are highly volatile at temperatures corresponding to a viscosity in the range of about 200 poise to about 100 kilopoise (i.e., about 10 -3 It does not contain any components that form gaseous species at equilibrium partial pressures above atm. In some embodiments, the glass composition forming the glass container does not contain any components that volatilize significantly at temperatures corresponding to viscosities in the range of about 1 kilopoise to about 50 kilopoise. In some other embodiments, the glass composition forming the glass container does not contain any components that volatilize significantly at temperatures corresponding to viscosities in the range of about 1 kilopoise to about 20 kilopoise. In some other embodiments, the glass composition forming the glass container does not contain any components that volatilize significantly at temperatures corresponding to viscosities in the range of about 1 kilopoise to about 10 kilopoise. Although we do not wish to be bound by theory, compounds that volatilize significantly under these conditions include, but are not limited to, boron and boron compounds, phosphorus and phosphorus compounds, zinc and zinc compounds, fluorine and fluorine compounds, chlorine and chlorine compounds, tin and tin compounds, and sodium and sodium compounds.

[0069] In some embodiments described herein, the glass containers are generally formed from an aluminosilicate glass composition, such as an alkali aluminosilicate glass composition or an alkaline earth aluminosilicate glass composition. As described herein, boron-containing species in glass can be highly volatile at the high temperatures used in glass forming and reforming, which can lead to delamination of the resulting glass containers. Moreover, boron-containing glass compositions are also susceptible to phase separation. Therefore, in the embodiments described herein, the boron concentration in the glass composition forming the glass container is limited to mitigate both delamination and phase separation. In some embodiments, the glass composition forming the glass container is not particularly limited, but contains an oxide of boron and / or a boron-containing compound, including B2O3, at a concentration of about 1.0 mol.% or less. In some of these embodiments, the concentration of the oxide of boron and / or a boron-containing compound in the glass composition may be about 0.5 mol.% or less, about 0.4 mol.% or less, or even about 0.3 mol.% or less. In some of these embodiments, the concentration of boron and / or boron-containing compound oxides in the glass composition may be about 0.2 mol.% or less, or even about 0.1 mol.% or less. In some other embodiments, the glass composition is substantially free of boron and boron-containing compounds.

[0070] Similar to boron, phosphorus also generally forms high-temperature, highly volatile species in glass compositions that are used in the molding and reshaping of glass. Therefore, phosphorus in glass compositions can lead to compositional heterogeneity in the final glass container, which can result in delamination. Accordingly, in the embodiments described herein, the concentrations of phosphorus and phosphorus-containing compounds (such as P2O5) in the glass composition forming the glass container are limited to mitigate delamination. In some embodiments, the glass composition from which the glass container is formed contains phosphorus and / or phosphorus-containing compound oxides at about 0.3 mol.% or less. In some of these embodiments, the concentration of phosphorus and / or phosphorus-containing compound oxides in the glass composition may be about 0.2 mol.% or less, or even about 0.1 mol.% or less. In some other embodiments, the glass composition is substantially free of phosphorus and phosphorus-containing compounds.

[0071] Similar to boron and phosphorus, zinc also generally forms high-temperature, highly volatile species in glass compositions that are used in the molding and reshaping of glass. Therefore, zinc in the glass composition can lead to compositional heterogeneity in the final glass container, which can result in delamination. Accordingly, in the embodiments described herein, the concentrations of zinc and zinc-containing compounds (such as ZnO) in the glass composition forming the glass container are limited to mitigate delamination. In some embodiments, the glass composition forming the glass container contains about 0.5 mol.% or less of zinc and / or zinc-containing compound oxides. In some other embodiments, the glass composition forming the glass container contains about 0.3 mol.% or less of zinc and / or zinc-containing compound oxides. In some of these embodiments, the concentration of zinc or zinc-containing compound oxides in the glass composition may be about 0.2 mol.% or less, or even about 0.1 mol.% or less. In some other embodiments, the glass composition is substantially free of zinc and zinc-containing compounds.

[0072] Lead and bismuth also form high-temperature, highly volatile species in the glass composition that are used in the molding and reshaping of glass. Therefore, in the embodiments described herein, the concentrations of lead, bismuth, lead-containing compounds, and bismuth-containing compounds in the glass composition forming the glass container are limited to reduce delamination. In some embodiments, lead oxides, bismuth oxides, lead-containing compounds, and / or bismuth-containing compounds are each present in the glass composition at a concentration of about 0.3 mol.% or less. In some of these embodiments, each of the lead oxides, bismuth oxides, lead-containing compounds, and / or bismuth-containing compounds is present in the glass composition at a concentration of about 0.2 mol.% or less, or even less than about 0.1 mol.%. In some other embodiments, the glass composition is substantially free of lead and / or bismuth, as well as lead and / or bismuth-containing compounds.

[0073] Species containing tin oxides, chlorine, and fluorine are also highly volatile at high temperatures used in glass forming and reshaping. Therefore, in the embodiments described herein, chlorine, fluorine, and tin oxides, as well as tin-containing compounds, chlorine-containing compounds, or fluorine-containing compounds, are present in the glass composition at concentrations that do not adversely affect the delamination resistance of the resulting glass. Specifically, chlorine, fluorine, and tin oxides, as well as tin-containing compounds, chlorine-containing compounds, or fluorine-containing compounds, are present in the glass composition forming the glass container at concentrations of about 0.5 mol.% or less, or even about 0.3 mol.% or less. In some embodiments, the glass composition is substantially free of tin, chlorine, and fluorine, as well as tin-containing compounds, chlorine-containing compounds, or fluorine-containing compounds.

[0074] While some embodiments of glass containers may not contain easily volatile components as described above, in certain other embodiments, the glass container may be formed from a glass composition that includes these volatile components, such as when the glass container has a barrier layer.

[0075] The glass composition from which the container is formed does not undergo phase separation. As used herein, the term “phase separation” refers to the separation of a glass composition into distinct phases, each having different compositional characteristics. For example, alkali borosilicate glass is generally known to undergo phase separation into a boron-rich phase and a silica-rich phase at high temperatures (such as molding and reshaping temperatures). In some embodiments described herein, the concentration of boron oxide in the glass composition is sufficiently low (i.e., about 1.0 mol.% or less) so that the glass composition does not undergo phase separation.

[0076] In one exemplary embodiment, the glass container is formed from a delamination-resistant glass composition, such as the alkaline earth aluminosilicate glass composition described in U.S. Patent Application No. 13 / 660,141, filed on 25 October 2012, titled "Alkaline Earth Alumino-Silicate Glass Compositions with Improved Chemical and Mechanical Durability" (Agent Reference No. SP11-241), which is entirely incorporated herein by reference. This first exemplary glass composition generally comprises a combination of SiO2, Al2O3, at least one alkaline earth oxide, and an alkali oxide containing at least Na2O and K2O. In some embodiments, the glass composition may also not contain boron and boron-containing compounds. The combination of these components results in a glass composition that is resistant to chemical decomposition and is also suitable for chemical strengthening by ion exchange. In some embodiments, the glass composition may further contain trace amounts of one or more additional oxides, such as SnO2, ZrO2, ZnO, etc. These components may be added as clarifying agents and / or to further enhance the chemical durability of the glass composition.

[0077] In the first exemplary embodiment of the glass composition, the glass composition generally contains SiO2 in amounts of about 65 mol.% or more and about 75 mol.% or less. In some embodiments, SiO2 is present in the glass composition in amounts of about 67 mol.% or more and about 75 mol.% or less. In some other embodiments, SiO2 is present in the glass composition in amounts of about 67 mol.% or more and about 73 mol.% or less. In each of these embodiments, the amount of SiO2 present in the glass composition may be about 70 mol.% or more, or even about 72 mol.% or more.

[0078] Furthermore, the first exemplary glass composition contains Al2O3. Al2O3, together with alkali oxides such as Na2O present in the glass composition, improves the glass's sensitivity to ion exchange strengthening. Moreover, the addition of Al2O3 to the composition reduces the tendency for alkali components (such as Na and K) to leach out of the glass, and as a result, the addition of Al2O3 increases the composition's resistance to hydrolysis. In addition, adding more than about 12.5 mol.% of Al2O3 can raise the softening point of the glass, which reduces the moldability of the glass. Therefore, the glass compositions described herein generally contain Al2O3 in amounts of about 6 mol.% or more and about 12.5 mol.% or less. In some embodiments, the amount of Al2O3 in the glass composition is about 6 mol.% or more and about 10 mol.% or less. In some other embodiments, the amount of Al2O3 in the glass composition is about 7 mol.% or more and about 10 mol.% or less.

[0079] The first exemplary glass composition also contains at least two alkali oxides. The alkali oxides promote the ion exchange properties of the glass composition, thereby promoting the chemical strengthening of the glass. Furthermore, the alkali oxides lower the softening point of the glass, thereby offsetting the increase in softening point due to the high SiO2 concentration in the glass composition. The alkali oxides also contribute to improving the chemical durability of the glass composition. Generally, alkali oxides are present in the glass composition in amounts of about 5 mol.% or more and about 12 mol.% or less. In some of these embodiments, the amount of alkali oxide may be about 5 mol.% or more and about 10 mol.% or less. In some other embodiments, the amount of alkali oxide may be about 5 mol.% or more and about 8 mol.% or less. In all of the glass compositions described herein, the alkali oxides include at least Na2O and K2O. In some embodiments, the alkali oxides further include Li2O.

[0080] The ion-exchangeability of a glass composition is primarily imparted to it by the amount of alkali oxide Na2O initially present in the glass composition prior to ion exchange. Specifically, in order to achieve the desired compressive stress and layer depth in the glass composition during ion-exchange strengthening, the glass composition contains Na2O in amounts of about 2.5 mol.% or more and about 10 mol.% or less, based on the molecular weight of the glass composition. In some embodiments, the glass composition may contain Na2O in amounts of about 3.5 mol.% or more and about 8 mol.% or less. In some of these embodiments, the glass composition may contain Na2O in amounts of about 6 mol.% or more and about 8 mol.% or less.

[0081] As described above, alkali oxides in glass compositions also contain K2O. The amount of K2O present in a glass composition is also related to the ion exchangeability of the glass composition. Specifically, as the amount of K2O present in the glass composition increases, the compressive stress obtained through ion exchange decreases. Therefore, it is desirable to limit the amount of K2O present in the glass composition. In some embodiments, the amount of K2O is greater than 0 mol.% and about 2.5 mol.% or less, based on the molecular weight of the glass composition. In some of these embodiments, the amount of K2O present in the glass composition is about 0.5 mol.% or less, based on the molecular weight of the glass composition.

[0082] In some embodiments, the alkali oxide in the first exemplary glass composition further comprises Li2O. The presence of Li2O in the glass composition further lowers the softening point of the glass. In embodiments in which the alkali oxide comprises Li2O, Li2O may be present in amounts of about 1 mol.% or more and about 3 mol.% or less. In some embodiments, Li2O may be present in amounts of more than about 2 mol.% and about 3 mol.% or less in the glass composition. However, in some other embodiments, the glass composition may be substantially free of lithium and lithium-containing compounds.

[0083] The alkaline earth oxides in the first exemplary glass composition improve the meltability of the glass batch material and enhance the chemical durability of the glass composition. Furthermore, the presence of alkaline earth oxides in the glass composition reduces the glass's susceptibility to delamination. In the glass compositions described herein, the glass composition generally contains at least one alkaline earth oxide in concentrations of about 8 mol.% or more, and more preferably 8.5 mol.% and about 15 mol.% or less. In some embodiments, the glass composition may contain alkaline earth oxides in concentrations of about 9 mol.% to about 15 mol.%. In some of these embodiments, the amount of alkaline earth oxide in the glass composition may be about 10 mol.% to about 14 mol.%.

[0084] The alkaline earth oxide in the first exemplary glass composition may include MgO, CaO, SrO, BaO, or a combination thereof. For example, in the embodiments described herein, the alkaline earth oxide may include MgO. In some embodiments, MgO may be present in the glass composition in an amount of about 2 mol.% or more and about 7 mol.% or less based on the molecular weight of the glass composition, or even more, in an amount of about 3 mol.% or more and about 5 mol.% or less based on the molecular weight of the glass composition.

[0085] In some embodiments, the alkaline earth oxide in the first exemplary glass composition also contains CaO. In these embodiments, CaO is present in the glass composition in an amount of about 2 mol.% to 7 mol.% or less, based on the molecular weight of the glass composition. In some embodiments, CaO is present in the glass composition in an amount of about 3 mol.% to 7 mol.% or less, based on the molecular weight of the glass composition. In some of these embodiments, CaO may be present in the glass composition in an amount of about 4 mol.% or more and about 7 mol.% or less. In some other embodiments, such as when CaO substitutes for MgO in the alkaline earth oxide to lower the liquid temperature and increase the liquid viscosity, CaO may be present in the glass in an amount of about 5 mol.% or more and about 6 mol.% or less. In yet another embodiment, such as when SrO substitutes for MgO in the alkaline earth oxide to lower the liquid temperature and increase the liquid viscosity, CaO may be present in the glass in an amount of about 2 mol.% or more and about 5 mol.% or less.

[0086] In some embodiments described herein, the alkaline earth oxide further comprises at least one of SrO or BaO. The inclusion of SrO lowers the liquid temperature of the glass composition, resulting in improved moldability. In some embodiments, the glass composition may contain SrO in amounts greater than 0 mol.% and about 6.0 mol.% or less. In some other embodiments, the glass composition may contain SrO in amounts greater than about 0 mol.% and about 5 mol.% or less. In some of these embodiments, the glass composition may contain SrO in amounts greater than or equal to about 2 mol.% and about 4 mol.% or less, such as when CaO replaces MgO in the alkaline earth oxide, in order to lower the liquid temperature and increase the liquid viscosity. In some other embodiments, the glass composition may contain SrO in amounts of about 1 mol.% to about 2 mol.%. In yet another embodiment, SrO may be present in the glass composition in amounts greater than or equal to about 3 mol.% and about 6 mol.% or less, such as when SrO replaces MgO in the alkaline earth oxide, in order to lower the liquid temperature and increase the liquid viscosity.

[0087] In embodiments where the glass composition contains BaO, BaO may be present in amounts greater than about 0 mol.% and less than about 2 mol.%. In some of these embodiments, BaO may be present in the glass composition in amounts of about 1.5 mol.% or less, or even less than about 0.5 mol.%. However, in some other embodiments, the glass composition is substantially free of barium and barium compounds.

[0088] In the embodiments of the glass compositions described herein, the glass compositions generally contain less than about 1 mol.% of boron or boron oxides, such as B2O3. For example, in some embodiments, the glass composition may contain about 0 mol.% or more of B2O3 and 1 mol.% or less of B2O3. In some other embodiments, the glass composition may contain about 0 mol.% or more of B2O3 and 0.6 mol.% or less of B2O3. In yet another embodiment, the glass composition is substantially free of boron and boron compounds, such as B2O3. Specifically, it has been determined that the chemical durability of the glass composition is significantly increased by forming the glass composition with or without a relatively small amount of boron or boron compounds (i.e., 1 mol.% or less). In addition, it was determined that forming a glass composition with or without a relatively small amount of boron or a boron compound improves the ion exchange properties of the glass composition by shortening the process time and / or lowering the process temperature required to achieve specific compressive stress and / or layer depth values.

[0089] In some embodiments of the glass compositions described herein, the glass compositions are substantially free of phosphorus and phosphorus-containing compounds, including P2O5, although this is not particularly limited. Specifically, it has been determined that forming a glass composition without phosphorus or phosphorus compounds enhances the chemical durability of the glass composition.

[0090] In addition to SiO2, Al2O3, alkali oxides and alkaline earth oxides, the first exemplary glass compositions described herein optionally include, for example, SnO2, As2O3 and / or Cl -The glass composition may further contain one or more clarifying agents, such as those derived from NaCl. When clarifying agents are present in the glass composition, they may be present in an amount of about 1 mol.% or less, or even about 0.5 mol.% or less. For example, in some embodiments, the glass composition may contain SnO2 as a clarifying agent. In these embodiments, SnO2 may be present in the glass composition in an amount of more than about 0 mol.% and about 0.30 mol.% or less.

[0091] Furthermore, the glass compositions described herein may contain one or more additional metal oxides to further improve the chemical durability of the glass composition. For example, the glass composition may further contain ZnO or ZrO2, each of which further improves the glass composition's resistance to chemical action. In these embodiments, the additional metal oxides may be present in amounts of about 0 mol.% or more and about 2.0 mol.% or less. For example, if the additional metal oxide is ZrO2, ZrO2 may be present in an amount of about 1.5 mol.% or less. Alternatively, the additional metal oxide may be ZnO in an amount of about 2.0 mol.% or less. In some embodiments, ZnO may be included as a substitution for one or more alkaline earth oxides. For example, in embodiments in which the glass composition contains alkaline earth oxides MgO, CaO and SrO, the amount of MgO may be reduced to lower the liquid temperature and increase the liquid viscosity, as described above. In these embodiments, ZnO may be added to the glass composition as a partial substitution for MgO, in addition to or instead of at least one of CaO or SrO.

[0092] Based on the above, in one embodiment, the first exemplary glass composition may contain about 65 mol.% to about 75 mol.% of SiO2; about 6 mol.% to about 12.5 mol.% of Al2O3; and about 5 mol.% to about 12 mol.% of alkali oxides, the alkali oxides of which should be understood to include Na2O and K2O. K2O may be present in amounts of 0.5 mol.% or less. The glass composition may also contain about 8.0 mol.% to about 15 mol.% of alkaline earth oxides. The glass composition may be easily strengthened by ion exchange.

[0093] In other embodiments of the first exemplary glass composition, the glass composition comprises about 67 mol.% to about 75 mol.% of SiO2; about 6 mol.% to about 10 mol.% of Al2O3; about 5 mol.% to about 12 mol.% of alkali oxides; and about 9 mol.% to about 15 mol.% of alkaline earth oxides. The alkali oxides include at least Na2O and K2O. The glass composition is free of boron and boron compounds, is readily subject to ion exchange, thereby promoting chemical strengthening of the glass and improving its mechanical durability.

[0094] In yet another embodiment of the first exemplary glass composition, the glass composition may contain about 67 mol.% to about 75 mol.% of SiO2; about 6 mol.% to about 10 mol.% of Al2O3; about 5 mol.% to about 12 mol.% of alkali oxides; and about 9 mol.% to about 15 mol.% of alkaline earth oxides. The alkaline earth oxides include at least one of SrO and BaO. The glass composition does not contain boron or boron compounds and is readily subject to ion exchange, thereby promoting chemical strengthening of the glass and improving its mechanical durability.

[0095] In some embodiments described herein, glass containers having continuous surface homogeneity and / or continuous layer homogeneity can be obtained by utilizing a molding process that provides a uniform temperature history to at least the inner surface of the body of the glass container. For example, in one embodiment, the body of the glass container can be molded at a molding temperature and / or molding speed that reduces the volatilization of chemical species from the glass composition in which the body is formed. Specifically, in order to mold the glass flow into a desired shape, it is necessary to control both the viscosity of the glass and the molding speed. When the viscosity is high, the molding speed must be slower, while when the viscosity is low, the molding speed can be increased. The bulk composition of the glass and the temperature are the biggest factors influencing the viscosity. By adjusting the temperature to match the viscosity at each stage of the molding process, it is possible to use the same molding process for different glasses. Therefore, one approach to reduce volatilization from the glass molten material is to carry out the process at a lower temperature (higher viscosity). This approach is disadvantageous because it also requires a decrease in the yield and capacity of the molding equipment, ultimately resulting in higher costs. Temperature is a major influencing factor for volatilization in the two exemplary compositions, and in all cases, Figure 16 shows that reducing temperature (and therefore rate) reduces the driving force related to volatilization losses. The viscosity associated with the tube-vial conversion process ranges from 200 P (highest temperature, during cutting and drilling operations) to 20,000 P (lowest temperature, during tube forming and finishing steps). For typical 51-expansion borosilicate glass, these viscosities are approximately 1100–1650°C. The main temperature range associated is 1350–1650°C, as volatilization is significantly reduced at lower temperatures.

[0096] In other embodiments, glass containers having continuous surface homogeneity and / or continuous layer homogeneity can be obtained by molding the body. There are several methods for molding molten glass into container shapes using molds. All are based on introducing a “gob” of molten glass, which is uniformly hot, into a molding machine. In blow-blow molding, the gob is first blown through an orifice (which forms the lip / finish) using pressurized air to form a preform (smaller than the final product). The preform (or parison) is then placed in a second mold, where it is further blown to contact the mold surface, defining the final shape of the container. In press-blow molding, the gob is held by a ring that defines the lip / finish, and a plunger is pushed into the gob to form a preform. The preform is then placed in a second mold and blown to contact the mold surface, forming the final container shape. Molding processes generally provide a uniform temperature history to the body during molding, resulting in continuous surface homogeneity and / or continuous layer homogeneity at least on the inner surface of the glass body, which can reduce the glass body's susceptibility to delamination. For example, molten glass can be molded into a container shape so that the glass body cools monotonically from the molten glass, and the temperature of the glass during cooling can be controlled. Monotonous cooling is achieved by lowering the temperature of the glass body from a molten state to solidification without any heating in between. This results in less volatilization compared to the process of converting a tube into a vial. This type of cooling can be facilitated by using molding processes such as blow molding, press-blow molding, and blow-blow molding. In some embodiments, these techniques can be used to mold glass containers with a delamination coefficient of 10 or less from a Type I Class B glass composition.

[0097] The glass compositions described herein are formed by mixing batches of glass raw materials (e.g., powders such as SiO2, Al2O3, alkali oxides, alkaline earth oxides, etc.) so that the batch of glass raw materials has a desired composition. The batch of glass raw materials is then heated to form a molten glass composition, which is then cooled and solidified to form the glass composition. During solidification (i.e., when the glass composition is plastically deformable), the glass composition may be shaped using standard shaping techniques to form the glass composition into a desired final form. Alternatively, the glass composition may be shaped into a stock form such as a sheet or tube, which is then reheated and formed into a glass container 100.

[0098] The glass compositions described herein can be shaped into various forms, such as sheets and tubes. Chemically durable glass compositions are particularly suitable for forming pharmaceutical packaging for encapsulating pharmaceutical formulations such as liquids and powders. For example, the glass compositions described herein can be used to form glass containers such as vials, ampoules, cartridges, syringe bodies, and / or any other glass containers for storing pharmaceutical formulations. Furthermore, by utilizing the fact that glass compositions can be chemically strengthened through ion exchange, it is possible to improve the mechanical durability of such pharmaceutical packaging. Therefore, in at least one embodiment, it should be understood that glass compositions are incorporated into pharmaceutical packaging to improve the chemical and / or mechanical durability of the pharmaceutical packaging.

[0099] Furthermore, in some embodiments, the glass containers comply with DIN 12116, ISO 695, ISO 719, ISO 720, and USP standards. <660> It may be formed from a glass composition that is chemically durable and resistant to degradation, as determined by tests and / or the European Pharmacopoeia 3.2.1 test.

[0100] Specifically, the DIN 12116 standard is a standard for the resistance of glass to decomposition when placed in acidic solutions. The DIN 12116 standard is divided into individual classes. Class S1 includes 0.7 mg / dm 2 The following weight loss is specified; for Class S2, 0.7 mg / dm 2 ~1.5 mg / dm 2 The following weight loss is specified; for Class S3, 1.5 mg / dm 2 ~15mg / dm 2 The following weight loss is specified; and for Class S4, 15 mg / dm 2 Weight loss exceeding a certain limit is specified. The glass compositions described herein have acid resistance of class S3 or higher in accordance with DIN 12116, and some embodiments have acid resistance of at least class S2 or higher, or even class S1. It should be understood that lower class ranks have improved acid resistance performance. Therefore, compositions graded as S1 have better acid resistance than compositions graded as class S2.

[0101] The ISO 695 standard is a criterion for the resistance of glass to decomposition when placed in a basic solution. The ISO 695 standard is divided into individual classes. Class A1 includes 75 mg / dm 2 The following weight loss is specified; Class A2 has a limit of 75 mg / dm 2 ~175 mg / dm 2 The following weight loss is specified; and for Class A3, 175 mg / dm 2 Weight loss exceeding a certain limit is specified. The glass compositions described herein have base resistance of Class A2 or higher in accordance with ISO 695, and some embodiments have base resistance of Class A1. It should be understood that lower class ranks have improved base resistance performance. Therefore, compositions graded as A1 have better base resistance than compositions graded as Class A2.

[0102] The glass composition forming glass containers is chemically durable and resistant to degradation, as determined by the ISO 720 standard. The ISO 720 standard is a criterion for the resistance of glass to degradation in distilled water (i.e., resistance to glass hydrolysis). Non-ion-exchange samples of glass are evaluated according to the ISO 720 protocol. Ion-exchange samples of glass are evaluated using a modified ISO 720 protocol, in which the glass is crushed to the particle size required by the ISO 720 standard, ion-exchanged in a molten salt bath of 100% KNO3 at a temperature of 450°C for at least 5 hours to induce a compressive stress layer in the individual glass particles, and then tested according to the ISO 720 standard. The ISO 720 standard is divided into individual types. Type HGA1 specifies an extracted Na2O equivalent of 62 μg or less; Type HGA2 specifies an extracted Na2O equivalent of more than 62 μg and 527 μg or less; and Type HGA3 specifies an extracted Na2O equivalent of more than 527 μg and 930 μg or less. The glass compositions described herein have ISO 720 hydrolysis resistance of Type HGA2 or higher, and some embodiments have Type HGA1 hydrolysis resistance or higher. It should be understood that lower class ranks have improved hydrolysis resistance performance. Therefore, compositions graded as HGA1 have better hydrolysis resistance than compositions graded as HGA2.

[0103] The glass composition forming the glass container is also chemically durable and resistant to degradation, as determined by the ISO 719 standard. The ISO 719 standard is the standard for the resistance of glass to degradation in distilled water (i.e., resistance to hydrolysis of glass). Non-ion-exchange samples of glass are evaluated according to the ISO 719 protocol. Ion-exchange samples of glass are evaluated using a modified ISO 719 protocol, in which the glass is crushed to the particle size required by the ISO 719 standard, ion-exchanged in a molten salt bath of 100% KNO3 at a temperature of 450°C for at least 5 hours to induce a compressive stress layer in the individual glass particles, and then tested according to the ISO 719 standard. The ISO 719 standard is divided into individual types. Type HGB1 specifies extracted Na2O equivalents of 31 μg or less; Type HGB2 specifies extracted Na2O equivalents greater than 31 μg and 62 μg or less; Type HGB3 specifies extracted Na2O equivalents greater than 62 μg and 264 μg or less; Type HGB4 specifies extracted Na2O equivalents greater than 264 μg and 620 μg or less; and Type HGB5 specifies extracted Na2O equivalents greater than 620 μg and 1085 μg or less. The glass compositions described herein have ISO 719 hydrolysis resistance of Type HGB2 or higher, and some embodiments have Type HGB1 hydrolysis resistance. It should be understood that lower class ranks have improved hydrolysis resistance performance. Therefore, compositions graded as HGB1 have better hydrolysis resistance than compositions graded as HGB2.

[0104] USP <660> With respect to the tests and / or European Pharmacopoeia 3.2.1 tests, the glass containers described herein have Type 1 chemical durability. As stated above, USP <660> Furthermore, the European Pharmacopoeia 3.2.1 test is performed in a glass container in its entirety, not with crushed glass particles, and therefore, USP <660> Furthermore, the European Pharmacopoeia 3.2.1 test can be used to directly evaluate the chemical durability of the inner surface of glass containers.

[0105] When referring to the classifications mentioned above in accordance with ISO 719, ISO 720, ISO 695, and DIN 12116, a glass composition or glass article having a specific classification "or higher" should be understood to mean that the performance of the glass composition is equal to or better than that of the specific classification. For example, a glass article with ISO 719 hydrolysis resistance of "HGB2" or higher may have the ISO 719 classification of HGB2 or HGB1. Damage resistance As described above in this specification, glass containers may be damaged, such as impact damage, scratches, and / or abrasions, as they are processed and filled. Such damage often occurs due to contact between separate glass containers or between a glass container and manufacturing equipment. This damage can generally result in through cracks that reduce the mechanical strength of the container and impair the integrity of its contents. Accordingly, in some embodiments described herein, the glass container 100 further comprises a smooth coating 160 located around at least a portion of the outer surface 106 of the body 102, as shown in Figure 8. In some embodiments, the smooth coating 160 may be located on at least the outer surface 106 of the body 102 of the glass container, while in other embodiments, one or more intermediate coatings may be located between the smooth coating and the outer surface 106 of the body 102, for example, when an inorganic coating is used to impart compressive stress to the surface of the body 102. The smooth coating reduces the coefficient of friction of a portion of the main body 102, thereby reducing the occurrence of abrasion and surface damage on the outer surface 106 of the glass main body 102. In short, the coating "slides" the container against other objects (or containers), thereby reducing the possibility of surface damage to the glass. Moreover, the smooth coating 160 also acts as a cushioning material on the main body 102 of the glass container 100, thereby reducing the impact of damage to the glass container from blunt impacts.

[0106] As used herein, the term "smooth" means that the coefficient of friction of a coating applied to the outer surface of a glass container is lower than that of an uncoated glass container, resulting in a glass container with improved resistance to damage such as scratches and abrasions.

[0107] Various properties of coated glass containers (i.e., coefficient of friction, horizontal compressive strength, four-point bending strength, clarity, colorlessness, etc.) can be measured in the as-coated state (i.e., after the application of the coating and before any further processing) or after one or more processing treatments, including but not limited to washing, freeze-drying, exothermic substance removal, autoclaving, etc., similar to or equivalent to those performed in a pharmaceutical filling line.

[0108] Pyrochemical removal is the process of removing a pyrogen from a substance. Pyrochemical removal from glass articles, such as pharmaceutical packaging, can be performed by heat treatment of the sample, where the sample is heated to a high temperature for a certain period of time. For example, pyrochemical removal may include a step of heating a glass container at a temperature of approximately 250°C to approximately 380°C for a period of approximately 30 seconds to approximately 72 hours, including, but not limited to, 20 minutes, 30 minutes, 40 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, 24 hours, 48 ​​hours, and 72 hours. After the heat treatment, the glass container is cooled to room temperature. One conventional pyrochemical removal condition commonly employed in the pharmaceutical industry is heat treatment at approximately 250°C for approximately 30 minutes. However, it is expected that the heat treatment time may be shortened when higher temperatures are used. The coated glass containers described herein may be exposed to high temperatures for a certain period of time. The high temperatures and times related to the heating steps described herein may or may not be sufficient for the removal of pyrogens from the glass container. However, it should be understood that some of the temperatures and times for the heating steps described herein are sufficient for the dehydrogenation of coated glass containers, such as the coated glass containers described herein. For example, as described herein, coated glass containers may be exposed to temperatures of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for a period of 30 minutes.

[0109] As used herein, freeze-drying conditions (i.e., freeze-drying step) refer to a process in which a sample is filled with a protein-containing liquid, then frozen at -100°C, and subsequently sublimated over 20 hours at -15°C under reduced pressure.

[0110] As used herein, autoclave conditions refer to purging a sample with steam at 100°C for 10 minutes, followed by exposing the sample to an environment at 121°C for a 20-minute stop, and then heat-treating it at 121°C for 30 minutes.

[0111] The coefficient of friction (μ) of a portion of a coated glass container having a smooth coating may be lower than that of an uncoated glass container formed from the same glass composition. The coefficient of friction (μ) is a quantitative measure of friction between two surfaces and depends on the mechanical and chemical properties of the first and second surfaces, including, but not limited to, surface roughness and environmental conditions such as temperature and humidity. As used herein, the measured coefficient of friction for a coated glass container 100 is reported as the coefficient of friction between the outer surface of a first glass container (having an outer diameter of about 16.00 mm to about 17.00 mm) and the outer surface of a second glass container equivalent to the first glass container, where the first and second glass containers have the same body and the same coating composition (if applicable) and were exposed to the same environment before, during, and after manufacturing. Unless otherwise specified herein, the coefficient of friction refers to the maximum coefficient of friction measured under a vertical load of 30 N in the vial superposition test fixture as described herein. However, it should be understood that a coated glass container that exhibits a maximum coefficient of friction at a particular load will also exhibit the same or better (i.e., a smaller) maximum coefficient of friction at smaller loads. For example, if a coated glass container exhibits a maximum coefficient of friction of 0.5 or less under a load of 50 N, it will also exhibit a maximum coefficient of friction of 0.5 or less under a load of 25 N.

[0112] In the embodiments described herein, the coefficient of friction of glass containers (both coated and uncoated) is measured using a vial superposition test fixture. A test fixture 300 is schematically illustrated in Figure 9. The same apparatus may also be used to measure the frictional force between two glass containers placed in the fixture. The vial superposition test fixture 300 comprises a first clamp 312 and a second clamp 322 arranged in an intersecting configuration. The first clamp 312 comprises a first fixing arm 314 connected to a first base 316. A first glass container 310 is attached to the first fixing arm 314, and the first glass container 310 is fixedly held against the first clamp 312. Similarly, the second clamp 322 comprises a second fixing arm 324 connected to a second base 326. A second glass container 320 is attached to a second fixed arm 324, and the glass container 320 is fixedly held in place by a second clamp 322. The first glass container 310 is positioned by the first clamp 312 and the second glass container 320 is positioned by the second clamp 322 such that the long axes of the first glass container 310 and the long axes of the second glass container 320 are positioned at an angle of approximately 90° to each other on a horizontal plane defined by the x and y axes.

[0113] The first glass container 310 is positioned to contact the second glass container 320 at a contact point 330. A normal force is applied in a direction perpendicular to the horizontal plane defined by the x and y axes. The normal force can be applied by static weight or other force applied to the second clamp 322 relative to the fixed first clamp 312. For example, a weight may be placed on the second base 326 and the first base 316 placed on a stable surface, thereby inducing a measurable force between the first glass container 310 and the second glass container 320 at the contact point 330. Alternatively, the force may be applied by a mechanical device such as a UMT (Universal Mechanical Tester) machine.

[0114] The first clamp 312 or the second clamp 322 may be moved relative to the other at a 45° angle along the long axis of the first glass container 310 and the long axis of the second glass container 320. For example, the first clamp 312 may be fixed, and the second clamp 322 may be moved so that the second glass container 320 crosses the first glass container 310 in the x-axis direction. A similar mechanism is described by RLDe Rosa et al., "Scratch Resistant Polyimide Coatings for Alumino Silicate Glass Surfaces", The Journal of Adhesion, 78:113-127, 2002. To measure the coefficient of friction, the force required to move the second clamp 322 and the vertical force applied to the first and second glass containers 310, 320 are measured with a load cell, and the coefficient of friction is calculated as the quotient of the ratio of the frictional force to the vertical force. The fixture is operated in an environment of 25°C and 50% relative humidity.

[0115] In the embodiments described herein, a portion of a coated glass container having a smooth coating has a coefficient of friction of about 0.7 or less compared to a similarly coated glass container, as measured by the vial overlay fixture described above. In other embodiments, the coefficient of friction may be about 0.6 or less, or even about 0.5 or less. In some embodiments, a portion of a coated glass container having a smooth coating has a coefficient of friction of about 0.4 or less, or even about 0.3 or less. Coated glass containers having a coefficient of friction of about 0.7 or less generally exhibit high resistance to frictional damage and, as a result, have high mechanical properties. For example, conventional glass containers (without a smooth coating) may have a coefficient of friction greater than 0.7.

[0116] In some embodiments described herein, the coefficient of friction of a portion of a coated glass container having a smooth coating is at least 20% lower than the coefficient of friction of the surface of an uncoated glass container formed from the same glass composition. For example, the coefficient of friction of a portion of a coated glass container having a smooth coating may be at least 20%, at least 25%, at least 30%, at least 40%, or even at least 50% lower than the coefficient of friction of the surface of an uncoated glass container formed from the same glass composition.

[0117] In some embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less after exposure for 30 minutes to temperatures of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C (i.e., under exothermic material removal conditions). In other embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less (i.e., about 0.6 or less, about 0.5 or less, about 0.4 or less, or even about 0.3 or less) after exposure to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for 30 minutes. In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating may not increase by more than about 30% after exposure to a temperature of about 260°C for 30 minutes. In another embodiment, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase by more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%) after exposure for 30 minutes to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C. In other embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase beyond about 0.5 (i.e., about 0.45, about 0.04, about 0.35, about 0.3, about 0.25, about 0.2, about 0.15, about 0.1, or even about 0.5) after exposure for 30 minutes to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C.In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase at all after being exposed for 30 minutes to temperatures of approximately 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, or 400°C.

[0118] In some embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less after being immersed in a water bath at a temperature of about 70°C for 10 minutes. In other embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less (i.e., about 0.6 or less, about 0.5 or less, about 0.4 or less, or even about 0.3 or less) after being immersed in a water bath at a temperature of about 70°C for 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or even 1 hour. In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating may not increase by more than about 30% after being immersed in a water bath at a temperature of about 70°C for 10 minutes. In other embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase by more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%) after immersion in a water bath at a temperature of about 70°C for 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or even 1 hour. In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase at all after immersion in a water bath at a temperature of about 70°C for 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or even 1 hour.

[0119] In some embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less after exposure to freeze-drying conditions. In other embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less (i.e., about 0.6 or less, about 0.5 or less, about 0.4 or less, or even about 0.3 or less) after exposure to freeze-drying conditions. In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase by more than about 30% after exposure to freeze-drying conditions. In other embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase by more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%) after exposure to freeze-drying conditions. In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase at all after exposure to freeze-drying conditions.

[0120] In some embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less after exposure to autoclave conditions. In other embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less (i.e., about 0.6 or less, about 0.5 or less, about 0.4 or less, or even about 0.3 or less) after exposure to autoclave conditions. In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase by more than about 30% after exposure to autoclave conditions. In other embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase by more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%) after exposure to autoclave conditions. In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating cannot increase at all after exposure to autoclave conditions.

[0121] In some embodiments, after a glass container 100 having a smooth coating 160 is rubbed with a 30N vertical force by a comparable glass container, the coefficient of friction of the rubbed area of ​​the glass container 100 does not increase by more than about 20% after further rubbing by the comparable glass container with a 30N vertical force at the same location. In other embodiments, after a glass container 100 having a smooth coating 160 is rubbed with a 30N vertical force by a comparable glass container, the coefficient of friction of the rubbed area of ​​the glass container 100 does not increase by more than about 15%, or even more than 10%, after further rubbing by the comparable glass container with a 30N vertical force at the same location. However, it is not essential that all embodiments of the glass container 100 having a smooth coating 160 exhibit such properties.

[0122] The coated glass containers described herein have horizontal compressive strength. The horizontal compressive strength described herein is measured by a horizontal compression device 500 schematically illustrated in Figure 4. The coated glass container 100 is tested by positioning the container horizontally between two platens 502a, 502b oriented parallel to the long axis of the glass container, as shown in Figure 4. A mechanical load 504 is then applied to the coated glass container 100 by the platens 502a, 502b in a direction perpendicular to the long axis of the glass container. The load rate for compressing the vial is 0.5 in / min, meaning that the platens move toward each other at a speed of 0.5 in / min. The horizontal compressive strength is measured at 25°C and 50% relative humidity. The measured value of horizontal compressive strength can be determined as the probability of fracture under a selected vertical compressive load. As used herein, fracture is defined as occurring when the glass container breaks in at least 50% of the samples under horizontal compression. In some embodiments, coated glass containers may have a horizontal compressive strength at least 10%, 20%, or 30% greater than that of uncoated vials.

[0123] Referring here to Figures 8 and 9, the measurement of horizontal compressive strength can also be performed on abraded glass containers. Specifically, the test fixture 300 is manipulated to form damage such as surface scratches or abrasions on the outer surface of the coated glass container 100, thereby reducing the strength of the coated glass container. The glass container is then subjected to the horizontal compression method described above, where the container is placed between two platens such that the scratches face outward parallel to the platens. The scratches can be characterized by a selected vertical pressure applied by a vial overlay fixture and the length of the scratches. Unless otherwise specified, scratches on abraded glass containers in the horizontal compression method are characterized by a scratch length of 20 mm formed by a vertical load of 30 N.

[0124] Coated glass containers can be evaluated for horizontal compressive strength after heat treatment. Heat treatment may involve 30 minutes of exposure to temperatures of approximately 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, or 400°C. In some embodiments, the horizontal compressive strength of a coated glass container, after exposure to a heat treatment such as those described above and then abrasion as described above, is not reduced by more than 20%, 30%, or even 40%. In one embodiment, the horizontal compressive strength of a coated glass container is not reduced by more than about 20% after being subjected to a heat treatment at about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for 30 minutes, and then rubbed.

[0125] In some other embodiments, a glass container 100 having a smooth coating 160 may be thermally stable at high temperatures. As used herein, the phrase “thermally stable” means that the smooth coating 160 applied to the glass container remains substantially intact on the surface of the glass container after exposure to high temperatures, such that any impact on the mechanical properties of the coated glass container, specifically the coefficient of friction and horizontal compressive strength, is minimal after the exposure. This indicates that the smooth coating remains adhered to the glass surface after exposure to high temperatures, continuously protecting the glass container from mechanical damage such as abrasion and impact. A glass container having a smooth coating as described herein may be thermally stable even after heating to a temperature of at least about 250°C, or even further to about 260°C for 30 minutes.

[0126] In the embodiments described herein, a glass container having a smooth coating (i.e., a coated glass container) is considered thermally stable if, after heating to a specific temperature and holding at that temperature for a specific time, it satisfies both the coefficient of friction criterion and the horizontal compressive strength criterion. To determine whether the coefficient of friction criterion is met, the coefficient of friction of a first coated glass container is measured in its as-received state (i.e., before heat exposure) using the test fixture shown in Figure 9 with a 30 N load. A second coated glass container (i.e., a glass container having the same glass composition and the same coating composition as the first coated glass container) is exposed to heat under specified conditions and cooled to room temperature. The coefficient of friction of the second glass container is then measured by rubbing the coated glass container with a 30 N load using the test fixture shown in Figure 9, resulting in a scratch approximately 20 mm long. The coefficient of friction criterion satisfies the purpose of measuring the thermal stability of the smooth coating if the coefficient of friction of the second coated glass container is less than 0.7 and there is no observable damage whatsoever on the glass surface of the second glass container in the abraded area. As used herein, the term “observable damage” means that the glass surface in the abraded area of ​​the glass container contains fewer than six glass cracks per 0.5 cm abraded area when observed at 100x magnification with a Nomarski or differential interference contrast (DIC) spectroscopic microscope using an LED or halogen light source. The definition of glass cracks or glass fractures is given in GD Quinn, “NIST Recommended Practice Guide: Fractography of Ceramics and Glasses,” NIST special publication, 960-17 (2006).

[0127] To determine whether the horizontal compressive strength criterion is met, the first coated glass container is rubbed under a 30 N load in the test fixture shown in Figure 9 to form a 20 mm scratch. The first coated glass container is then subjected to the horizontal compression test described herein to measure its residual strength. The second coated glass container (i.e., a glass container having the same glass composition and coating composition as the first coated glass container) is exposed to heat under specified conditions and cooled to room temperature. The second coated glass container is then rubbed under a 30 N load in the test fixture shown in Figure 9. The second coated glass container is then subjected to the horizontal compression test as described herein to measure its residual strength. If the residual strength of the second coated glass container does not decrease by more than approximately 20% compared to the first coated glass container, the horizontal compressive strength criterion is met for the purpose of determining the thermal stability of the smooth coating.

[0128] In the embodiments described herein, a coated glass container is considered thermally stable if the friction coefficient criterion and the horizontal compressive strength criterion are met after the coated glass container has been exposed to a temperature of at least about 250°C, or more precisely, about 260°C, for about 30 minutes (i.e., the coated glass container is thermally stable for about 30 minutes at a temperature of at least about 250°C, or more precisely, about 260°C). Thermal stability may also be evaluated at temperatures between about 250°C and about 400°C. For example, in some embodiments, a coated glass container would be considered thermally stable if the criteria are met for about 30 minutes at a temperature of at least about 270°C, or more precisely, about 280°C. In yet another embodiment, a coated glass container would be considered thermally stable if the criteria are met for about 30 minutes at a temperature of at least about 290°C, or more precisely, about 300°C. In a further embodiment, a coated glass container would be considered thermally stable if the criteria are met at a temperature of at least about 310°C, or even more precisely, about 320°C for about 30 minutes. In yet another embodiment, a coated glass container would be considered thermally stable if the criteria are met at a temperature of at least about 330°C, or even more precisely, about 340°C for about 30 minutes. In yet another embodiment, a coated glass container would be considered thermally stable if the criteria are met at a temperature of at least about 350°C, or even more precisely, about 360°C for about 30 minutes. In some other embodiments, a coated glass container would be considered thermally stable if the criteria are met at a temperature of at least about 370°C, or even more precisely, about 380°C for about 30 minutes. In yet another embodiment, a coated glass container would be considered thermally stable if the criteria are met at a temperature of at least about 390°C, or even more precisely, about 400°C for about 30 minutes.

[0129] The coated glass containers disclosed herein may also be thermally stable over a range of temperatures, meaning that the coated glass containers are thermally stable by meeting friction coefficient and horizontal compressive strength criteria at each temperature within the range. For example, in embodiments described herein, the coated glass containers may be thermally stable at temperatures of at least about 250°C or even more between about 260°C and about 400°C. In some embodiments, the coated glass containers may be thermally stable in the range of at least about 250°C or even more between about 260°C and about 350°C. In some other embodiments, the coated glass containers may be thermally stable at temperatures of at least about 280°C and about 350°C. In yet another embodiment, the coated glass containers may be thermally stable at at least about 290°C and about 340°C. In other embodiments, the coated glass containers may be thermally stable in a range of temperatures of about 300°C and about 380°C. In other embodiments, the coated glass container may be thermally stable over a range of temperatures from about 320°C to about 360°C.

[0130] Mass loss refers to a measurable property of a coated glass container related to the amount of volatile matter released from the coated glass container when it is exposed to a selected high temperature for a selected time. Mass loss generally indicates the mechanical degradation of the coating due to thermal exposure. Since the glass body of a coated glass container does not exhibit measurable mass loss at the measured temperature, mass loss tests, as detailed herein, only provide mass loss data for smooth coatings applied to glass containers. Several factors can influence mass loss. For example, the amount of organic material that can be removed from the coating can affect mass loss. Breakage of the carbon back chain and side chains in polymers theoretically results in 100% coating removal. Organometallic polymer materials typically lose all of their organic components, while the inorganic components remain. Therefore, the mass loss results are normalized based on the degree to which the coating is organic and inorganic (e.g., % silica of the coating) in a complete theoretical oxidation.

[0131] To measure mass loss, a coated sample, such as a coated glass container, is first heated to 150°C and maintained at this temperature for 30 minutes to dry the coating and completely evaporate H2O from the coating. The sample is then heated from 150°C to 350°C in an oxidizing environment such as air at a heating rate of 10°C / min. For the purpose of measuring mass loss, only data recovered between 150°C and 350°C is considered. In some embodiments, a smooth coating has a mass loss of less than about 5% of its mass when heated from 150°C to 350°C at a heating rate of about 10°C / min. In other embodiments, a smooth coating has a mass loss of less than about 3%, or even less than 2%, when heated from 150°C to 350°C at a heating rate of about 10°C / min. In some other embodiments, a smooth coating has a mass loss of less than 1.5% when heated from 150°C to 350°C at a heating rate of about 10°C / min. In some other embodiments, the smooth coating has a mass loss of less than 0.75% when heated from 150°C to 350°C at a heating rate of about 10°C / min. In some other embodiments, the smooth coating loses virtually no mass when heated from 150°C to 350°C at a heating rate of about 10°C / min.

[0132] The mass loss results are based on a method of comparing the weight of the coated glass container before and after heat treatment, such as heating from 150°C to 350°C at a rate of 10°C / minute, as described herein. The weight difference between the vial before and after heat treatment, as can be determined by comparing the weight of the coating before heat treatment (excluding the glass body of the container, after the preheating step) with the weight of an uncoated glass container and the weight of a coated glass container before treatment, represents the weight loss of the coating. This can be standardized as the weight loss ratio of the coating. Alternatively, the total mass of the coating can be determined by a total organic carbon test or other similar means.

[0133] Referring here to Figure 10, degassing refers to a measurable characteristic of the coated glass container 100 relating to the amount of volatile matter released from the coated glass container 100 when the coated glass container is exposed to a selected high temperature for a selected time. In this specification, the degassing measurement is reported as the amount of free volatile matter per unit surface area of ​​the coated glass container during exposure to a high temperature for a set period of time. Since the glass body of the coated glass container does not exhibit measurable degassing at the temperature reported for degassing, the degassing test, as detailed above, substantially yields degassing data only for the smooth coating applied to the glass container. The degassing results are based on a method in which the coated glass container 100 is placed in the glass sample chamber 402 of the apparatus 400 illustrated in Figure 10. A background sample from an empty sample chamber is collected prior to each sample test. The sample chamber is maintained under a constant air purge of 100 ml / min as measured by a rotometer 406, while the heating furnace 404 is heated to 350°C and held at that temperature for 1 hour to collect a background sample from the chamber. Subsequently, a coated glass container 100 is placed in the sample chamber 402, and the sample chamber is maintained under a constant air purge of 100 ml / min, heated to a high temperature, and held at that temperature for a certain period of time to collect a sample from the coated glass container 100. The glass sample chamber 402 is made of "Pyrex" and its maximum analytical temperature is limited to 600°C. A Carbotrap 300 adsorbent trap 408 is constructed at the discharge port of the sample chamber, and volatile species released from the sample are adsorbed by blowing an absorbent resin for volatile species adsorption with an air purge gas 410. Next, the absorbent resin is placed directly into the Gerstel Thermal Desorption unit, which is directly connected to the Hewlett Packard 5890 Series II gas chromatograph / Hewlett Packard 5989 MS engine.The degassed species are thermally desorbed from the adsorbent resin at 350°C and collected at cryogenic temperatures on the head of a nonpolar gas chromatography column (DB-5MS). The temperature in gas chromatography is increased at a rate of 10°C / min to a final temperature of 325°C to separate and purify volatile and semi-volatile organic species. The separation mechanism has been demonstrated to be substantially based on the heat of vaporization of different organic species, resulting in boiling point or distillation chromatograms. After separation, the purified species are analyzed by conventional electron shock ionization mass spectrometry protocols. By operating under standard conditions, the resulting mass spectra can be compared to existing mass spectrum libraries.

[0134] In some embodiments, the coated glass containers described herein exhibit degassing of less than or equal to about 54.6 ng / cm², less than or equal to about 27.3 ng / cm², or even less than or equal to about 5.5 ng / cm² during exposure to high temperatures of about 250°C, about 275°C, about 300°C, about 320°C, about 360°C, or even about 400°C for a period of about 15 minutes, about 30 minutes, about 45 minutes, or about 1 hour. Furthermore, the coated glass containers may be thermally stable in a particular temperature range, meaning that the coated containers exhibit constant degassing as described above at all temperatures within that particular range. Prior to degassing measurement, the coated glass containers may be in their uncoated state (i.e., immediately after the application of the smooth coating) or after one of the following: removal of exothermic substances, freeze-drying, or autoclave. In some embodiments, the coated glass container 100 may not exhibit substantially degassing.

[0135] In some embodiments, degassing data can be used to measure the mass loss rate of a smooth coating. The pre-heat treatment coating mass can be measured by the coating thickness (measured by SEM imaging or other means), the density of the smooth coating, and the surface area of ​​the coating. The coated glass container can then be subjected to a degassing method, and the mass loss rate can be measured by finding the ratio of the mass released during degassing to the pre-heat treatment mass.

[0136] The coated glass containers described herein have a four-point bending strength. To measure the four-point bending strength of the glass container, a glass tube that will be a precursor to the coated glass container 100 is used for the measurement. The glass tube has the same diameter as the glass container but does not have the bottom or mouth of the glass container (i.e., before the glass container is formed from the tube). The glass tube is then subjected to a four-point bending stress test to induce mechanical failure. The test is performed at a relative humidity of 50%, with the outer contact members separated by 9 inches (22.86 cm) and the inner contact members separated by 3 inches (7.62 cm), and at a loading rate of 10 mm / min.

[0137] Four-point bending stress measurements can also be performed on coated and abraded tubes. As described in the measurement of the horizontal compressive strength of abraded vials, the test fixture 300 is manipulated to form abrasions on the tube surface, such as surface scratches that reduce the strength of the tube. The glass tube is then subjected to a four-point bending stress test to induce mechanical failure. The test is performed at 25°C and 50% relative humidity, using an outer probe spaced 9 inches (22.86 cm) apart and an inner contact member spaced 3 inches (7.62 cm) apart at a loading rate of 10 mm / min, while the tube is positioned so that scratches are formed under tension during the test.

[0138] In some embodiments, the four-point bending strength of a glass tube with a smooth coating after abrasion is, on average, at least 10%, 20%, or even 50% higher than that of an uncoated glass tube abraded under the same conditions.

[0139] Referring to Figure 11, the transparency and color of a coated container can be evaluated by measuring the light transmittance of the container using a spectrophotometer at a range of wavelengths from 400 to 700 nm. The measurement is performed by directing a light beam perpendicular to the container wall so that the light beam passes through the smooth coating twice, once upon entry into the container and once upon exit. In some embodiments, the light transmittance of a coated glass container may be at least 55% of that of an uncoated glass container at wavelengths from about 400 nm to about 700 nm. As described herein, the light transmittance can be measured before or after heat treatment, such as the heat treatment described herein. For example, at each wavelength from about 400 nm to about 700 nm, the light transmittance may be at least 55% of that of an uncoated glass container. In other embodiments, the light transmittance of the coated glass container is approximately 55% or more, approximately 60%, approximately 65%, approximately 70%, approximately 75%, approximately 80%, or even approximately 90% of the light transmittance of the uncoated glass container for wavelengths of approximately 400 nm to approximately 700 nm.

[0140] As described herein, light transmittance can be measured before or after environmental treatments such as heat treatment as described herein. For example, after heat treatment at approximately 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C for 30 minutes, or after exposure to freeze-drying conditions, or after exposure to autoclave conditions, the light transmittance of a coated glass container is approximately 55% or more, approximately 60%, approximately 65%, approximately 70%, approximately 75%, approximately 80%, or even approximately 90% of the light transmittance of an uncoated glass container for wavelengths of approximately 400 nm to approximately 700 nm.

[0141] In some embodiments, the coated glass container 100 may be perceived as colorless and transparent to the naked eye when viewed from all angles. In some other embodiments, the smooth coating 160 may have a perceptible tint, such as when the smooth coating 160 contains a polyimide formed from poly(pyromellitic dianhydride-co-4,4'-oxydianiline)amide acid, which is commercially available from Aldrich.

[0142] In some embodiments, the glass container 100 having a smooth coating 160 may have an outer surface to which an adhesive label can be attached. In other words, although the smooth coating 160 has a low coefficient of friction, the coating is capable of to which an adhesive label can be attached so that the label is securely attached. However, the ability to attach an adhesive label is not required for all embodiments of the glass container 100 having a smooth coating 160 described herein.

[0143] Referring again to Figure 8, in some embodiments, the smooth coating 160 may be a temporary coating. As used herein, the term “temporary coating” means that the coating is not permanently adhered to the glass container 100, but can be removed from the glass container 100 by washing, heating (i.e., thermal decomposition), etc. For example, in embodiments where the smooth coating 160 is a temporary coating that can be removed by thermal decomposition, the coating can be thermally decomposed at a temperature of about 300°C or less. Alternatively, the smooth coating 160 may be a temporary coating that can be removed by washing the glass container with a solution of detergent and water.

[0144] In the embodiments described herein, glass containers may be coated with inorganic coatings, pseudo-organic coatings, and / or robust organic coatings to achieve a desired low coefficient of friction and resistance to damage. Inorganic coating Referring further to Figure 8, in some embodiments described herein, the smooth coating 160 is an inorganic coating. The inorganic coating may be a robust inorganic coating permanently bonded to the outer surface 106 of the body 102 of the glass container. The properties of the robust inorganic coating are not degraded by exposure to high temperatures, and therefore the coefficient of friction and horizontal compressive strength of the glass container having the robust inorganic coating are substantially the same before and after exposure to high temperatures, including temperatures in the range of about 250°C to about 400°C, although this is not particularly limited. The robust inorganic coating is a continuous coating applied to at least a portion of the outer surface of the body and is generally insoluble in water and / or organic solvents. For example, in some embodiments, the robust inorganic coating may include a metal nitride coating, a metal sulfide coating, a metal oxide coating, SiO2, diamond-like carbon, or carbide coating. For example, robust inorganic coatings may include tin, BN, hBN, TiO2, Ta2O5, HfO2, Nb2O5, V2O5, SnO, SnO2, ZrO2, Al2O3, SiO2, ZnO, MoS2, BC, SiC, or at least one of similar metal oxides, metal nitrides, and carbide coatings, exhibiting a relatively low coefficient of friction compared to similar coated glass containers, and having relatively high thermal stability. In these embodiments, the coating may be applied to the outer surface of the glass container by physical vapor deposition methods such as evaporation, electron beam evaporation, DC magnetron sputtering, non-equilibrium DC magnetron sputtering, AC magnetron sputtering, and non-equilibrium AC magnetron sputtering. Alternatively, the coating may be applied by powder coating. Chemical vapor deposition (CVD) techniques can also be used for coating applications, including ultra-high vacuum CVD, low-pressure CVD, atmospheric pressure CVD, metal-organic CVD, laser CVD, photochemical CVD, aerosol-assisted CVD, microwave plasma-assisted CVD, plasma-assisted CVD, direct liquid injection CVD, atomic layer CVD, combustion CVD, hot-wire CVD, fast thermal CVD, chemical vapor deposition penetration, and chemical beam epitaxy.

[0145] In a particular embodiment, the robust inorganic coating is diamond-like carbon. Films or coatings formed from diamond-like carbon generally exhibit a low coefficient of friction and high hardness. Specifically, a substantial amount of carbon in the DLC coating is SP3 hybridized carbon. This material imparts certain properties of diamond to these coatings, such as high hardness and excellent wear resistance. The hardness of the DLC coating is directly proportional to the SP3 hybridized content. DLC coatings can be deposited on the outer surface of glass containers by ion beam deposition, cathode arc spraying, pulsed laser ablation, argon ion sputtering, and plasma-assisted chemical deposition. Depending on the thickness of the DLC coating to be deposited, the specific deposition method, and the composition of the coating, the color of the deposited layer can be changed from optically transparent yellow (i.e., a 0.1 μm thick DLC film may be optically transparent with a slightly yellowish tint) to amber and black.

[0146] Alternatively, the smooth coating 160 may be an inorganic coating that is temporarily fixed to the outer surface of a glass container, such as a temporary coating. In these embodiments, the temporary coating may contain inorganic salts such as MgSO4, CaSO4, Ca3(PO4)2, Mg3(PO4)2, KNO3, K3PO4, etc. Organic coating In some alternative embodiments, the smooth coating 160 may be an organic coating that is temporarily fixed to the outer surface of the glass container, such as a temporary coating, or a robust organic coating that is permanently fixed to the outer surface of the glass container.

[0147] Regarding organic temporary coatings, it is desirable to protect the surface of glass articles (such as glass containers) from damage during manufacturing in order to mitigate the reduction in the mechanical strength of the glass due to surface defects caused by contact with the glass. This is generally achieved by applying a coating with a low coefficient of friction, as described above. However, since glass containers may be subjected to further processing, it is not necessary to permanently adhere the coating to the outer surface of the glass container; instead, the coating can be removed in downstream processing steps after it has served its purpose of protecting the glass article. For example, the temporary coating can be removed by thermal decomposition. In the embodiments described herein, the temporary coating can be thermally decomposed at a temperature of 300°C or less for a time of 1 hour or less. Alternatively, the temporary coating can be thermally decomposed at a temperature of 265°C for 2.5 hours, or even at a temperature of 360°C for 10 minutes or less.

[0148] Various organic materials can be used to form a temporary coating. For example, in some embodiments, the temporary coating may include a mixture of polyoxyethylene glycol, methacrylate resin, melamine formaldehyde resin, and polyvinyl alcohol, as disclosed in U.S. Patent No. 3,577,256. Such a coating can be applied to the outer surface of a molded glass container and can be thermally decomposed from the glass surface in an annealing slow-cooling kiln.

[0149] In other embodiments, the artificial organic coating may comprise one or more polysaccharides, as disclosed in U.S. Patent No. 6,715,316B2, which describes removable protective coatings. Such coatings can be removed from glass surfaces using a mild aqueous cleaning agent, such as 2% Semiclean KG in water.

[0150] In other embodiments, the pseudo-organic coating may be a “cold-end” coating as described in U.S. Patent No. 4,055,441, or a similar coating. Such coatings may include poly(ethylene oxide), poly(propylene oxide), ethylene oxide-propylene oxide copolymer, polyvinyl-pyrrolidinone, polyethyleneamine, poly(methyl vinyl ether), polyacrylamide, polymethacrylamide, polyurethane, poly(vinyl acetate), polyvinyl formal, polyformaldehyde including polyacetal and acetal copolymers, poly(alkyl methacrylate), methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, sodium carboxymethylcellulose, methylhydroxypropylcellulose, poly(acrylic acid) and its salts, poly(methacrylic acid) and its salts, ethylene-maleic anhydride copolymer, ethylene - May be formed from at least one of vinyl alcohol copolymers, ethylene-acrylic acid copolymers, vinyl acetate-vinyl alcohol copolymers, methyl vinyl ether-maleic anhydride copolymers, emulsifying polyurethanes, polyoxyethylene stearate, and polyethylene, polyolefins including polypropylene and its copolymers, starch and modified starch, hydrophilic colloids, polyacryloamides, vegetable fats and animal fats, waxes, tallow, soaps, stearin-paraffin emulsions, polysiloxanes of dimethyl or diphenyl or methyl / phenyl mixtures, perfluorinated siloxanes and other substituted siloxanes, alkylsilanes, aromatic silanes, and polyethylene oxide and combinations thereof or similar coatings.

[0151] A temporary organic coating can be applied by bringing such a coating into direct contact with a glass container. For example, the coating can be applied by a dipping process, or by spraying or other suitable means. The coating can then be dried and optionally cured at a high temperature.

[0152] Referring here to Figures 8 and 12A, in some embodiments, the smooth coating 160 is a robust organic coating adhered to at least a portion of the outer surface 106 of the glass body 102. The robust organic coating has a low coefficient of friction as described above, and is also thermally stable at high temperatures. The smooth coating 160 has an outer surface 162 and a glass contact surface 164. In embodiments where the smooth coating 160 is a robust organic coating, the smooth coating 160 may include a coupling agent layer 180 that is in direct contact with the outer surface 106 of the glass body 102, and a polymer layer 170 that is in direct contact with the coupling agent layer 180. However, it should be understood that in some embodiments, the smooth coating 160 may not include the coupling agent layer 180, and the polymer layer 170 may be in direct contact with the outer surface 106 of the glass body 102. In some embodiments, the smooth coating 160 is the coating layer described in U.S. Provisional Patent Application No. 13 / 780,754, filed on 28 February 2013 and titled “Glass Articles with Low Friction Coatings,” which is incorporated herein by reference in its entirety.

[0153] Referring here to Figures 8 and 12A, in one embodiment, the smooth coating 160 comprises a two-layer structure. Figure 12A shows a cross-section of a portion of a coated glass container, where the smooth coating 160 comprises a polymer layer 170 and a coupling agent layer 180. The polymer chemical composition may be contained in the polymer layer 170, and the coupling agent may be contained in the coupling agent layer 180. The coupling agent layer 180 may be in direct contact with the outer surface 106 of the glass body 102. The polymer layer 170 may be in direct contact with the coupling agent layer 180 and may form the outer surface 162 of the smooth coating 160. In some embodiments, the coupling agent layer 180 is bonded to the outer surface 106 of the glass body 102, and the polymer layer 170 is bonded to the coupling agent layer 180 at an interface 174. However, it should be understood that in some embodiments, the smooth coating 160 may not contain a coupling agent, and the polymer chemical composition may be present in the polymer layer 170 that is in direct contact with the outer surface 106 of the glass body 102. In other embodiments, the polymer chemical composition and the coupling agent may be substantially mixed in a single layer. In some other embodiments, the polymer layer 170 may be located on the upper surface of the coupling agent layer 180, meaning that the polymer layer 170 is an outer layer relative to the coupling agent layer 180 and the outer surface 106 of the glass body 102. As used herein, a first layer located on the "upper surface" of a second layer means that the first layer may be in direct contact with the second layer, or it may be separated from the second layer, such as when a third layer is positioned between the first and second layers.

[0154] Referring here to Figure 12B, in one embodiment, the smooth coating 160 may further include an interface layer 190 located between the coupling agent layer 180 and the polymer layer 170. The interface layer 190 may include one or more chemical compositions of the polymer layer 170 bonded to one or more chemical compositions of the coupling agent layer 180. In this embodiment, the interface layer 190 is formed at the interface between the coupling agent layer 180 and the polymer layer 170, where bonding occurs between the polymer chemical composition and the coupling agent. However, in some embodiments, as described above with reference to Figure 12A, there may be no layer corresponding to the interface between the coupling agent layer 180 and the polymer layer 170, in which case it should be understood that the polymer and the coupling agent are chemically bonded to each other.

[0155] In other embodiments, the polymer chemical composition and the coupling agent may be substantially mixed in a single layer to form a homogeneous layer of smooth coating. Such a mixed single layer may be in direct contact with the outer surface 106 of the glass body 102. As described herein, the materials of the polymer layer 170 and the coupling agent layer 180 (i.e., at least polymer and at least coupling agent, respectively) may be mixed to form at least one layer of smooth coating 160. The mixed layer smooth coating 160 may further contain materials other than the polymer chemical composition and the coupling agent. To form the mixed layer smooth coating 160, the various materials of such layers may be mixed together in solution before application of the smooth coating 160 to the glass container 100. In other embodiments, the mixed layer may be above or below the unmixed layer, for example, a mixed layer of polymer and coupling agent below a layer consisting substantially only of polymer material. In other embodiments, the smooth coating may contain three or more layers, such as three or four layers.

[0156] The smooth coating 160 applied to the outer surface 106 of the glass body 102 may have a thickness of less than about 100 μm, or even less than about 1 μm. In some embodiments, the thickness of the smooth coating 160 may be less than about 100 nm. In other embodiments, the smooth coating 160 may be less than about 90 nm, less than about 80 nm, less than about 70 nm, less than about 60 nm, less than about 50 nm, or even less than about 25 nm. In some embodiments, the smooth coating 160 may not have a uniform thickness over the entire surface of the glass body 102. For example, the coated glass container 100 may have a thicker smooth coating 160 in certain areas due to the process of bringing the outer surface 106 of the glass body 102 into contact with one or more coating solutions that form the smooth coating 160. In some embodiments, the smooth coating 160 may have an uneven thickness. For example, the thickness of the coating may vary across different areas of the coated glass container 100, which may enhance protection in selected areas. In other embodiments, only a selected portion of the outer surface 106 of the glass body is coated with the smooth coating 160.

[0157] In embodiments comprising at least two layers, such as a polymer layer 170, an interface layer 190, and / or a coupling agent layer 180, each layer may have a thickness of less than about 100 μm, or even less than about 1 μm. In some embodiments, the thickness of each layer may be less than about 100 nm. In other embodiments, each layer may have a thickness of less than about 90 nm, less than about 80 nm, less than about 70 nm, less than about 60 nm, less than about 50 nm, or even less than about 25 nm.

[0158] As described herein, in some embodiments, the smooth coating 160 includes a coupling agent. The coupling agent can improve the adhesion or bonding of the polymer chemical composition to the outer surface 106 of the glass body 102, and is generally located between the glass body 102 and the polymer chemical composition of the chemical composition layer 170, or mixed with the polymer chemical composition. As used herein, adhesion refers to the strength of the adhesion or bonding of the polymer layer before and after a treatment applied to the coated glass container, such as heat treatment. Examples of heat treatments, though not particularly limited, include autoclaving, removal of exothermic substances, and freeze-drying.

[0159] In one embodiment, the coupling agent may comprise at least one silane chemical composition. As used herein, a “silane” chemical composition is any chemical composition comprising an organosilane functional group and a silane moiety comprising a silanol formed from silane in aqueous solution. The silane chemical composition of the coupling agent may be aromatic or aliphatic. In some embodiments, at least one silane chemical composition may comprise an amine moiety, such as a primary amine moiety or a secondary amine moiety. Furthermore, the coupling agent may comprise hydrolysates and / or oligomers of such silanes, such as one or more silsesquioxane chemical compositions formed from one or more silane chemical compositions. The silsesquioxane chemical composition may comprise a fully caged structure, a partially caged structure, or an uncaged structure.

[0160] The coupling agent may comprise any number of different chemical compositions, such as one chemical composition, two different chemical compositions, or more than two different chemical compositions comprising oligomers formed from two or more monomeric chemical compositions. In one embodiment, the coupling agent may comprise (1) a first silane chemical composition, its hydrolysate or its oligomer, and (2) at least one of a chemical composition formed from oligomerization of at least the first silane chemical composition and the second silane chemical composition. In other embodiments, the coupling agent comprises first and second silanes. As used herein, the “first” silane chemical composition and the “second” silane chemical composition are silanes having different chemical compositions. The first silane chemical composition may be an aromatic or aliphatic chemical composition, optionally containing an amine moiety, and optionally being an alkoxysilane. Similarly, the second silane chemical composition may be an aromatic or aliphatic chemical composition, optionally containing an amine moiety, and optionally being an alkoxysilane.

[0161] For example, in one embodiment, only one silane chemical composition is applied as the coupling agent. In such embodiments, the coupling agent may include the silane chemical composition, its hydrolysate, or its oligomer.

[0162] In other embodiments, multiple silane chemical compositions may be applied as coupling agents. In such embodiments, the coupling agent may include (1) a mixture of a first silane chemical composition and a second silane chemical composition, and (2) at least one of a chemical composition formed from oligomerization of at least the first silane chemical composition and the second silane chemical composition.

[0163] Referring to the embodiments described above, the first silane chemical composition, the second silane chemical composition, or both may be aromatic chemical compositions. As used herein, an aromatic chemical composition contains one or more six-membered carbon rings, which are characteristic of benzene systems and associated organic moieties. The aromatic silane chemical composition may be an alkoxysilane such as a dialkoxysilane chemical composition, its hydrolysate or oligomer, or a trialkoxysilane chemical composition, its hydrolysate or oligomer. In some embodiments, the aromatic silane may contain an amine moiety and may be an alkoxysilane containing an amine moiety. In other embodiments, the aromatic silane chemical composition may be an aromatic alkoxysilane chemical composition, an aromatic acyloxysilane chemical composition, an aromatic halogen silane chemical composition, or an aromatic aminosilane chemical composition. In other embodiments, the aromatic silane chemical composition may be selected from the group consisting of aminophenyl, 3-(m-aminophenoxy)propyl, N-phenylaminopropyl, or (chloromethyl)phenyl-substituted alkoxy, acyloxy, halogen, or aminosilane. For example, aromatic alkoxysilanes are not particularly limited, but may include aminophenyltrimethoxysilane (sometimes referred to herein as "APhTMS"), aminophenyldimethoxysilane, aminophenyltriethoxysilane, aminophenyldiethoxysilane, 3-(m-aminophenoxy)propyltrimethoxysilane, 3-(m-aminophenoxy)propyldimethoxysilane, 3-(m-aminophenoxy)propyltriethoxysilane, 3-(m-aminophenoxy)propyldiethoxysilane, N-phenylaminopropyltrimethoxysilane, N-phenylaminopropyldimethoxysilane, N-phenylaminopropyltriethoxysilane, N-phenylaminopropyldiethoxysilane, their hydrolysates, or oligomerized chemical compositions thereof. In exemplary embodiments, the aromatic silane chemical composition may be aminophenyltrimethoxysilane.

[0164] Referring again to the embodiments described above, the first silane chemical composition, the second silane chemical composition, or both may be aliphatic chemical compositions. As used herein, aliphatic chemical compositions are non-aromatic, such as alkanes, alkenes, and alkynes, which have an open-chain structure. For example, in some embodiments, the coupling agent may include a chemical composition such as an alkoxysilane, and may be an aliphatic alkoxysilane such as a dialkoxysilane chemical composition, its hydrolysate or oligomer, or a trialkoxysilane chemical composition such as its hydrolysate or oligomer. In some embodiments, the aliphatic silane may include an amine moiety and may be an alkoxysilane containing an amine moiety, such as an aminoalkyltrialkoxysilane. In one embodiment, the aliphatic silane chemical composition may be selected from the group consisting of 3-aminopropyl, N-(2-aminoethyl)-3-aminopropyl, vinyl, methyl, N-phenylaminopropyl, (N-phenylamino)methyl, N-(2-vinylbenzylaminoethyl)-3-aminopropyl substituted alkoxy, acyloxy, halogen, or aminosilane, its hydrolysate or oligomer. Examples of aminoalkyltrialkoxysilanes, but not limited to these, include 3-aminopropyltrimethoxysilane (sometimes referred to herein as "GAPS"), 3-aminopropyldimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyldiethoxysilane, their hydrolysates, and their oligomerized chemical compositions. In other embodiments, the aliphatic alkoxysilane chemical composition may include an amine moiety such as alkyltrialkoxysilane or alkylbialkoxysilane.Examples of such alkyltrialkoxysilanes or alkylbialkoxysilanes include, but are not limited to, vinyltrimethoxysilane, vinyldimethoxysilane, vinyltriethoxysilane, vinyldiethoxysilane, methyltrimethoxysilane, methyldimethoxysilane, methyltriethoxysilane, methyldiethoxysilane, their hydrolysates, or, but are not limited to, oligomerized chemical compositions containing amino-functionalized silsesquioxane oligomers such as Gelest WSA-7011, WSA-9911, WSA-7021, and WSAV-6511. In exemplary embodiments, the aliphatic silane chemical composition is 3-aminopropyltrimethoxysilane.

[0165] In other embodiments, the coupling agent layer 180 may include, but is not limited to, chemical species that are hydrolyzed analogs of aminoalkoxysilanes, such as (3-aminopropyl)silanetriol, N-(2-aminoethyl)-3-aminopropyl-silanetriol, and / or mixtures thereof.

[0166] In other embodiments, the coupling agent layer 180 may contain a chemical species that is an aminoalkylsilsesquioxane. In one embodiment, the coupling agent layer 180 contains an aminopropylsilsesquioxane (APS) oligomer (commercially available as an aqueous solution from Gelest).

[0167] In other embodiments, the coupling agent layer 180 may be an inorganic material such as a metal and / or ceramic film. Non-limiting examples of suitable inorganic materials used as the coupling agent layer 180 include tin, titanium and / or its oxides.

[0168] It has been found that the thermal stability of the smooth coating 160 can be improved by forming a coupling agent from a combination of different chemical compositions, particularly a combination of silane chemical compositions. For example, it has been found that a combination of aromatic silanes and aliphatic silanes, such as those described above, improves the thermal stability of the smooth coating, resulting in a coating whose mechanical properties, such as friction coefficient and adhesion performance, are maintained even after heat treatment at high temperatures. Therefore, in one embodiment, the coupling agent includes a combination of aromatic and aliphatic silanes. In these embodiments, the ratio of aliphatic silane to aromatic silane (aliphatic:aromatic) may be about 1:3 to about 1:0.2. When the coupling agent includes at least two or more chemical compositions, such as aliphatic silanes and aromatic silanes, the weight ratio of these two chemical compositions may be any ratio, such as a weight ratio of about 0.1:1 to about 10:1 for the first silane chemical composition to the second silane chemical composition (first silane:second silane). For example, in some embodiments, the ratio can be 0.5:1 to about 2:1, such as 2:1, 1:1, or 0.5:1. In some embodiments, the coupling agent may comprise a combination of multiple aliphatic silanes and / or multiple aromatic silanes, which can be applied to a glass container in one or more steps, with or without organic or inorganic fillers. In some embodiments, the coupling agent comprises an oligomer such as silsesquioxane formed from both aliphatic and aromatic silanes.

[0169] In exemplary embodiments, the first silane chemical composition is an aromatic silane chemical composition, and the second silane chemical composition is an aliphatic silane chemical composition. In one exemplary embodiment, the first silane chemical composition is an aromatic alkoxysilane chemical composition comprising at least one amine moiety, and the second silane chemical composition is an aliphatic alkoxysilane chemical composition comprising at least one amine moiety. In other exemplary embodiments, the coupling agent comprises an oligomer of one or more silane chemical compositions, the oligomer being a silsesquioxane chemical composition, and at least one of the silane chemical compositions comprising at least one aromatic moiety and at least one amine moiety. In one specific exemplary embodiment, the first silane chemical composition is aminophenyltrimethoxysilane, and the second silane chemical composition is 3-aminopropyltrimethoxysilane. The ratio of aromatic silane to aliphatic silane may be about 1:1. In other specific exemplary embodiments, the coupling agent comprises an oligomer formed from aminophenyltrimethoxy and 3-aminopropyltrimethoxy. In other embodiments, the coupling agent may include both a mixture of aminophenyltrimethoxy and 3-aminopropyltrimethoxy, and an oligomer formed from these two.

[0170] In one embodiment, the coupling agent is applied to the outer surface 106 of the glass body 102 by bringing the surface into contact with the coupling agent diluted by an immersion process. The coupling agent may also be mixed in a solvent when applied to the glass body 102. In another embodiment, the coupling agent may be applied to the glass body 102 by spraying or other suitable means. The glass body 102 to which the coupling agent has been applied may then be dried at about 120°C for about 15 minutes, or at any time and temperature sufficient to adequately release water and / or other organic solvents present on the outer surface 106 of the wall portion 110.

[0171] Referring to Figure 12A, in one embodiment, the coupling agent is positioned as a coupling agent layer 180 in a glass container and is applied as a solution containing about 0.5 wt% of a first silane and about 0.5 wt% of a second silane (totaling 1 wt% silane) mixed with at least one of an organic solvent such as methanol and water, but not limited to these. However, it should be understood that the total silane concentration in the solution may be greater than or less than about 1 wt%, such as about 0.1 wt% to about 10 wt%, about 0.3 wt% to about 5.0 wt%, or about 0.5 wt% to about 2.0 wt%. For example, in one embodiment, the weight ratio of organic solvent to water (organic solvent:water) may be about 90:10 to about 10:90, and in one embodiment, it may be about 75:25. The weight ratio of silane to solvent may affect the thickness of the coupling agent layer, where a larger proportion of the silane chemical composition in the coupling agent solution may result in a thicker coupling agent layer 180. However, it should be understood that other variable factors, such as details of the dip coating process, including the withdrawal speed from the bath, may affect the thickness of the coupling agent layer 180. For example, a faster withdrawal speed may result in a thicker coupling agent layer 180.

[0172] In one embodiment, the coupling agent layer 180 is applied as a solution containing a first silane species and a second silane species that can improve the thermal stability and / or mechanical properties of the smooth coating 160. For example, the first silane species may be an aliphatic silane such as GAPS, and the second silane species may be an aromatic silane such as APhTMS. In this example, the aliphatic silane to aromatic silane ratio (aliphatic:aromatic) may be about 1:1. However, as mentioned above, it should be understood that other ratios, including about 1:3 to about 1:0.2, are also possible. The aromatic silane species and aliphatic silane species may be mixed with at least one of an organic solvent such as methanol and water, but are not limited to these. This solution is then coated onto the outer surface 106 of the glass body 102 and cured to form the coupling agent layer 180.

[0173] In other embodiments, the coupling agent layer 180 is applied as a solution containing 0.1 vol% of a commercially available aminopropylsilsesquioxane oligomer. However, other concentrations of the coupling agent layer solution containing 0.01 to 10.0 vol% of the aminopropylsilsesquioxane oligomer solution may be used.

[0174] In some embodiments, the coupling agent layer 180 is thermally stable enough so that it can function as a smooth coating 160 on its own without any additional coatings such as a chemical composition layer 170. Therefore, in these embodiments, it should be understood that the smooth coating 160 specifically comprises a single composition such as a coupling agent.

[0175] As described herein, if the smooth coating 160 is a robust organic coating, the coating may also include a polymer chemical composition as a polymer chemical composition layer 170. The polymer chemical composition may include, and may not include, organic or inorganic fillers, but may be a mixture of thermally stable polymers such as polyimides, polybenzimidazoles, polysulfones, polyetheretherketones, polyetherimides, polyamides, polyphenyls, polybenzothiazoles, polybenzoxazoles, polybisthiazoles, and polyaromatic heterocyclic polymers. The polymer chemical composition may be formed from other thermally stable polymers, such as polymers that do not degrade at temperatures in the range of 200°C to 400°C, including 250°C, 300°C, and 350°C. These polymers may be applied with or without coupling agents.

[0176] In one embodiment, the polymer chemical composition is a polyimide chemical composition. When the smooth coating 160 contains polyimide, the polyimide composition may be derived from a polyamic acid formed in solution by polymerization of monomers. One such polyamic acid is Novastrat® 800 (commercially available from NeXolve). The polyamic acid is imidized in the curing step to form a polyimide. The polyamic acid can be formed from the reaction of a diamine monomer, such as a diamine, with an anhydride monomer, such as a dianhydride. As used herein, polyimide monomers are described as diamine monomers and dianhydride monomers. However, although a diamine monomer contains two amine moieties, it should be understood that in the following description, any monomer containing at least two amine moieties may be suitable as a diamine monomer, and should consist of a silane chemical composition. Similarly, although a dianhydride monomer contains two anhydride moieties, it should be understood that in the following description, any monomer containing at least two anhydride moieties may be suitable as a dianhydride monomer. The reaction between the anhydride moiety of the anhydride monomer and the amine moiety of the diamine monomer forms the polyamic acid. Therefore, as used herein, a polyimide chemical composition formed from the polymerization of specific monomers refers to a polyimide formed after the imidation of a polyamic acid formed from these specific monomers. Generally, the molar ratio of the total anhydride monomers to the diamine monomers may be approximately 1:1. A polyimide can be formed from only two different chemical compositions (one anhydride monomer and one diamine monomer), but at least one anhydride monomer may be polymerized, and at least one diamine monomer may be polymerized from polyimide. For example, one anhydride monomer may be polymerized with two different diamine monomers. Any number of monomer species combinations can be used.Furthermore, the ratio of one anhydride monomer to a different anhydride monomer, or the ratio of one or more diamine monomers to a different diamine monomer, can be any of the following ratios, such as approximately 1:0.1 to 0.1:1, including approximately 1:9, 1:4, 3:7, 2:3, 1:1, 3:2, 7:3, 4:1, or 9:1.

[0177] The anhydride monomer with which a polyimide is formed together with the diamine monomer may include any of the anhydride monomers. In one embodiment, the anhydride monomer includes a benzophenone structure. In an exemplary embodiment, benzophenone-3,3',4,4'-tetracarboxylic dianhydride may be at least one of the anhydride monomers with which a polyimide is formed. In other embodiments, the diamine monomer may have an anthracene structure, a phenanthrene structure, a pyrene structure, or a pentacene structure, including substituted versions of the above dianhydride.

[0178] The diamine monomers with which polyimides are formed together with anhydride monomers may include any of the diamine monomers. In one embodiment, the diamine monomer includes at least one aromatic ring moiety. Figures 13 and 14 show examples of diamine monomers that can form polyimides containing polymer chemical compositions together with one or more selected anhydride monomers. The diamine monomer may have one or more carbon molecules linking two aromatic ring moieties, as shown in Figure 13, where R in Figure 13 corresponds to an alkyl moiety containing one or more carbon atoms. Alternatively, the diamine monomer may have two directly bonded aromatic ring moieties, as shown in Figure 14, and may not be separated by at least one carbon molecule. The diamine monomer may have one or more alkyl moieties represented by R' and R'' in Figures 13 and 14. For example, in Figures 13 and 14, R' and R'' may represent alkyl moieties bonded to one or more aromatic ring moieties, such as methyl, ethyl, propyl, or butyl moieties. For example, a diamine monomer may have two aromatic ring moieties, each aromatic ring moiety having an alkyl moiety bonded to it, and an adjacent amine moiety bonded to the aromatic ring moiety. It should be understood that R' and R'' in both Figure 13 and Figure 14 may be the same chemical moiety or different chemical moieties. Alternatively, R' and / or R'' in both Figure 13 and Figure 14 may not represent atoms.

[0179] Two different chemical compositions of diamine monomers can be formed from polyimide. In one embodiment, the first diamine monomer comprises two aromatic ring moieties that are directly bonded and not separated by a bonding carbon molecule, and the second diamine monomer comprises two aromatic ring moieties bonded by at least one carbon molecule that connects the two aromatic ring moieties. In one exemplary embodiment, the first diamine monomer, the second diamine monomer, and the anhydride monomer have a molar ratio of about 0.465:0.035:0.5 (first diamine monomer: second diamine monomer: anhydride monomer). However, the ratio of the first diamine monomer to the second diamine monomer can vary in the range of about 0.01:0.49 to about 0.40:0.10, while the anhydride monomer ratio is maintained at about 0.5.

[0180] In one embodiment, the polyimide composition is formed from the polymerization of at least a first diamine monomer, a second diamine monomer, and an anhydride monomer, wherein the first and second diamine monomers are different chemical compositions. In one embodiment, the anhydride monomer is benzophenone, the first diamine monomer contains two directly bonded aromatic rings, and the second diamine monomer contains two aromatic rings bonded by at least one carbon molecule connecting the first and second aromatic rings. The first diamine monomer, the second diamine monomer, and the anhydride monomer may have a molar ratio of about 0.465:0.035:0.5 (first diamine monomer: second diamine monomer: anhydride monomer).

[0181] In exemplary embodiments, the first diamine monomer is orthotolidine, the second diamine monomer is 4,4'-methylene-bis(2-methylaniline), and the anhydride monomer is benzophenone-3,3',4,4'-tetracarboxylic dianhydride. The first diamine monomer, the second diamine monomer, and the anhydride monomer may have a molar ratio of about 0.465:0.035:0.5 (first diamine monomer: second diamine monomer: anhydride monomer).

[0182] In some embodiments, the polyimide is: bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic dianhydride, cyclopentane-1,2,3,4-tetracarboxyl 1,2;3,4-dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic dianhydride, 4arH,8acH)-decahydro-1t,4t:5c,8c-dimethanonaphthalene-2t,3t,6c,7c-tetracarboxyl 2,3:6,7-dianhydride, 2c,3c,6c,7c-tetracarboxyl 2,3:6,7-dianhydride, 5 -Endocarboxymethylbicyclo[2.2.1]-heptane-2-exo,3-exo,5-exo-tricarboxylic acid 2,3:5,5-dianhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic acid anhydride, isomers of bis(aminoethyl)bicyclo[2.2.1]heptane, or 4,4'-methylenebis(2-methylcyclohexylamine), pyromelitic acid dianhydride (PMDA), 3,3',4,4'-biphenyl dianhydride (4,4'-BPDA), 3,3',4,4 '-Benzophenone dianhydride (4,4'-BTDA), 3,3',4,4'-oxydiphthalic acid anhydride (4,4'-ODPA), 1,4-bis(3,4-dicarboxyl-phenoxy)benzene dianhydride (4,4'-HQDPA), 1,3-bis(2,3-dicarboxyl-phenoxy)benzene dianhydride (3,3'-HQDPA), 4,4'-bis(3,4-dicarboxylphenoxyphenyl)-isopropylidene dianhydride (4,4'-BPADA), 4,4'-(2,2,2-trifluoro-1-pentafluorophenylethylidene) ) Diphthalic anhydride (3FDA), 4,4'-oxydianiline (ODA), m-phenylenediamine (MPD), p-phenylenediamine (PPD), m-toluenediamine (TDA), 1,4-bis(4-aminophenoxy)benzene (1,4,4-APB), 3,3'-(m-phenylenebis(oxy))dianiline (APB), 4,4'-diamino-3,3'-dimethyldiphenylmethane (DMMDA), 2,2'-bis(4-(4-aminophenoxy)phenyl)propane (BAPP), 1,4-cyclohexanediamine 2,2'-Bis[4-(4-amino-phenoxy)phenyl]hexafluoroisopropylidene (4-BDAF), 6-amino-1-(4'-aminophenyl)-1,3,3-trimethylindan (DAPI), maleic anhydride (MA), citraconic anhydride (CA), nadoic anhydride (NA), 4-(phenylethynyl)-1,2-benzenedicarboxylic acid anhydride (PEPA), 4,4'-diaminobenzani Lido (DABA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6-FDA), pyromellitic dianhydride, benzophenone-3,3',4,4'-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, 4,4'-o Xydiphthalic anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 4,4'-(4,4'-isopropylidene diphenoxy)bis(phthalic anhydride), 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, and U.S. Patent No. 7,619,042, U.S. Patent No. 8,053,492, U.S. It may be formed from the polymerization of one or more materials described in U.S. Patent No. 4,880,895, U.S. Patent No. 6,232,428, U.S. Patent No. 4,595,548, International Publication No. 2007 / 016516, U.S. Patent Application Publication No. 2008 / 0214777, U.S. Patent No. 6,444,783, U.S. Patent No. 6,277,950, and U.S. Patent No. 4,680,373. Figure 15 shows the chemical structures of some preferred monomers that may be used to form a polyimide coating applied to a glass body 102. In other embodiments, the polyamic acid solution in which the polyimide is formed may include poly(pyromellitic dianhydride-co-4,4'-oxydianiline)amic acid (commercially available from Aldrich).

[0183] In other embodiments, the polymer chemical composition may include a fluorinated polymer. The fluorinated polymer may be a copolymer in which both monomers are highly fluorinated. Some of the monomers of the fluorinated polymer may be fluoroethylenes. In one embodiment, the polymer chemical composition includes, but is not limited to, an amorphous fluorinated polymer such as Teflon AF (commercially available from DuPont). In other embodiments, the polymer chemical composition includes, but is not limited to, perfluoroalkoxy (PFA) resin particles such as Teflon PFA TE-7224 (commercially available from DuPont).

[0184] In other embodiments, the polymer chemical composition may include a silicone resin. The silicone resin has a general formula R n Si(X) m O y The resin may be a highly branched three-dimensional polymer formed by a branched cage-like oligosiloxane having (wherein R is a non-reactive substituent, usually methyl or phenyl, and X is OH or H). While we do not wish to be bound by theory, it is thought that the curing of the resin occurs via a condensation reaction of the Si-OH moiety involving the formation of Si-O-Si bonds. The silicone resin may have at least one of four possible siloxane-functional monomer units, including M-resins, D-resins, T-resins, and Q-resins, where M-resins refer to resins having the general formula R3SiO, D-resins refer to resins having the general formula R2SiO2, T-resins refer to resins having the general formula RSiO3, and Q-resins refer to resins having the general formula SiO4 (fused quartz). In some embodiments, the resin is formed from D and T units (DT resin) or M and Q units (MQ resin). In other embodiments, other combinations (MDT, MTQ, QDT) are also used.

[0185] In one embodiment, the polymer chemical composition includes a phenylmethyl silicone resin for higher thermal stability compared to methyl or phenyl silicone resins. The ratio of phenyl to methyl moieties in the silicone resin can vary in the polymer chemical composition. In one embodiment, the phenyl to methyl ratio is about 1.2. In another embodiment, the phenyl to methyl ratio is about 0.84. In another embodiment, the phenyl to methyl moiety ratio may be about 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.3, 1.4, or 1.5. In one embodiment, the silicone resin is DC255 (commercially available from Dow Corning). In another embodiment, the silicone resin is DC806A (commercially available from Dow Corning). In another embodiment, the polymer chemical composition may include any of the DC series resins (commercially available from Dow Corning) and / or any of the Hardsil Series AP and AR resins (commercially available from Gelest). The silicone resin can be used without a coupling agent or with a coupling agent.

[0186] In other embodiments, the polymer chemical composition may include, but is not limited to, silsesquioxane polymers such as T-214 (commercially available from Honeywell), SST-3M01 (commercially available from Gelest), POSS Imiclear (commercially available from Hybrid Plastics), and FOX-25 (commercially available from Dow Corning). In one embodiment, the polymer chemical composition may include a silanol moiety.

[0187] Referring again to Figures 8 and 12A, the smooth coating 160 may be applied in a multi-stage process, in which the glass body 102 is brought into contact with the coupling agent solution to form a coupling agent layer 180 (as described above), which is then dried and subsequently brought into contact with a polymer chemical composition solution such as a polymer or polymer precursor solution by an immersion process or the like, or the polymer layer 170 may be applied by spraying or other suitable means, dried, and then cured at a high temperature. Alternatively, if the coupling agent layer 180 is not used, the polymer chemical composition of the polymer layer 170 may be applied directly to the outer surface 106 of the glass body 102. In other embodiments, the polymer chemical composition and the coupling agent may be mixed in the smooth coating 160, and the solution containing the polymer chemical composition and the coupling agent may be applied to the glass body 102 in a single coating step.

[0188] In one embodiment, the polymer chemical composition includes a polyimide, where a polyamic acid solution is applied to the coupling agent layer 180. In other embodiments, polyamic acid derivatives such as polyamic acid salts and polyamic acid esters may be used. For example, a preferred polyamic acid salt may include a polyamic acid salt formed from triethylamine. Other preferred salts may include salts formed by deprotonation of the carboxylic acid group of a polyamic acid with a basic additive that results in an ionic interaction between the resulting carboxylate group and its conjugate acid. The basic additive may include organic, inorganic, or organometallic species, or combinations thereof. The inorganic may include parts such as alkalis, alkaline earth elements, or metallic bases. The organic base (proton acceptor) may include aliphatic amines, aromatic amines, or other organic bases. Aliphatic amines include primary amines such as ethylamine, secondary amines such as diethylamine, and tertiary amines such as triethylamine, although these are not particularly limited to these. Examples of aromatic amines include aniline, pyridine, and imidazole. Examples of organometallic bases include magnesium 2,2-dimethylpropyl chloride or others. In one embodiment, the polyamic acid solution may comprise a mixture of 1 vol.% polyamic acid and 99 vol% organic solvent. The organic solvent may comprise a mixture of toluene and at least one of N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), and 1-methyl-2-pyrrolizinone (NMP) solvent or a mixture thereof. In one embodiment, the organic solvent solution comprises about 85 vol% of at least one of DMAc, DMF, and NMP, and about 15 vol% toluene. However, other suitable organic solvents may be used. The coated glass container 100 can then be dried at about 150°C for about 20 minutes, or for any time and temperature sufficient to suitably release the organic solvent present in the smooth coating 160.

[0189] In a laminated pseudo-organic smooth coating embodiment, a coupling agent is brought into contact with the glass body 102 to form a coupling agent layer 180, and a polyamic acid solution is brought into contact with it to form a polymer layer 170. After this, the coated glass container 100 can be cured at a high temperature. The coated glass container 100 may be cured at 300°C for about 30 minutes or less, or it may be cured for a short time at a temperature above 300°C, such as at least 320°C, 340°C, 360°C, 380°C, or 400°C. In the curing step, it is thought that the polyamic acid in the polymer layer 170 is imidized by the reaction of the carboxylic acid moiety and the amide moiety, thereby forming a polymer layer 170 containing polyimide. The curing step may also promote bonding between the polyimide and the coupling agent. The coated glass container 100 is then cooled to room temperature.

[0190] Furthermore, although not limited by the limitations, it is believed that volatile materials such as water and other organic molecules are removed by the curing steps of the coupling agent, polymer chemical composition, or both. Therefore, these volatile materials released during the curing step are not present when the article is used as a container, either when it is heat-treated (e.g., for the removal of exothermic substances) or when it comes into contact with materials such as pharmaceuticals in which it is packaged. It should be understood that the curing processes described herein are separate heat treatments from those described herein, such as heat treatments used to define the thermal stability described herein, or heat treatments similar to or equivalent to those used in the pharmaceutical packaging industry, such as the removal of exothermic substances.

[0191] In one embodiment, the coupling agent includes a silane chemical composition such as an alkoxysilane that can improve the adhesion of the polymer chemical composition to the glass body. Although not theoretically constrained, alkoxysilane molecules are thought to be rapidly hydrolyzed in water to form isolated monomers, cyclic oligomers, and large intramolecular rings. In various embodiments, control over which species is dominant can be determined by the silane type, concentration, pH, temperature, storage conditions, and time. For example, at low concentrations in aqueous solution, aminopropyltrialkoxysilane (APS) can be stable and can form trisilanol monomers and ultra-low molecular weight oligomeric rings.

[0192] While not theoretically constrained, it is believed that numerous steps may be involved in the reaction of one or more silane chemical compositions with glass bodies. As shown in Figure 17, in some embodiments, a reactive silanol moiety may be formed after hydrolysis of the silane chemical composition, which can condense with other silanol moieties on the surface of a substrate, such as a glass body. After the first and second hydrolyzable moieties are hydrolyzed, a condensation reaction may be initiated. In some embodiments, the tendency toward self-condensation can be controlled by the use of a fresh solution, an alcoholic solvent, dilution, and careful selection of the pH range. For example, silanetriols are most stable at pH 3-6, but condense rapidly at pH 7-9.3, and silsesquioxane can be produced by partial condensation of silanol monomers. As shown in Figure 17, the formed silanol moieties may form hydrogen bonds with silanol moieties on the substrate, and covalent bonds may be formed with the substrate during the drying or curing step, accompanied by the desorption of water. For example, with a moderate curing cycle (15 minutes at 110°C), the silanol portion may remain in a free form and, together with any of the silane organic functional groups, may bond with the subsequent topcoat, resulting in improved adhesion.

[0193] In some embodiments, one or more silane chemical compositions of the coupling agent may contain an amine moiety. Although not theoretically restricted, it is believed that this amine moiety acts as a basic catalyst in hydrolysis and copolymerization, thereby increasing the adsorption rate of the silane containing the amine moiety onto the glass surface. This can also result in a high pH (9.0-10.0) in aqueous solution, which conditions the glass surface and increases the density of the surface silanol moiety. The strong interaction between water and the protic solvent maintains the solubility and stability of the silane containing an amine partial chemical composition such as APS.

[0194] In exemplary embodiments, the glass body may include ion-exchange glass, and the coupling agent may be silane. In some embodiments, the adhesion of a smooth coating to the ion-exchange glass body may be stronger than the adhesion of a smooth coating to a non-ion-exchange glass body. While not theoretically bound, it is believed that any of the various embodiments of ion-exchange glass may promote bonding and / or adhesion compared to non-ion-exchange glass. Firstly, ion-exchange glass may have high chemical stability / hydrolysis stability, which can affect the stability of the coupling agent and / or its adhesion to the glass surface. Non-ion-exchange glass typically has low hydrolysis stability, and under humid and / or high-temperature conditions, alkali metals may migrate from the glass body to the interface between the glass surface and the coupling agent layer (if present), or even to the coupling agent layer itself, if present. If alkali metals migrate as described above, and there is a change in pH, hydrolysis of the Si-O-Si bond at the glass / coupling agent layer interface, or in the coupling agent layer itself, may weaken the mechanical properties of the coupling agent or its adhesion to the glass. Secondly, when ion-exchange glass is exposed to a strong oxidizing agent bath such as a potassium nitrite bath at a high temperature of 400°C to 450°C and then removed, the organic chemical composition on the glass surface is removed, making it particularly suitable for silane coupling agents without further cleaning. For example, non-ion-exchange glass may require additional surface cleaning treatment, which adds time and expense to the process.

[0195] In one exemplary embodiment, the coupling agent may comprise at least one silane containing an amine moiety, and the polymer chemical composition may comprise a polyimide chemical composition. Referring to Figure 18, although not bound by theory, it is believed that this amine moiety interaction and the interaction of the polyimide with the polyamic acid precursor proceeds in a stepwise process. As shown in Figure 18, the first step is the formation of a polyamic acid salt between the carboxyl moiety and the amine moiety of the polyamic acid. The second step is a thermal conversion from the salt to the amide moiety. The third step is a further conversion of the amide moiety to the imide moiety, involving the cleavage of the polymer amide bond. As a result, as shown in Figure 18, a covalent imide bond is obtained between the shortened polymer chain (polyimide chain) and the amine moiety of the coupling agent. [Examples]

[0196] Various embodiments of glass containers with improved properties will be further described by the following examples. These examples are illustrative and should not be understood as limiting the subject matter of this disclosure. Example 1 Glass vials were formed from Type IB glass having the same composition as Table 2 of Example 2 above, and from the glass composition specified as "Example E" in Table 1 of U.S. Patent Application No. 13 / 660,394, filed on October 25, 2012, titled "Glass Compositions with Improved Chemical and Mechanical Durability," assigned to Corning Incorporated (hereinafter referred to as the "reference glass composition"). The vials were washed with deionized water, dried by nitrogen blasting, and dip-coated with a 0.1% solution of APS (aminopropylsilsesquioxane). The APS coating was dried in a convection oven at 100°C for 15 minutes. Next, the vials were immersed in a 0.1% solution of Novastrat® 800 polyamic acid in a 15 / 85 toluene / DMF (dimethylformamide) solution, or in a 0.1% to 1% solution of poly(pyromellitic dianhydride-co-4,4'-oxydianiline)amic acid (PMDA-ODA (poly(4,4'-oxydiphenylene-pyromellitoimide))) in N-methyl-2-pyrrolidone (NMP). The coated vials were heated to 150°C and held for 20 minutes to vaporize the solvent. The coating was then cured by placing the coated vials in a preheated furnace at 300°C for 30 minutes. After curing, the vials coated with a 0.1% solution of Novastrat® 800 had no visible color. However, vials coated with a solution of poly(pyromellitic dianhydride-co-4,4'oxydianiline) appeared visually yellow due to the thickness of the coating. Both coatings exhibited a low coefficient of friction in the vial superposition contact test. Example 2 The mechanical strength loss due to abrasion was evaluated by comparing glass vials (as-is / uncoated) and vials coated with a smooth coating, both formed from Type IB glass vials made from the same composition as Table 2 of Example 2 above. The coated vials were first prepared by ion exchange strengthening of glass vials made from a reference glass composition. Ion exchange strengthening was performed in a 100% KNO3 bath at 450°C for 8 hours. After that, these vials were washed with deionized water, air-dried with nitrogen, and immersion coated with a 0.1% solution of APS (aminopropylsilsesquioxane) in water. The APS coating was dried in a convection oven at 100°C for 15 minutes. Next, these vials were immersed in a 0.1% solution of Novastrat® 800 polyamic acid in a 15 / 85 toluene / DMF solution. The coated vials were heated to 150°C and held for 20 minutes to evaporate the solvent. Subsequently, the coated vials were placed in a preheated heating furnace and the coating was cured at 300°C for 30 minutes. Then, the coated vials were immersed in 70°C deionized water for 1 hour and heated in air at 320°C for 2 hours to simulate actual processing conditions.

[0197] Unscratched vials formed from Type IB glass, which is made from the same composition as Table 2 of Example 2 above, and unscratched vials formed from ion-exchange strengthened and coated reference glass compositions were tested for fracture in a horizontal compression test (i.e., a plate was placed on top of the vial and another plate was placed on the bottom of the vial, and both plates were pressed together to measure the load at the time of fracture using a load cell). Figure 19 illustrates the fracture probability in response to the load in the horizontal compression test for vials formed from the reference glass composition, vials formed from the coated and scraped reference glass composition, vials formed from Type IB glass, and vials formed from the scraped Type IB glass. The fracture load of the unscratched vials is illustrated in the Weibull plot. Next, the sample vials formed from Type IB glass and the unscratched vials formed from ion-exchange strengthened and coated glass were placed in the vial superposition jig shown in Figure 9, and the coefficient of friction between the vials was measured by rubbing them together. The load applied to the vials during testing was varied between 24N and 44N using a UMT machine. The applied loads and corresponding maximum friction coefficients are reported in the table included in Figure 20. For uncoated vials, the maximum friction coefficient was varied from 0.54 to 0.71 (shown as vial samples "3&4" and "7&8" in Figure 20, respectively), while for coated vials, the maximum friction coefficient was varied from 0.19 to 0.41 (shown as vial samples "15&16" and "12&14" in Figure 20, respectively). Subsequently, the scratched vials were tested in a horizontal compression test to evaluate the loss of mechanical strength compared to the unscratched vials. The fracture load applied to the unscratched vials is illustrated in the Weibull plot in Figure 19.

[0198] As shown in Figure 19, uncoated vials showed a significant decrease in strength after abrasion, while coated vials showed a relatively minor decrease in strength after abrasion. Based on these results, it is considered that the coefficient of friction between vials should be less than 0.7 or 0.5, or even less than 0.45, in order to reduce the loss of strength after vial superposition abrasion. Example 3 In this embodiment, multiple sets of glass tubes were tested using a four-point bend test to evaluate their respective strengths. The first set of tubes, formed from a reference glass composition, was tested using a four-point bend test in its raw state (uncoated and non-ion-exchange strengthened). The second set of tubes, formed from the reference glass composition, was ion-exchange strengthened in a 100% KNO3 bath at 450°C for 8 hours and then tested using a four-point bend test. The third set of tubes, formed from the reference glass composition, was ion-exchange strengthened in a 100% KNO3 bath at 450°C for 8 hours, coated with 0.1% APS / 0.1% Novastrat® 800 as described in Example 2, and then tested using a four-point bend test. The coated tubes were also immersed in 70°C deionized water for 1 hour and heated in air at 320°C for 2 hours to simulate actual processing conditions. These coated tubes were also rubbed under a 30N load in the vial overlay fixture shown in Figure 9 before the bend test. A fourth set of tubes, formed from a reference glass composition, were ion-exchange strengthened in a 100% KNO3 bath at 450°C for 1 hour and then tested in a four-point bend test. These uncoated ion-exchange strengthened tubes were also rubbed under a 30N load in the vial overlay fixture shown in Figure 9 before the bend test. A fifth set of tubes, formed from Type IB glass, were tested in a four-point bend test in their as-is condition (uncoated, non-ion-exchange strengthened). A sixth set of tubes, formed from Type IB glass, were ion-exchange strengthened in a 100% KNO3 bath at 450°C for 1 hour and then tested in a four-point bend test. The test results are illustrated in the Weibull plot shown in Figure 21.

[0199] Referring to Figure 21, the second set of tubes, which were not abraded, formed from a reference glass composition, and strengthened by ion exchange, withstood the highest stress before breaking. The third set of tubes, coated with 0.1% APS / 0.1% Novastrat® 800 before abrasion, showed a slight decrease in strength compared to the uncoated, unabraded equivalent (i.e., the second set of tubes). However, the decrease in strength was relatively minor even after abrasion following coating. Example 4 Two sets of vials were prepared and passed through a pharmaceutical filling line. Pressure-sensitive tape (commercially available from Fujifilm Corporation) was inserted between the vials to measure the contact / impact forces between the vials and between the vials and the instrument. The first set of vials was formed from Type IB glass and was uncoated. The second set of vials was formed from the reference glass composition as described above and coated with a low-friction polyimide coating with a coefficient of friction of approximately 0.25. Analysis of the pressure-sensitive tape after passing the vials through the pharmaceutical filling line demonstrated that the second set of coated vials showed a 2-3 times reduction in stress compared to the first set of uncoated vials. Example 5 Each of the three sets of four vials was prepared. All vials were formed from a reference glass composition. The first set of vials was coated with APS / Novastrat® 800 coating as described in Example 2. The second set of vials was immersion coated with 0.1% DC806A in toluene. The solvent was evaporated at 50°C and the coating was cured at 300°C for 30 minutes. Each set of vials was placed in a tube and heated at 320°C for 2.5 hours under air purging to remove any trace contaminants adsorbed on the vials in the laboratory environment. Then, each set of samples was heated in the tube for a further 30 minutes, and the degassed volatiles were collected in an activated carbon adsorbent trap. The trap was heated to 350°C for 30 minutes to desorb all the collected material, which was then supplied to a gas chromatograph-mass spectrometer. Figure 22 shows gas chromatography-mass spectrometer output data for the APS / Novastrat® 800 coating. Figure 23 shows gas chromatography-mass spectrometer output data for the DC806A coating. No degassing was detected from either the 0.1% APS / 0.1% Novastrat® 800 coating or the DC806A coating.

[0200] A set of four vials was coated with a binding layer using a 0.5% / 0.5% GAPS / APhTMS (3-aminopropyltrimethoxysilane / aminophenyltrimethoxysilane) solution in a methanol / water mixture. The coated surface area of ​​each vial was approximately 18.3 cm². 2The solvent was vaporized from a coated vial at 120°C for 15 minutes. Next, a 0.5% Novastrat® 800 solution in dimethylacetamide was applied to the sample. The solvent was vaporized at 150°C for 20 minutes. These uncured vials were subjected to the degassing test described above. The vials were heated to 320°C in an airflow (100 mL / min), and after reaching 320°C, the released volatiles were collected every 15 minutes using an activated carbon adsorbent trap. Next, the trap was heated to 350°C for 30 minutes or more to desorb the collected material, and this was placed in a gas chromatograph-mass spectrometer. Table 3 shows the amount of substance collected over the time segments in which the sample was held at 320°C. Time zero corresponds to the time when the sample first reached a temperature of 320°C. As shown in Table 3, after heating for 30 minutes, the amount of volatiles was reduced to less than 100 ng, the detection limit of the instrument. Table 3 also reports the loss of volatile matter per square centimeter of the coated surface.

[0201] [Table 3]

[0202] Example 6 Multiple vials were prepared with various silicon resin or polyimide-based coatings, with and without coupling agents. When coupling agents were used, the coupling agents included APS and GAPS, a precursor of APS. The outer coating layer was prepared from silicone resins such as Novastrat® 800, poly(pyromellitic acid dianhydride-co-4,4'-oxydianiline), or DC806A and DC255. The APS / poly(4,4'-oxydiphenylene-pyromellitoimide) coating was prepared using a 0.1% solution of APS (aminopropylsilsesquioxane) and a 0.1%, 0.5%, or 1.0% solution of poly(pyromellitic acid dianhydride-co-4,4'-oxydianiline)amide acid (PMDA-ODA-poly(4,4'-oxydiphenylene-pyromellitoimide)) in N-methyl-2-pyrrolidone (NMP). Poly(4,4'-oxydiphenylene-pyromellitoimide) coatings were also applied without a coupling agent using a 1.0% solution of poly(pyromellitic dianhydride-co-4,4'oxydianiline) in NMP. APS / Novastrat® 800 coatings were prepared using a 0.1% solution of APS and a 0.1% solution of Novastrat® 800 polyamic acid in a 15 / 85 toluene / DMF solution. DC255 coatings were applied directly to glass without a coupling agent using a 1.0% solution of DC255 in toluene. APS / DC806A coatings were prepared by first applying a 0.1% aqueous solution of APS, and then a 0.1% or 0.5% solution of DC806A in toluene. The GAPS / DC806A coating was applied using a 1.0% solution of GAPS in 95 wt% ethanol in water as a coupling agent, followed by a 1.0% solution of DC806A in toluene. The coupling agent and coating were applied using the dip coating method described herein, where the coupling agent was heat-treated after application, and the silicon resin and polyimide coatings were dried and cured after application. The coating thickness was estimated based on the concentration of the solutions used.The table included in Figure 24 lists various coating compositions, estimated coating thicknesses, and test conditions.

[0203] Subsequently, some of the vials were subjected to tumblers to simulate coating damage, while others were subjected to abrasion under 30N and 50N loads in the vial superposition fixture shown in Figure 9. All vials were then filled with 0.5 mL of sodium chloride solution and subjected to freeze-drying (freeze-drying process) at -100°C. Freeze-drying was then carried out for 20 hours at -15°C under reduced pressure. These vials were examined using optical quality assurance equipment and under a microscope. No damage to the coating due to freeze-drying was observed. Example 7 Three sets of six vials were prepared to evaluate the effect of increasing load on the coefficient of friction of uncoated vials and vials coated with Dow Corning DC 255 silicone resin. The first set of vials was formed from Type IB glass and left uncoated. The second set of vials was formed from a reference glass composition, coated with a 1% solution of DC255 in toluene, and cured at 300°C for 30 minutes. The third set of vials was formed from Type IB glass and coated with a 1% solution of DC255 in toluene. Each set of vials was placed in the vial overlay fixture shown in Figure 9, and the coefficient of friction for the similarly coated vials was measured during abrasion under static loads of 10N, 30N, and 50N. The results are reported in Figure 25. As shown in Figure 25, the coated vials exhibited a significantly lower coefficient of friction compared to the uncoated vials when abraded under the same conditions, regardless of the glass composition. Example 8 Three sets of two glass vials were prepared along with an APS / poly(4,4'-oxydiphenylene-pyromellitoimide) coating. First, each vial was dipped in a 0.1% solution of APS (aminopropylsilsesquioxane). The APS coating was dried in a convection oven at 100°C for 15 minutes. Next, the vials were immersed in a 0.1% poly(pyromellitic dianhydride-co-4,4'-oxydianiline)amide acid solution (PMDA-ODA(poly(4,4'-oxydiphenylene-pyromellitoimide))) in N-methyl-2-pyrrolidone (NMP). The coating was then cured by placing the coated vials in a preheated furnace at 300°C for 30 minutes.

[0204] Two vials were placed on the vial overlay fixture shown in Figure 9 and rubbed with a 10 N load. The rubbing method was repeated four more times over the same area, and the coefficient of friction was measured for each rub. The areas between the rubble on these vials were wiped, and the starting point of each rubble was placed in an area that had not yet been rubbed. However, each rubble moved along the same "track". The same method was repeated for loads of 30 N and 50 N. The coefficient of friction of each rubble (i.e., A1 to A5) for each load is illustrated in Figure 26. As shown in Figure 26, the coefficient of friction of the APS / poly(4,4'-oxydiphenylene-pyromellitoimide) coated vials was generally less than 0.30 for all rubble at all loads. This example demonstrates the improved scratch resistance of polyimide coatings when applied to a glass surface treated with a coupling agent. Example 9 Three pairs of two glass vials were prepared with APS coatings. Each vial was immersion coated in a 0.1% solution of APS (aminopropylsilsesquioxane) and heated in a convection oven at 100°C for 15 minutes. The two vials were placed in the vial overlay fixture shown in Figure 9 and rubbed under a 10N load. The rubbing method was repeated four more times on the same area, and the coefficient of friction was measured for each scratch. The areas between the scratches on these vials were wiped, and the starting point of each scratch was placed in an area that had not yet been rubbed. However, each scratch moved along the same "track". The same method was repeated under loads of 30N and 50N. The coefficient of friction of each scratch (i.e., A1-A5) for each load is illustrated in Figure 27. As shown in Figure 27, the coefficient of friction of the vials coated with APS alone was generally higher than 0.3, often reaching 0.6 or higher. Example 10 Three sets of two glass vials were prepared with APS / poly(4,4'-oxydiphenylene-pyromellitoimide) coating. Each vial was dip-coated in a 0.1% solution of APS (aminopropylsilsesquioxane). The APS coating was heated in a convection oven at 100°C for 15 minutes. The vials were then immersed in a 0.1% poly(pyromellitic dianhydride-co-4,4'-oxydianiline)amide acid solution (PMDA-ODA-poly(4,4'-oxydiphenylene-pyromellitoimide)) in N-methyl-2-pyrrolidone (NMP). The coating was then cured by placing the coated vials in a preheated furnace at 300°C for 30 minutes. The coated vials were then subjected to exothermic removal (heating) at 300°C for 12 hours.

[0205] Two vials were placed on the vial overlay fixture shown in Figure 9 and rubbed with a 10N load. The rubbing method was repeated four more times on the same area, and the coefficient of friction was measured for each rub. The areas between the rubble on these vials were wiped, and the starting point of each rub was positioned in the already rubbed area, and each rub was performed on the same "track". The same method was repeated for loads of 30N and 50N. The coefficient of friction for each rubble (i.e., A1 to A5) is illustrated in Figure 28 for each load. As shown in Figure 28, the coefficient of friction of the APS / poly(4,4'-oxydiphenylene-pyromellitoimide) coated vials was generally uniform, approximately 0.20 or less for rubble introduced with loads of 10N and 30N. However, when the load was increased to 50N, the coefficient of friction increased for each consecutive rub, with the fifth rub having a coefficient of friction slightly less than 0.40. Example 11 Three sets of two glass vials were prepared with an APS (aminopropylsilsesquioxane) coating. Each vial was immersed in a 0.1% APS solution and heated in a convection oven at 100°C for 15 minutes. The coated vials were then subjected to exothermic heating at 300°C for 12 hours. The two vials were placed in the vial overlay fixture shown in Figure 9 and rubbed under a 10N load. The rubbing method was repeated four more times on the same area, and the coefficient of friction was measured for each scratch. The areas between the scratches on these vials were wiped, and the starting point of each scratch was placed in the already rubbed area, so that each scratch moved along the same "track". The same method was repeated under loads of 30N and 50N. The coefficient of friction of each scratch (i.e., A1-A5) for each load is shown in Figure 29. As shown in Figure 29, the coefficient of friction of the APS-coated vial after 12 hours of exothermic removal was significantly higher than that of the APS-coated vial shown in Figure 27, and was similar to that of the uncoated glass vial, indicating that the vial may have significantly lost its mechanical strength due to abrasion. Example 12 Three sets of glass vials, each consisting of two vials formed from Type IB glass, were prepared with a poly(4,4'-oxydiphenylene-pyromellitoimide) coating. The vials were immersed in a 0.1% poly(pyromellitic dianhydride-co-4,4'-oxydianiline)amide acid solution (PMDA-ODA-poly(4,4'-oxydiphenylene-pyromellitoimide)) in N-methyl-2-pyrrolidone (NMP). The coating was then dried at 150°C for 20 minutes, and subsequently cured by placing the coated vials in a preheated furnace at 300°C for 30 minutes.

[0206] Two vials were placed on the vial overlay fixture shown in Figure 9 and rubbed with a 10 N load. The rubbing method was repeated four more times over the same area, and the coefficient of friction was measured for each rub. The areas between the rubble on these vials were wiped, and the starting point of each rubble was placed in an area that had not yet been rubbed. However, each rubble moved along the same "track". The same method was repeated for loads of 30 N and 50 N. The coefficient of friction of each rubble (i.e., A1 to A5) for each load is illustrated in Figure 30. As shown in Figure 30, the coefficient of friction of the poly(4,4'-oxydiphenylene-pyromellitoimide) coated vials generally increased after the first rub, demonstrating the inferior abrasion resistance of polyimide coatings applied to glass without a coupling agent. Example 13 The vials coated with APS / Novastrat® 800 in Example 6 were tested for friction coefficient under a 30N load using the vial superposition jig shown in Figure 9 after freeze-drying. No increase in friction coefficient was detected after freeze-drying. Figure 31 includes a table showing the friction coefficient for the APS / Novastrat® 800 coated vials before and after freeze-drying. Example 14 A reference glass composition vial was ion-exchanged and coated as described in Example 2. The coated vial was autoclaved using the following protocol: steam purging at 100°C for 10 minutes, followed by a 20-minute stop (the coated glass container 100 was exposed to a 121°C environment), followed by processing at 121°C for 30 minutes. The coefficient of friction for autoclaved and non-autoclaved vials was measured with a 30N load using the vial superposition jig shown in Figure 9. Figure 32 shows the coefficient of friction for APS / Novastrat® 800 coated vials before and after autoclaving. No increase in the coefficient of friction was detected after autoclaving. Example 15 Three sets of vials were coated with an APS / APhTMS (1:8 ratio) binding layer, and the outer layer consisted of Novastrat® 800 polyimide, which was imidized at 300°C using a solution of polyamic acid in dimethylacetamide. One set underwent exothermic removal at 320°C for 12 hours. The second set underwent exothermic removal at 320°C for 12 hours, followed by autoclaving at 121°C for 1 hour. The third set of vials was left uncoated. Each set of vials was then subjected to a vial superposition test under a 30N load. The coefficient of friction for each set of vials is reported in Figure 33. Photographs of the vial surface showing damage (or absence of damage) are also shown in Figure 33. As shown in Figure 33, the uncoated vials generally had a coefficient of friction greater than approximately 0.7. The uncoated vials also showed visually perceptible damage as a result of the test. However, the coated vials had a coefficient of friction of less than 0.45 without any visually perceptible surface damage.

[0207] The coated vials were also subjected to exothermic material removal, autoclaving, or both conditions as described above. Figure 34 illustrates the probability of failure in the horizontal compression test of the vials as the load increased. No statistically significant difference was observed between the exothermic material removal vials and the exothermic material removal and autoclaving vials. Example 16 Vials formed from Type IB ion-exchange glass were prepared with smooth coatings having various silane ratios. Referring to Figure 35, vials were prepared with three different coating compositions, and the curing of the applied coatings with different silane ratios relative to the coefficient of friction was evaluated. The first coating composition consisted of a coupling agent layer with a 1:1 GAPS to aminophenyltrimethyloxysilane (APhTMS) ratio and an outer coating layer consisting of 1.0% Novastrat® 800 polyimide. The second coating composition consisted of a coupling agent layer with a 1:0.5 GAPS to APhTMS ratio and an outer coating layer consisting of 1.0% Novastrat® 800 polyimide. The third coating composition consisted of a coupling agent layer with a 1:0.2 GAPS to APhTMS ratio and an outer coating layer consisting of 1.0% Novastrat® 800 polyimide. All vials were subjected to exothermic removal at 320°C for 12 hours. Subsequently, the vials were subjected to vial superposition friction tests under loads of 20 N and 30 N. The average applied vertical force, coefficient of friction, and maximum frictional force (Fx) for each vial are reported in Figure 35. As shown in Figure 35, as the amount of aromatic silane (i.e., aminophenyltrimethyloxysilane) decreases, the coefficient of friction between the vials and the frictional force experienced by the vials increase. Example 17 Vials formed from Type IB ion exchange glass were prepared with smooth coatings having various silane ratios.

[0208] Samples were prepared with a coupling agent layer formed from 0.125% APS and 1.0% aminophenyltrimethoxysilane (APhTMS) (having an APS / APhTMS ratio of 1:8), and an outer coating layer formed from 0.1% Novastrat® 800 polyimide. The thermal stability of the applied coating was evaluated by measuring the coefficient of friction and the friction-induced force associated with the vial before and after performing exotherm removal. Specifically, the coated vials were subjected to a vial stack friction test under a load of 30 N. The coefficient of friction and the friction-induced force were measured and are plotted against time in FIG. 36. A second set of vials was subjected to exotherm removal at 320° C for 12 hours and then to the same vial stack friction test under a load of 30 N. The coefficient of friction remained the same both before and after exotherm removal, indicating that the coating was thermally stable and that it protected the glass surface from friction-induced damage. Photographs of the glass contact areas are also shown.

[0209] Samples were prepared with a coupling agent layer formed from 0.0625% APS and 0.5% APhTMS (having an APS / APhTMS ratio of 1:8), and an outer coating layer formed from 0.05% Novastrat® 800 polyimide. The thermal stability of the applied coating was evaluated by measuring the coefficient of friction and the friction-induced force associated with the vial before and after performing exotherm removal. Specifically, the coated vials were subjected to a vial stack friction test under a load of 30 N. The coefficient of friction and the friction-induced force were measured and are plotted against time / distance in FIG. 37. A second set of vials was subjected to exotherm removal at 320° C for 12 hours and then to the same vial stack friction test under a load of 30 N. The coefficient of friction remained the same both before and after exotherm removal, indicating that the coating was thermally stable. Photographs of the glass contact areas are also shown.

[0210] Figure 38 illustrates the probability of failure in horizontal compression tests with respect to applied load for vials with a smooth coating formed from 0.125% APS and 1.0% APhTMS, a vial with an outer coating layer formed from 0.1% Novastrat® 800 polyimide (indicated as "260" in Figure 38), a vial with a smooth coating formed from 0.0625% APS and 0.5% APhTMS, and a vial with an outer coating layer of 0.05% Novastrat® 800 polyimide (indicated as "280" in Figure 38). The data shows that the failure load did not change from uncoated and unscratched samples to coated, exothermic material removed, and scratched samples, demonstrating the protection of the glass from damage by the coating.

[0211] Vials were prepared with a smooth coating using GAPS hydrolysate. Samples were prepared with a composition including a coupling agent layer formed from 0.5% Dynasylan® Hydrosil 1151 (3-aminopropylsilane hydrolysate) and 0.5% aminophenyltrimethyloxysilane (APhTMS) (in a 1:1 ratio), and an outer coating layer formed from 0.05% Novastrat® 800 polyimide. Coating performance was evaluated by measuring the coefficient of friction and frictional force on the vial before and after exothermic substance removal. Specifically, Type IB vials strengthened by ion exchange (100% KNO3, 450°C for 8 hours) were subjected to a vial superposition friction test under a load of 30N. The coefficient of friction and frictional force were measured and plotted against time / distance in Figure 39. A second set of vials was subjected to exothermic substance removal at 320°C for 12 hours and subjected to the same vial superposition friction test under a load of 30N. The coefficient of friction remained the same both before and after the removal of the exothermic substance, indicating that the coating was thermally stable. Photographs of the glass contact area are also shown. This suggests that the hydrolysate of aminosilane is also useful in the coating formulation.

[0212] The thermal stability of the applied coating was also evaluated for a series of exotherm removal conditions. Specifically, Type IB ion exchange glass vials were prepared with a coupling agent layer having a 1:1 GAPS (0.5%) to aminophenyltrimethoxysilane (APhTMS) (0.5%) ratio, and an outer coating layer consisting of 0.5% Novastrat® 800 polyimide. The vials were dip-coated in solution using an automatic dip coater at a withdrawal rate of 2 mm / s. The sample vials were subjected to one of the following exotherm removal cycles: 12 hours at 320 °C; 24 hours at 320 °C; 12 hours at 360 °C; or 24 hours at 360 °C. The coefficient of friction and the force due to friction were then measured using the vial stack friction test and plotted against time for each exotherm removal condition as shown in Figure 40. As shown in Figure 40, the coefficient of friction of the vials did not change depending on the exotherm removal conditions, indicating that the coating was thermally stable. Figure 41 illustrates the coefficient of friction after various heat treatment cycles at 360 °C and 320 °C. Example 18 The vials were coated with the APS / Novastrat 800 coating as described in Example 2. The light transmittance of the coated vials, as well as that of the uncoated vials, was measured using a spectrophotometer within the wavelength range of 400 - 700 nm. The measurement was performed by directing the light beam perpendicular to the walls of the container such that the light beam passed through the smooth coating twice, once upon entry into the container and then once upon exit. Figure 11 illustrates the light transmittance data measured in the visible light spectrum of 400 - 700 nm for the coated and uncoated vials. Line 440 represents the uncoated glass container, and line 442 represents the coated glass container. Example 19 Vials were coated with a 0.25% GAPS / 0.25% APhTMS coupling agent and 1.0% Novastrat® 800 polyimide, and their light transmittance was tested before and after 12 hours of exothermic removal at 320°C. Uncoated vials were also tested. The results are shown in Figure 42. Example 20 To improve the uniformity of the polyimide coating, 4 g of triethylamine was added to 1 L of methanol, and then Novastrat® 800 polyamic acid was added to form a 0.1% solution, thereby converting Novastrat® 800 polyamic acid to a polyamic acid salt, which was then dissolved in methanol, a solvent that evaporates significantly faster than dimethylacetamide. A methanol-soluble salt of poly(pyromellitic dianhydride-co-4,4'-oxydianiline)amic acid was produced.

[0213] Coatings were formed on Type IB ion exchange vials using 1.0% GAPS / 1.0% APhTMS in a methanol / water mixture and 0.1% Novastrat® 800 polyamate in methanol. The coated vials were subjected to exothermic removal at 360°C for 12 hours. Samples that had not been subjected to exothermic removal and those that had been subjected to exothermic removal were rubbed with vertical loads of 10N, 20N, and 30N in a vial overlay fixture. No glass damage was observed with vertical forces of 10N, 20N, and 30N. Figure 43 shows the coefficient of friction, applied force, and force due to friction on the samples after heat treatment at 360°C for 12 hours. Figure 44 illustrates the probability of failure depending on the applied load in a horizontal compression test on the samples. Statistically, the series of samples at 10N, 20N, and 30N were distinguishable from each other. Low-load fracture samples broke from a cusp away from the scratch.

[0214] As shown in Figures 45-47, the thickness of the coating layer was estimated using polarization analysis and scanning electron microscopy (SEM). Samples for coating thickness measurement were prepared using silicon wafers (polarization analysis) and glass slides (SEM). This method yielded various thicknesses, ranging from 55 to 180 nm for the bonding layer and 35 nm for the Novastrat® 800 polyamate. Example 21 Plasma-cleaned Si wafer pieces were dip-coated with a 0.5% GAPS / 0.5% APhTMS solution in a 75 / 25 methanol / water vol / vol mixture. The coatings were exposed to 120°C for 15 minutes. The coating thickness was measured using polarization analysis. Three samples were prepared, with thicknesses of 92.1 nm, 151.7 nm, and 110.2 nm, respectively, and a standard deviation of 30.6 nm.

[0215] Glass slides were dip-coated and tested with a scanning electron microscope. Figure 45 shows an SEM image of a glass slide dip-coated at a pulling speed of 8 mm / s in a coating solution of 1.0% GAPS, 1.0% APhTMS, and 0.3% NMP in a 75 / 25 methanol / water mixture, followed by curing at 150°C for 15 minutes. The coating appears to be approximately 93 nm thick. Figure 46 shows an SEM image of a glass slide dip-coated at a pulling speed of 4 mm / s in a coating solution of 1.0% GAPS, 1.0% APhTMS, and 0.3 NMP in a 75 / 25 methanol / water mixture, followed by curing at 150°C for 15 minutes. The coating appears to be approximately 55 nm thick. Figure 47 shows an SEM image of a glass slide that was dip-coated in a 0.5% Novastrat® 800 coating solution at a pulling speed of 2 mm / s, cured at 150°C for 15 minutes, and heat-treated at 320°C for 30 minutes. The coating appears to be approximately 35 nm thick. Comparative example A Glass vials formed from Type IB glass were coated with a diluted Bayer Silicone aqueous emulsion of Baysilone M with a solid content of approximately 1-2%. These vials were treated at 150°C for 2 hours to remove water from the surface, leaving a polydimethylsiloxane coating on the outer surface of the glass. The nominal thickness of the coating was approximately 200 nm. The first set of vials was left untreated (i.e., "plain coated vials"). The second set of vials was treated at 280°C for 30 minutes (i.e., "treated vials"). Several vials from each set were first mechanically tested by applying scratches approximately 20 mm long with loads increasing linearly from 0 to 48 N using a UMT-2 friction meter and vial superposition test fixture. The scratches were evaluated for friction coefficient and morphology to determine whether the scratching method damaged the glass or whether the coating protected the glass from scratch damage.

[0216] Figure 48 is a plot showing the coefficient of friction, scratch penetration, applied normal force, and friction force (y-coordinate) for a plain coated vial, depending on the length of the applied scratch (x-coordinate). As illustrated in Figure 48, the plain coated vial exhibited a coefficient of friction of approximately 0.03 at loads below approximately 30 N. The data shows that below approximately 30 N, the COF is always less than 0.1. However, at normal forces exceeding 30 N, the coating begins to break, as indicated by the presence of glass cracks along the length of the scratch. Glass cracks indicate glass surface damage, and as a result of this damage, the glass tends to break more easily.

[0217] Figure 49 is a plot showing the coefficient of friction, scratch penetration, applied normal force, and frictional force (y-coordinate) for a treated vial, depending on the length of the applied scratch (x-coordinate). For the treated vial, the coefficient of friction remained low until the load reached approximately 5 N. At this point, the coating began to break, and the glass surface was severely damaged, as evidenced by the large amount of glass cracking that occurred with increasing load. The coefficient of friction of the treated vial increased to approximately 0.5. However, after thermal exposure, the coating was unable to protect the glass surface under a load of 30 N, indicating that the coating was thermally unstable.

[0218] Next, the vials were tested by applying a static load of 30 N across the entire length of a 20 mm scratch. Ten samples of uncoated vials and ten samples of treated vials were tested under horizontal compression by applying a static load of 30 N across the entire length of a 20 mm scratch. None of the uncoated samples were damaged by the scratch, while six of the ten treated vials were damaged by the scratch, indicating a decrease in residual strength in the treated vials. Comparative example B A 2% solution of Wacker Silres MP50 (product number 60078465, lot number EB21192) was applied to vials formed from a reference glass composition. These vials were first cleaned by applying plasma for 10 seconds before coating. The vials were dried at 315°C for 15 minutes to remove water from the coating. The first set of vials was maintained in a "plain coating" state. The second set of vials was heated at a temperature in the range of 250°C to 320°C for 30 minutes (i.e., "treated vials"). Several vials from each set were first mechanically tested by applying scratches approximately 20 mm long with loads increasing linearly from 0 to 48 N using a UMT-2 friction meter. The scratches were evaluated for friction coefficient and morphology to determine whether the scratching method damaged the glass or whether the coating protected the glass from scratch damage.

[0219] Figure 50 is a plot showing the coefficient of friction, degree of scratch penetration, applied normal force, and frictional force (y-coordinate) for a plain coated vial, depending on the length of the applied scratch (x-coordinate).

[0220] Figure 51 is a plot showing the coefficient of friction, scratch penetration, applied normal force, and frictional force (y-coordinate) as a function of the length of the applied scratch (x-coordinate) for a treated vial treated at 280°C. The treated vial showed significant glass surface damage at loads exceeding approximately 20 N. The load threshold for glass damage decreased with increasing thermal exposure temperature, indicating that the coating deteriorated at high temperatures (i.e., the coating was thermally unstable). Samples treated at temperatures below 280°C showed glass damage at loads exceeding 30 N. Comparative example C Vials formed from a reference glass composition were treated with Evonik Silikophen P 40 / W diluted to 2% solids in water. The samples were then dried at 150°C for 15 minutes and cured at 315°C for 15 minutes. The first set of vials was maintained in a "primary coating" state. The second set of vials was treated at 260°C for 30 minutes (i.e., "260°C treated vials"). The third set of vials was treated at 280°C for 30 minutes (i.e., "280°C treated vials"). These vials were scratched with a static load of 30 N using the test fixture shown in Figure 9. These vials were then tested under horizontal compression. The 260°C treated and 280°C treated vials were damaged under compression, while two of the sixteen primary coated vials were damaged by scratching. This indicates that the coating degraded upon exposure to high temperatures, and as a result, the coating did not adequately protect the surface from a 30N load. Example 22 Vials formed from a reference glass composition were coated with a 75 / 25 methanol / water solution of 1.0% / 1.0% GAPS / m-APhTMS solution. The vials were dip-coated in the solution at a pulling speed of 2 mm / s. The coating was cured at 150°C for 15 minutes. The first set of vials was kept in an untreated state (i.e., "uncoated vials"). The second set of vials was subjected to exothermic removal at 300°C for 12 hours (i.e., "treated vials"). Several vials from each set were mechanically tested by applying a 10N load scratch from the shoulder to the heel of the vial using a UMT-2 friction meter and vial overlay test fixture. Additional vials from each set were mechanically tested by applying a 30N load scratch from the shoulder to the heel of the vial using a UMT-2 friction meter and vial overlay test fixture. The scratches were evaluated in terms of friction coefficient and morphology to determine whether the scratching method damaged the glass or whether the coating protected the glass from damage caused by the scratches.

[0221] Figures 52 and 53 are plots showing the coefficient of friction, scratch penetration, applied perpendicular force, and frictional force (y-coordinate) for a plain coated vial, depending on the length of the applied scratch (x-coordinate). As illustrated in Figures 52 and 53, the plain coated vial showed some scratches and glass damage after the test. However, the coefficient of friction was approximately 0.4–0.5 during the test. Figures 54 and 55 show the results of a similar test performed on a treated vial. After the test, the treated vial showed some abrasion on the coating surface, as well as some damage to the glass. The coefficient of friction was approximately 0.7–0.8 during the test. Example 23 Vials formed from a reference glass composition were coated with a 75 / 25 methanol / water solution of 1.0% / 1.0% GAPS / m-APhTMS solution. The vials were dip-coated in the solution by pulling them up at a pulling speed ranging from 0.5 mm / s to 4 mm / s, varying the coating thickness on each vial. The coatings were cured at 150°C for 15 minutes. The first set of vials was kept in an untreated state (i.e., "uncoated vials"). The second set of vials was subjected to exothermic removal at 300°C for 12 hours (i.e., "treated vials"). Several vials from each set were mechanically tested by applying a 10N load scratch from the shoulder to the heel of the vial using a UMT-2 friction meter. Additional vials from each set were mechanically tested by applying a 30N load scratch from the shoulder to the heel of the vial using a UMT-2 friction meter. Next, the vials were tested under horizontal compression. The results of the horizontal compression tests are reported in Figures 56 and 57. The vials scratched under a 10N load showed relatively small differences in mechanical strength despite varying coating thicknesses. Vials scratched at 30N and with thinner coatings (i.e., coatings corresponding to a pulling speed of 0.5 mm / s) were more prone to failure under horizontal compression compared to vials with relatively thicker coatings.

[0222] It should be understood that the glass containers described herein have at least two performance characteristics selected from resistance to delamination, improved strength, and high damage resistance. For example, the glass containers may have resistance to delamination and improved strength; improved strength and high damage resistance; or a combination of resistance to delamination and high damage resistance. These glass containers can be understood in various embodiments.

[0223] In a first aspect, the glass container may include a body having an inner surface, an outer surface, and a wall portion extending between the outer surface and the inner surface. The compressive stress layer may extend from the outer surface of the body into the wall portion. The compressive stress layer may have a surface compressive stress of 150 MPa or more. The smooth coating may be located around at least a portion of the outer surface of the body. The outer surface of the body with the smooth coating may have a coefficient of friction of 0.7 or less.

[0224] In a second aspect, the glass container may include a body having an inner surface, an outer surface, and a wall portion extending between the outer surface and the inner surface. The body may be formed from Type 1, Class B glass compliant with ASTM standard E438 - 92. The compressive stress layer may extend from the outer surface of the body into the wall portion. The compressive stress layer may have a surface compressive stress of 150 MPa or more. The smooth coating may be located around at least a portion of the outer surface of the body. The outer surface of the body with the smooth coating may have a coefficient of friction of 0.7 or less.

[0225] A third aspect includes the glass containers of the first to second aspects where the surface compressive stress is 200 MPa or more.

[0226] A fourth aspect includes the glass containers of any one of the first to third aspects where the surface compressive stress is 300 MPa or more.

[0227] A fifth aspect includes the glass containers of any one of the first to fourth aspects where the compressive stress layer extends to a layer depth of 3 μm or more.

[0228] A sixth aspect includes the glass containers of any one of the first to fifth aspects where the compressive stress layer extends to a layer depth of 25 μm or more.

[0229] A seventh aspect includes the glass containers of any one of the first to sixth aspects where the body is ion - exchange strengthened.

[0230] The eighth embodiment includes a glass container of any of the first to seventh embodiments, which is enhanced with high-temperature ion exchange.

[0231] The ninth embodiment includes a glass container of any of the first to sixth embodiments, wherein the body is heat-strengthened.

[0232] The tenth embodiment includes a glass container of the ninth embodiment, wherein the compressive stress layer extends into the thickened portion to a layer depth of approximately 22% or less of the thickened portion.

[0233] The eleventh embodiment includes a glass container of any of the first to sixth embodiments, wherein the main body comprises laminated glass.

[0234] The twelfth aspect is that the laminated glass has a core thermal expansion coefficient CTE core A core layer having; and a second thermal expansion coefficient CTE that is fused with the core layer clad It comprises at least one cladding layer having CTE, where CTE core is CTE clad This includes a glass container of an eleventh form, which is different from the previous one.

[0235] A thirteenth aspect is a cladding layer comprising at least one cladding layer comprising a first cladding layer and a second cladding layer; the first cladding layer being fused to a first surface of the core layer, and the second cladding layer being fused to a second surface of the core layer; and CTE core is CTE clad This includes a glass container of a twelfth form that is larger than the one described above.

[0236] The 14th embodiment includes a glass container of any of the 12th to 13th embodiments, wherein the compressive stress layer extends to a layer depth of approximately 1 μm to approximately 90% of the thickness of the wall portion.

[0237] The 15th embodiment includes a glass container of any of the 12th to 13th embodiments, wherein the compressive stress layer extends to a layer depth of approximately 1 μm to approximately 33% of the thickness of the glass container.

[0238] The sixteenth embodiment includes a glass container of any of the twelveth to fifteenth embodiments, wherein at least one cladding layer forms the inner surface of the body.

[0239] The 17th embodiment includes a glass container of any of the first to 16 embodiments, further comprising an inorganic coating located on at least a portion of the outer surface of the glass body, wherein the inorganic coating has a coefficient of thermal expansion smaller than that of the glass body.

[0240] The 18th embodiment includes a glass container of any of the first to 17 embodiments, wherein the smooth coating is thermally stable for 30 minutes at a temperature of at least about 250°C.

[0241] The 19th embodiment includes a glass container of any of the first to 18 embodiments, wherein the smooth coating is thermally stable for 30 minutes at a temperature of at least about 260°C.

[0242] The 20th embodiment includes a glass container of any of the first to 19 embodiments, wherein the smooth coating is thermally stable for 30 minutes at a temperature of at least about 280°C.

[0243] The 21st embodiment includes a glass container of any of the first to 20th embodiments, wherein the smooth coating is a robust inorganic coating.

[0244] A 22nd aspect includes a glass container of the 21st aspect, wherein the robust inorganic coating is a metal nitride coating, a metal oxide coating, a metal sulfide coating, SiO2, diamond-like carbon, graphene, or a carbide coating.

[0245] A 23rd embodiment includes a glass container of the 21st embodiment, wherein the robust inorganic coating comprises at least one of tin, BN, HBN TiO2, Ta2O5, HfO2, Nb2O5, V2O5, SiO2, MoS2, SiC, SnO, SnO2, ZrO2, Al2O3, BN, ZnO, and BC.

[0246] The 24th embodiment includes a glass container of any of the first to 20 embodiments, wherein the smooth coating comprises a robust organic coating having a mass loss of less than 5% of its mass when heated to a temperature of 150°C to 350°C at a heating rate of about 10°C / minute.

[0247] A 25th embodiment includes a glass container of the 24th embodiment, wherein the robust organic coating comprises a polymer chemical composition.

[0248] A 26th embodiment includes a glass container of the 25th embodiment, wherein the robust organic coating further comprises a coupling agent.

[0249] The 27th embodiment includes a glass container of any of the first to 17th embodiments, wherein the smooth coating is a temporary coating.

[0250] The 28th embodiment includes a glass container of the 27th embodiment, wherein the temporary coating is thermally decomposed within one hour at a temperature of 300°C or less.

[0251] The 29th embodiment includes a glass container of either the 27th or 28th embodiment, wherein the temporary coating comprises a mixture of polyoxyethylene glycol, methacrylate resin, melamine formaldehyde resin, and polyvinyl alcohol.

[0252] The 30th embodiment includes a glass container of either the 27th or 29th embodiment, wherein the temporary coating contains one or more polysaccharides.

[0253] The 31st embodiment includes a glass container of any of the 27th to 30th embodiments, wherein the temporary coating contains polyacrylic acid or a derivative of polyacrylic acid.

[0254] The 32nd embodiment includes a glass container of any of the 27th to 31st embodiments, wherein the temporary coating contains an inorganic salt.

[0255] The 33rd aspect is a temporary coating made of: poly(ethylene oxide), poly(propylene oxide), ethylene oxide-propylene oxide copolymer, polyvinyl-pyrrolidinone, polyethyleneamine, poly(methyl vinyl ether), polyacrylamide, polymethacrylamide, polyurethane, poly(vinyl acetate), polyvinyl formal, polyacetal and acetal copolymers, polyformaldehyde, poly(alkyl methacrylate), methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, sodium carboxymethylcellulose, methylhydroxypropylcellulose, poly(acrylic acid) and its salts, poly(methacrylic acid) and its salts, ethylene-maleic anhydride copolymer, ethylene -Includes a glass container of any of the 27th to 32nd embodiments, comprising at least one of vinyl alcohol copolymer, ethylene-acrylic acid copolymer, vinyl acetate-vinyl alcohol copolymer, methyl vinyl ether-maleic anhydride copolymer, emulsifying polyurethane, polyoxyethylene stearate, and polyolefins including polyethylene, polypropylene and its copolymers, starch and modified starch, hydrophilic colloid, polyacryloamide, vegetable fat and animal fat, wax, tallow, soap, stearin-paraffin emulsion, polysiloxane of dimethyl or diphenyl or methyl / phenyl mixture, perfluorinated siloxane and other substituted siloxane, alkylsilane, aromatic silane, and oxidized polyethylene.

[0256] The 34th embodiment includes a glass container according to any of the first to 33 embodiments, wherein the light transmittance of the glass container having a smooth coating is approximately 55% or more of the light transmittance of the uncoated glass container for light wavelengths of approximately 400 nm to approximately 700 nm.

[0257] It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments described herein, without departing from the spirit and scope of the claimed subject matter. Therefore, this specification is intended to encompass various modifications and variations to the embodiments described herein, provided that such modifications and variations fall within the scope of the appended claims and their equivalents. Preferred embodiments of the present invention are described below in separate sections.

[0258] Embodiment 1 Coated glass pharmaceutical packaging, USP <660> A glass body formed from either a borosilicate glass composition that meets the criteria of Type 1 in accordance with the test, or an alkali aluminosilicate glass composition that has Class HGA1 hydrolysis resistance at the time of testing according to the ISO 720-1985 test, comprising the glass body having an inner surface, an outer surface, and a wall extending between them, The smooth coating has a thickness of less than 100 microns and is disposed on at least a portion of the outer surface. A portion of the outer surface of the coated glass pharmaceutical package having the smooth coating has a coefficient of friction at least 20% lower than that of an uncoated glass pharmaceutical package formed from a similar glass composition. A coated glass pharmaceutical package, wherein, at a light wavelength of approximately 400 nm to approximately 700 nm, the light transmittance through a portion of the outer surface of the coated glass pharmaceutical package is approximately 55% or more compared to the light transmittance through an uncoated glass pharmaceutical package.

[0259] Embodiment 2 A portion of the outer surface of the coated glass pharmaceutical package having the smooth coating has a coefficient of friction of 0.6 or less compared to a similar coated glass pharmaceutical package formed from a similar glass composition after the exothermic substance removal cycle. The coated glass pharmaceutical package according to Embodiment 1, wherein the exothermic substance removal cycle includes heating the coated glass pharmaceutical package to a temperature of at least 250°C in air for at least 30 minutes, and the coated glass pharmaceutical package is thermally stable after the exothermic substance removal cycle.

[0260] Embodiment 3 The coated glass pharmaceutical package according to Embodiment 2, wherein the smooth coating is thermally stable for 30 minutes at a temperature of at least 260°C.

[0261] Embodiment 4 The coated glass pharmaceutical package according to Embodiment 2, wherein the exothermic substance removal cycle includes heating the coated glass package to a temperature of about 250°C to about 400°C for at least 30 minutes.

[0262] Embodiment 5 The coated glass pharmaceutical package according to Embodiment 1, wherein the coefficient of friction of the coated glass pharmaceutical package is 0.5 or less compared to a similar coated glass pharmaceutical package formed from a similar glass composition. Embodiment 6 The coated glass pharmaceutical package according to Embodiment 1, wherein the glass body has acid resistance of at least Class S3 or higher in accordance with DIN 12116.

[0263] Embodiment 7 The coated glass pharmaceutical package according to Embodiment 1, wherein the smooth coating is an inorganic coating.

[0264] Embodiment 8 The coated glass pharmaceutical package according to Embodiment 1, wherein the smooth coating is an organic coating.

[0265] Embodiment 9 The coated glass pharmaceutical package according to Embodiment 1, wherein the smooth coating comprises a polymer chemical composition and a coupling agent, the coupling agent is in direct contact with the outer surface, and the polymer chemical composition is in direct contact with the coupling agent.

[0266] Embodiment 10 The coated glass pharmaceutical package according to Embodiment 1, wherein the coefficient of friction of the smooth coating does not increase by more than 30% after exposure to a freeze-drying cycle, and the freeze-drying cycle comprises filling the coated glass pharmaceutical package with a protein-containing liquid, then freezing the coated glass pharmaceutical package at a temperature of -100°C, and then sublimating the water at -15°C in a vacuum for 20 hours.

Claims

1. 1. A method for manufacturing a glass pharmaceutical container, comprising: providing a glass composition; melting the glass composition to form molten glass; forming the molten glass into a tube; converting the tube into a glass pharmaceutical container having an interior surface and an exterior surface, wherein the interior surface of the glass pharmaceutical container does not include a boron-rich layer when the glass pharmaceutical container is in an as-formed state; and coating the exterior surface of the glass pharmaceutical container with a lubricious coating, wherein the glass pharmaceutical container including the lubricious coating has a coefficient of friction of 0.7 or less, and the lubricious coating has a thickness of less than 100 μm. A method comprising:

2. The glass composition comprises: 65 mol % to 75 mol % SiO 2 , 6 mol% to 12.5 mol% Al 2 O 3 , 8 mol % to 15 mol % alkaline earth oxides; 5 mol % to 12 mol % alkali oxide, and 0 mol % to 0.5 mol % B 2 O 3 The method of claim 1 , comprising:

3. 10. The method of claim 1, further comprising subjecting the glass pharmaceutical container to depyrogenation, wherein the coefficient of friction does not increase by more than 30% after depyrogenation.

4. 4. The method of claim 3, wherein the depyrogenation comprises heating the glass pharmaceutical container having the smooth coating to a temperature of at least 250°C for at least 30 minutes.

5. 4. The method of claim 3, wherein the depyrogenation comprises heating the glass pharmaceutical container with the smooth coating at a temperature of at least 250°C for up to 72 hours.

6. 4. The method of claim 3, wherein the depyrogenation comprises heating the glass pharmaceutical container with the smooth coating at a temperature of from about 250°C to about 400°C for from about 30 minutes to about 72 hours.

7. The step of applying the smooth coating comprises: applying a layer of coupling agent directly contacting said exterior surface; and applying a polymer layer in direct contact with said coupling agent layer The method of claim 1 , comprising:

8. 10. The method of claim 1, further comprising subjecting the glass pharmaceutical container to a freeze-drying cycle, wherein the coefficient of friction does not increase by more than 30% after the freeze-drying cycle.

9. 9. The method of claim 8, wherein the freeze-drying cycle comprises filling the glass pharmaceutical container with a liquid containing a protein, then freezing the glass pharmaceutical container at a temperature of −100° C., and then sublimating the water under vacuum at −15° C. for 20 hours.